A Comparison of GFR Estimation Formulae in Pediatric Oncology - Rechenauer, Tobias; Zierk, Jakob; Graefe, Daniel; Rascher, Wolfgang; Rauh, Manfred; Metzler, Markus (Klinische Pädiatrie, 2018)
BACKGROUND: Application of potentially nephrotoxic chemotherapy requires continuous monitoring of renal function for toxicity and dosing. Novel pediatric glomerular filtration rate (GFR) estimating equations including cystatin C have been proposed to enhance the reliability of GFR calculation. MATERIALS AND METHODS: We examined a pediatric oncologic data set with a total of 363 GFR measurements. An analysis of distribution characteristics and comparison of medians was performed to compare creatinine and cystatin C-based GFR estimating formulae. Furthermore, we investigated the clinical impact of different equations in regard to therapeutic consequences. RESULTS: Significant differences in estimated GFR values were calculated depending on the applied formula (range of median GFR from 94.8 to 180.9 mL/min per 1.73 m2) which may result in different therapeutic consequences for the use of potentially nephrotoxic chemotherapeutic agents. Significant correlation for all examined formulae was identified, however there were large fluctuations among the correlation coefficients ranging from 0.254 to 1.0. CONCLUSION: This study compares proposed pediatric GFR estimating equations in a clinical setting. It underlines the current limitations and difficulties of GFR estimation including potential dosing errors. Cystitis C-based equations can be used as alternatives to creatinine-based estimations when the appropriate laboratory method has been applied. A comparative calculator for pediatric GFR estimating equations along with background information is provided at http://gfr.pedz.de and may support clinical decision-making.
EVALuna2:35479

Active visfatin is elevated in serum of maintenance haemodialysis patients and correlates inversely with circulating HDL cholesterol - Nuesken, Kai-Dietrich; Petrasch, Maurice; Rauh, Manfred; Stoehr, Wolfgang; Nuesken, Eva; Schneider, Holm; Dötsch, Jörg (Nephrology Dialysis Transplantation, 2009)
Background. Increased circulating visfatin may be associated both with endothelial damage and with increased mortality in end-stage renal disease (ESRD). HDL cholesterol is an independent, strong inverse predictor of cardiovascular events. However, associations between visfatin and parameters of lipid metabolism are unclear. Moreover, serum concentrations of visfatin measured by an enzyme immuno assay (EIA) are conflicting and do not correlate with ELISA (enzyme-linked immunosorbent assay) data, which predominantly detect enzymatically active visfatin.Methods. A total of 74 haemodialysis (HD) patients and 35 control individuals (C) were studied. All subjects (mean age 62.9 years) provided fasted blood samples (HD patients after 66-69 h without dialysis). Circulating visfatin was measured by the ELISA. Body composition was evaluated using waist circumference, skinfold thickness and body impedance analysis. Results obtained by the ELISA were compared with EIA data.Results. Active serum visfatin was increased in HD (5.58 ± 6.50 ngml) versus C 0.97 ± 1.79 ngml, mean ± SD; P < 0.0001 by multiple regression analysis (MRA) independently of plasma glucose, serum insulin, diabetes, HDL cholesterol and body composition. Within the HD group, only plasma HDL cholesterol (4 lower per additional mgdl HDL; P = 0.001) and insulin-treated diabetes mellitus subgroup of n = 18; 119 higher compared with patients without diabetes (n = 40); P = 0.011 were independently (by MRA) associated with active serum visfatin. Visfatin measured by an EIA showed no correlation with ELISA data.Conclusions. Our study provides reliable data on active visfatin in HD patients using a well-characterized ELISA. Loss of renal function is accompanied by increased circulating active visfatin concentrations in our patients. Furthermore, decreased HDL cholesterol may hint at an increased probability of cardiovascular events in HD patients with elevated serum visfatin.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Body composition; Diabetes; End-stage renal disease; HDL cholesterol; Visfatin

Adaptive physiological water conservation explains hypertension and muscle catabolism in experimental chronic renal failure - Kovarik, Johannes; Morisawa, Norihiko; Wild, Johannes; Marton, Adriana; Takase-Minegishi, Kaoru; Minegishi, Shintaro; Daub, Steffen; Sands, Jeff M.; Klein, Janet D.; Bailey, James L.; Kovalik, Jean Paul; Rauh, Manfred; et al. (Acta Physiologica, 2021)
Aim: We have reported earlier that a high salt intake triggered an aestivation-like natriuretic-ureotelic body water conservation response that lowered muscle mass and increased blood pressure. Here, we tested the hypothesis that a similar adaptive water conservation response occurs in experimental chronic renal failure. Methods: In four subsequent experiments in Sprague Dawley rats, we used surgical 5/6 renal mass reduction (5/6 Nx) to induce chronic renal failure. We studied solute and water excretion in 24-hour metabolic cage experiments, chronic blood pressure by radiotelemetry, chronic metabolic adjustment in liver and skeletal muscle by metabolomics and selected enzyme activity measurements, body Na+, K+ and water by dry ashing, and acute transepidermal water loss in conjunction with skin blood flow and intra-arterial blood pressure. Results: 5/6 Nx rats were polyuric, because their kidneys could not sufficiently concentrate the urine. Physiological adaptation to this renal water loss included mobilization of nitrogen and energy from muscle for organic osmolyte production, elevated norepinephrine and copeptin levels with reduced skin blood flow, which by means of compensation reduced their transepidermal water loss. This complex physiologic-metabolic adjustment across multiple organs allowed the rats to stabilize their body water content despite persisting renal water loss, albeit at the expense of hypertension and catabolic mobilization of muscle protein. Conclusion: Physiological adaptation to body water loss, termed aestivation, is an evolutionary conserved survival strategy and an under-studied research area in medical physiology, which besides hypertension and muscle mass loss in chronic renal failure may explain many otherwise unexplainable phenomena in medicine.
CRIS-Team Scopus Importer:2021-03-19
Keywords: aestivation; body sodium; body water; dehydration; double-barrier concept; glucose-alanine-shuttle; glycine methylation; hepato-renal; hypertension; kidney; liver; muscle mass loss; organic osmolytes; purine metabolism; skin; transamination; transepidermal water loss; urea cycle; urine concentration

Adenosine-generating CD39+ plasmablasts predispose to successful infliximab therapy in pediatric IBD - Schnell, Alexander; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Schuh, Wolfgang; Regensburger, Adrian; Rauh, Manfred; Wölfle, Joachim; Hörning, André (Life Science Alliance, 2025)
B cells display several immunoregulatory mechanisms including the production of interleukin-10. Ectonucleotidases like CD39 and CD73 influence immune homeostasis by metabolizing eATP and generating immunosuppressive adenosine. The major objective was to examine the expression of those immunoregulatory molecules on B-cell subsets, and, more specifically, to determine their association with an infliximab (IFX) treatment in a pediatric inflammatory bowel disease (IBD) cohort. 42 IBD patients were assessed for IFX response after 12 mo of therapy and compared against 14 healthy controls (HC). Although IL10-producing plas-mablasts were decreased in IFX nonresponders (NRS), we de-tected an up-regulation of CD39 on plasmablasts and increased fractions of CD39/CD73-co-expressing naïve and memory B cells in responding patients (RS). In addition, B cells of responders proved to have superior ATP degradation capacities and aden-osine production before therapy initiation compared with NRS and HC. Moreover, IFX nonresponders had a marked deficiency of α4β7hi plasmablasts, whereas both cohorts had fewer CCR9-expressing plasmablasts. Consequently, CD39+ plasmablasts were decreased in biopsies of inflamed mucosal tissues, espe-cially in IFX nonresponders. Our results highlight the regulatory potential of CD39/CD73-expressing B cells in pediatric IBD and suggest CD39+ plasmablasts as a potential determinant of a successful immunosuppressive therapy with IFX.
CRIS-Team Scopus Importer:2025-05-02

Adhesive blood microsampling systems for steroid measurement via LC-MS/MS in the rat - Heussner, Kirsten; Rauh, Manfred; Cordasic, Nada; Menendez-Castro, Carlos; Hübner, Hanna; Rübner, Matthias; Schmidt, Marius; Hartner, Andrea; Rascher, Wolfgang; Fahlbusch, Fabian B. (Steroids, 2017)
INTRODUCTION: Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS) allows for the direct analysis of multiple hormones in a single probe with minimal sample volume. Rodent-based animal studies strongly rely on microsampling, such as the dry blood spot (DBS) method. However, DBS suffers the drawback of hematocrit-dependence (non-volumetric). Hence, novel volumetric microsampling techniques were introduced recently, allowing sampling of fixed accurate volumes. We compared these methods for steroid analysis in the rat to improve inter-system comparability. EXPERIMENTAL: We analyzed steroid levels in blood using the absorptive microsampling devices Whatman® 903 Protein Saver Cards, Noviplex™ Plasma Prep Cards and the Mitra™ Microsampling device and compared the obtained results to the respective EDTA plasma levels. Quantitative steroid analysis was performed via LC-MS/MS. For the determination of the plasma volume factor for each steroid, their levels in pooled blood samples from each human adults and rats (18weeks) were compared and the transferability of these factors was evaluated in a new set of juvenile (21days) and adult (18weeks) rats. Hematocrit was determined concomitantly. RESULTS: Using these approaches, we were unable to apply one single volume factor for each steroid. Instead, plasma volume factors had to be adjusted for the recovery rate of each steroid and device individually. The tested microsampling systems did not allow the use of one single volume factor for adult and juvenile rats based on an unexpectedly strong hematocrit-dependency and other steroid specific (pre-analytic) factors. DISCUSSION: Our study provides correction factors for LC-MS/MS steroid analysis of volumetric and non-volumetric microsampling systems in comparison to plasma. It argues for thorough analysis of chromatographic effects before the use of novel volumetric systems for steroid analysis.
EVALuna2:34007

Adrenarche and pubarche in girls with turner syndrome during growth-promoting therapy with human growth hormone - Dörr, Helmuth-Günther; Penger, Theresa; Marx, Martin; Rauh, Manfred; Oppelt, Patricia; Völkl, Thomas (BMC Endocrine Disorders, 2019)
Background: Data on adrenarche and pubarche in girls with Turner syndrome (TS) are inconsistent in the literature. Methods: The cohort consisted of 94 girls and young women with TS born between 1971 and 2001 (age range: 3.1-23.2 yrs.), who were treated with human growth hormone and regularly presented at our outpatient clinic every 4 to 6 months.The longitudinal data of all patients were ascertained retrospectively from patient charts. The data collection ended in January 2016. Adrenarche was assessed by serum DHEAS levels and pubertal status by Tanner stages. Pubarche was defined as the appearance of pubic hair (PH2), whereas spontaneous puberty was defined as Tanner stage B2. The patients were retrospectively subdivided in two groups with regard to pubertal development: group 1 (n = 21) with spontaneous puberty and group 2 (n = 70) with induced puberty. Since blood samples were not taken at every visit, we generated seven groups according to the age of the children at which the blood samples were taken: 3-5, 5-7, 7-9, 9-11, 11-13, 13-15, and 15-17 yrs. Serum DHEAS and follicle-stimulating hormone (FSH) levels were measured by chemiluminescence immunoassay and compared with those of a control group of healthy girls. Results: Adrenarche started in TS girls between 5 and 7 years. TS girls had higher DHEAS levels than the control group, with statistically significant differences in the age groups 7 to 17 years. No differences were determined between the TS girls with spontaneous puberty and those with POI. TS girls in group 2 reached the Tanner stages PH2 (p < 0.04), PH3 (p < 0.01), PH4 and PH5 (p < 0.001) markedly later than TS girls in group 1. Conclusions: The onset of adrenarche in girls with TS undergoing GH therapy does not differ from that in healthy girls. However, adrenarche is more pronounced in girls with TS. There is no difference in DHEAS levels between the TS girls with spontaneous puberty and the TS girls with primary ovarian insufficiency (POI), while the tempo of pubarche is markedly slower in the girls with POI.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adrenarche; DHEAS; Primary ovarian insufficiency; Turner syndrome

Aestivation motifs explain hypertension and muscle mass loss in mice with psoriatic skin barrier defect - Wild, Johannes; Jung, Rebecca; Knopp, Tanja; Efentakis, Panagiotis; Benaki, Dimitra; Grill, Alexandra; Wegner, Joanna; Molitor, Michael; Garlapati, Venkata; Rakova, Natalia; Markó, Lajos; Marton, Adriana; et al. (Acta Physiologica, 2021)
Aim: Recent evidence suggests that arterial hypertension could be alternatively explained as a physiological adaptation response to water shortage, termed aestivation, which relies on complex multi-organ metabolic adjustments to prevent dehydration. Here, we tested the hypothesis that chronic water loss across diseased skin leads to similar adaptive water conservation responses as observed in experimental renal failure or high salt diet. Methods: We studied mice with keratinocyte-specific overexpression of IL-17A which develop severe psoriasis-like skin disease. We measured transepidermal water loss and solute and water excretion in the urine. We quantified glomerular filtration rate (GFR) by intravital microscopy, and energy and nitrogen pathways by metabolomics. We measured skin blood flow and transepidermal water loss (TEWL) in conjunction with renal resistive indices and arterial blood pressure. Results: Psoriatic animals lost large amounts of water across their defective cutaneous epithelial barrier. Metabolic adaptive water conservation included mobilization of nitrogen and energy from muscle to increase organic osmolyte production, solute-driven maximal anti-diuresis at normal GFR, increased metanephrine and angiotensin 2 levels, and cutaneous vasoconstriction to limit TEWL. Heat exposure led to cutaneous vasodilation and blood pressure normalization without parallel changes in renal resistive index, albeit at the expense of further increased TEWL. Conclusion: Severe cutaneous water loss predisposes psoriatic mice to lethal dehydration. In response to this dehydration stress, the mice activate aestivation-like water conservation motifs to maintain their body hydration status. The circulatory water conservation response explains their arterial hypertension. The nitrogen-dependency of the metabolic water conservation response explains their catabolic muscle wasting.
CRIS-Team Scopus Importer:2021-03-05
Keywords: aestivation; catabolism; dehydration; double barrier concept; hypertension; transepidermal water loss

Age- and sex-specific dynamics in 22 hematologic and biochemical analytes from birth to adolescence - Zierk, Jakob; Arzideh, Farhad; Rechenauer, Tobias; Haeckel, Rainer; Rascher, Wolfgang; Metzler, Markus; Rauh, Manfred (Clinical Chemistry, 2015)
Pediatric laboratory test results must be interpreted in the context of interindividual variation and age- and sex-dependent dynamics. Reference intervals as presently defined for separate age groups can only approximate the age-related dynamics encountered in pediatrics. Continuous reference intervals from birth to adulthood are not available for most laboratory analytes because of the ethical and practical constraints of defining reference intervals using a population of healthy community children. We applied an indirect method to generate continuous reference intervals for 22 hematologic and biochemical analytes by analyzing clinical laboratory data from blood samples taken during clinical care of patients.We included samples from 32 000 different inpatients and outpatients (167 000 samples per analyte) from a German pediatric tertiary care center. Measurements were performed on a Sysmex-XE 2100 and a Cobas Integra 800 during clinical care over a 6-year period. The distribution of samples considered normal was estimated with an established indirect statistical approach and used for the calculation of reference intervals.We provide continuous reference intervals from birth to adulthood for 9 hematology analytes (hemoglobin, hematocrit, red cell indices, red cell count, red cell distribution width, white cell count, and platelet count) and 13 biochemical analytes (sodium, chloride, potassium, calcium, magnesium, phosphate, creatinine, aspartate transaminase, alanine transaminase, ?-glutamyltransferase, alkaline phosphatase, lactate dehydrogenase, and total protein).Continuous reference intervals capture the population changes in laboratory analytes during pediatric development more accurately than age groups. After local validation, the reference intervals provided should allow a more precise consideration of these dynamics in clinical decision making.
EVALuna2:18920

Age- and sex-specific pediatric reference intervals for neutrophil-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and platelet-to-lymphocyte ratio - Moosmann, Julia; Krusemark, Anja; Dittrich, Sven; Ammer, Tatjana; Rauh, Manfred; Wölfle, Joachim; Metzler, Markus; Zierk, Jakob (International Journal of Laboratory Hematology, 2021)
Introduction: Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are emerging biomarkers for systemic inflammation and have been shown to predict morbidity and mortality for several diseases. However, lack of pediatric reference intervals (RIs) prevents their comprehensive use in patient care and medical research. Material and Methods: We calculated reference intervals and corresponding confidence intervals for NLR, PLR, and LMR from birth to 18 years using a data-mining approach: We analyzed 232 746 blood counts from 60 685 patients performed during patient care and excluded patients with elevated C-reactive protein and procalcitonin. Test results were separated according to age and sex, and the distribution of physiological ratios was estimated using an indirect approach (refineR). Additionally, we investigated the ratios’ diagnostic benefit for different inflammatory diseases (acute appendicitis, asthma, Bell's palsy, Henoch-Schonlein purpura, and cystic fibrosis) using the newly obtained reference intervals. Results: We estimated age- and sex-specific reference intervals from birth to adulthood for NLR, PLR, and LMR. Analyses in pediatric inflammatory diseases showed that PLR and LMR were poor markers to detect the examined inflammatory diseases, while NLR was significantly increased in patients with appendicitis and asthma. Conclusion: We provide pediatric reference intervals for NLR, PLR, and LMR to improve the interpretation of these biomarkers in children.
CRIS-Team Scopus Importer:2021-12-03
Keywords: blood components; inflammation; leukocytes; monocytes; neutrophils; platelets

Agreement Between 24-Hour Salt Ingestion and Sodium Excretion in a Controlled Environment - Lerchl, Kathrin; Rakova, Natalia; Dahlmann, Anke; Rauh, Manfred; Goller, Ulrike; Basner, Mathias; Dinges, David F.; Beck, Luis; Agureev, Alexander; Larina, Irina; Baranov, Victor; Morukov, Boris; et al. (Hypertension, 2015)
Accurately collected 24-hour urine collections are presumed to be valid for estimating salt intake in individuals. We performed 2 independent ultralong-term salt balance studies lasting 105 (4 men) and 205 (6 men) days in 10 men simulating a flight to Mars. We controlled dietary intake of all constituents for months at salt intakes of 12, 9, and 6 g/d and collected all urine. The subjects' daily menus consisted of 27 279 individual servings, of which 83.0% were completely consumed, 16.5% completely rejected, and 0.5% incompletely consumed. Urinary recovery of dietary salt was 92% of recorded intake, indicating long-term steady-state sodium balance in both studies. Even at fixed salt intake, 24-hour urine collection for sodium excretion (UNaV) showed infradian rhythmicity. We defined a ±25 mmol deviation from the average difference between recorded sodium intake and UNaV as the prediction interval to accurately classify a 3-g difference in salt intake. Because of the biological variability in UNaV, only every other daily urine sample correctly classified a 3-g difference in salt intake (49%). By increasing the observations to 3 consecutive 24-hour collections and sodium intakes, classification accuracy improved to 75%. Collecting seven 24-hour urines and sodium intake samples improved classification accuracy to 92%. We conclude that single 24-hour urine collections at intakes ranging from 6 to 12 g salt per day were not suitable to detect a 3-g difference in individual salt intake. Repeated measurements of 24-hour UNaV improve precision. This knowledge could be relevant to patient care and the conduct of intervention trials.
EVALuna2:3790

A high-salt diet compromises antibacterial neutrophil responses through hormonal perturbation - Jobin, Katarzyna; Stumpf, Natascha E.; Schwab, Sebastian; Eichler, Melanie; Neubert, Patrick; Rauh, Manfred; Adamowski, Marek; Babyak, Olena; Hinze, Daniel; Sivalingam, Sugirthan; Weisheit, Christina; Hochheiser, Katharina; et al. (Science Translational Medicine, 2020)
The Western diet is rich in salt, which poses various health risks. A high-salt diet (HSD) can stimulate immunity through the nuclear factor of activated T cells 5 (Nfat5)-signaling pathway, especially in the skin, where sodium is stored. The kidney medulla also accumulates sodium to build an osmotic gradient for water conservation. Here, we studied the effect of an HSD on the immune defense against uropathogenic E. coli-induced pyelonephritis, the most common kidney infection. Unexpectedly, pyelonephritis was aggravated in mice on an HSD by two mechanisms. First, on an HSD, sodium must be excreted; therefore, the kidney used urea instead to build the osmotic gradient. However, in contrast to sodium, urea suppressed the antibacterial functionality of neutrophils, the principal immune effectors against pyelonephritis. Second, the body excretes sodium by lowering mineralocorticoid production via suppressing aldosterone synthase. This caused an accumulation of aldosterone precursors with glucocorticoid functionality, which abolished the diurnal adrenocorticotropic hormone-driven glucocorticoid rhythm and compromised neutrophil development and antibacterial functionality systemically. Consistently, under an HSD, systemic Listeria monocytogenes infection was also aggravated in a glucocorticoid-dependent manner. Glucocorticoids directly induced Nfat5 expression, but pharmacological normalization of renal Nfat5 expression failed to restore the antibacterial defense. Last, healthy humans consuming an HSD for 1 week showed hyperglucocorticoidism and impaired antibacterial neutrophil function. In summary, an HSD suppresses intrarenal neutrophils Nfat5-independently by altering the local microenvironment and systemically by glucocorticoid-mediated immunosuppression. These findings argue against high-salt consumption during bacterial infections.
CRIS-Team Scopus Importer:2020-04-07

Aloxe3 knockout mice reveal a function of epidermal lipoxygenase-3 as hepoxilin synthase and its pivotal role in barrier formation - Krieg, Peter; Rosenberger, Sabine; De Juanes, Silvia; Latzko, Susanne; Hou, Jin; Dick, Angela; Kloz, Ulrich; Van Der Hoeven, Frank; Hausser, Ingrid; Esposito, Irene; Rauh, Manfred; Schneider, Holm (Journal of Investigative Dermatology, 2013)
Loss-of-function mutations in the lipoxygenase (LOX) genes ALOX12B and ALOXE3 are the second most common cause of autosomal recessive congenital ichthyosis. The encoded proteins, 12R-LOX and epidermal LOX-3 (eLOX-3), act in sequence to convert fatty acid substrates via R-hydroperoxides to specific epoxyalcohol derivatives and have been proposed to operate in the same metabolic pathway during epidermal barrier formation. Here, we show that eLOX-3 deficiency in mice results in early postnatal death, associated with similar but somewhat less severe barrier defects and morphological changes than reported earlier for the 12R-LOX-knockout mice. Skin lipid analysis demonstrated that the severity of barrier failure is related to the loss of covalently bound ceramides in both 12R-LOX- and eLOX-3-null mice, confirming a proposed functional linkage of the LOX pathway to ceramide processing and formation of the corneocyte lipid envelope. Furthermore, analysis of free oxygenated fatty acid metabolites revealed strongly reduced levels of hepoxilin metabolites in eLOX-3-deficient epidermis, indicating an additional function of eLOX-3 in mammalian skin as a hepoxilin synthase linked to the 12S-LOX pathway. © 2013 The Society for Investigative Dermatology.
CRIS-Team Scopus Importer:2020-07-01

Altered patterns of heartbeat-evoked potentials in depersonalization/derealization disorder: neurophysiological evidence for impaired cortical representation of bodily signals - Schulz, Andre; Koester, Susann; Beutel, Manfred E.; Schaechinger, Hartmut; Voegele, Claus; Rost, Silke; Rauh, Manfred; Michal, Matthias (Psychosomatic Medicine, 2015)
Core features of depersonalization/derealization disorder (DPD) are emotional numbing and feelings of disembodiment. Although there are several neurophysiological findings supporting subjective emotional numbing, the psychobiology of disembodiment remains unclear.Heartbeat-evoked potentials (HEPs), which are considered psychophysiological indicators for the cortical representation of afferent signals originating from the cardiovascular system, were assessed in 23 patients with DPD and 24 healthy control individuals during rest and while performing a heartbeat perception task.Absolute HEP amplitudes did not differ between groups. Nevertheless, healthy individuals showed higher HEPs during the heartbeat perception task than during rest, whereas no such effect was found in patients with DPD (p = .031). Patients with DPD had higher total levels of salivary ?-amylase than did healthy individuals (9626.6 [8200.0] versus 5344.3 [3745.8] kU min/l; p = .029), but there were no group differences in cardiovascular measures (heart rate = 76.2 [10.1] versus 74.3 [7.5] beats/min, p = .60; normalized low-frequency heart rate variability = 0.63 [0.15] versus 0.56 [0.15] normalized units, p = .099; low frequency/high frequency ratio = 249.3 [242.7] versus 164.8 [108.8], p = .10), salivary cortisol (57.5 [46.7] versus 55.1 [43.6] nmol min/l, p = .86), or cortisone levels (593.2 [260.3] versus 543.8 [257.1] nmol min/l, p = .52).These results suggest altered cortical representation of afferent signals originating from the cardiovascular system in patients with DPD, which may be associated with higher sympathetic tone. These findings may reflect difficulties of patients with DPD to attend to their actual bodily experiences.
EVALuna2:18929

A mathematical model of white blood cell dynamics during maintenance therapy of childhood acute lymphoblastic leukemia - Le, Thuy T.T.; Jost, Felix; Raupach, Thomas; Zierk, Jakob; Rauh, Manfred; Suttorp, Meinolf; Stanulla, Martin; Metzler, Markus; Sager, Sebastian (Mathematical Medicine and Biology, 2019)
Acute lymphoblastic leukemia is the most common malignancy in childhood and requires prolonged oral maintenance chemotherapy to prevent disease relapse after remission induction with intensive intravenous chemotherapy. In maintenance therapy, drug doses of 6-mercaptopurine (6-MP) and methotrexate (MTX) are adjusted to achieve sustained antileukemic activity without excessive myelosuppression. However, uncertainty exists regarding timing and extent of drug dose responses and optimal dose adaptation strategies. We propose a novel comprehensive mathematical model for 6-MP and MTX pharmacokinetics, pharmacodynamics and myelosuppression in acute lymphoblastic maintenance therapy. We personalize and cross-validate the mathematical model using clinical data and propose a real-time algorithm to predict chemotherapy responses with a clinical decision support system as a potential future application.
CRIS-Team Scopus Importer:2019-12-24
Keywords: chemotherapy; childhood acute lymphoblastic leukemia; maintenance therapy; ordinary differential equations; parameter estimation; real-time algorithm

A mouse organotypic tissue culture model for autosomal recessive congenital ichthyosis - Rosenberger, S.; Dick, Angela; Latzko, S.; Hausser, I.; Stark, H. -J.; Rauh, Manfred; Schneider, Holm; Krieg, P. (British Journal of Dermatology, 2014)
Autosomal recessive congenital ichthyoses (ARCIs) are keratinization disorders caused by impaired skin barrier function. Mutations in the genes encoding the lipoxygenases 12R-LOX and eLOX-3 are the second most common cause of ARCIs. In recent years, human skin equivalents recapitulating the ARCI phenotype have been established.To develop a murine organotypic tissue culture model for ARCI.Epidermal keratinocytes were isolated from newborn 12R-LOX-deficient mice and cocultivated with mouse dermal fibroblasts embedded in a scaffold of native collagen type I.With this experimental set-up the keratinocytes formed a well-organized multilayered stratified epithelium resembling skin architecture in vivo. All epidermal layers were present and the keratinocytes within showed the characteristic morphological features. Markers for differentiation and maturation indicated regular epidermal morphogenesis. The major components of epidermal structures were expressed, and were obviously processed and assembled properly. In contrast to their wild-type counterparts, 12R-LOX-deficient skin equivalents showed abnormal vesicular structures in the upper epidermal layers correlating with altered lipid composition and increased transepidermal water loss, comparable with 12R-LOX-deficient mice.The mouse skin equivalents faithfully recapitulate the 12R-LOX-deficient phenotype observed in vivo, classifying them as appropriate in vitro models to study molecular mechanisms involved in the development of ARCI and to evaluate novel therapeutic agents. In contrast to existing human three-dimensional skin models, the generation of these murine models is not constrained by a limited supply of material and does not depend on in vitro expansion and/or genetic manipulations that could result in inadvertent genotypic and phenotypic alterations.
EVALuna2:18903

Angiotensin pathways under therapy with empagliflozin in patients with chronic heart failure - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Rauh, Manfred; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2023)
Aims: Large outcome studies demonstrated a reduction of heart failure hospitalization or cardiovascular death in patients with chronic heart failure (CHF). The renin–angiotensin system (RAS) is a key player in fluid and sodium regulation. The classic angiotensin-converting enzyme–angiotensin II–angiotensin-1 receptor axis (Ang I–ACE–Ang II receptor axis) is predominantly angiotensin II (Ang-II) induced and promotes vasoconstriction. In contrast, the angiotensin-converting-enzyme-2–angiotensin-(1-7)–Mas axis (Mas-axis) is mediated by the metabolites angiotensin-1-7 (Ang-(1-7)) and angtiotensin-1-5 (Ang-(1-5)) and exerts cardioprotective effects. Methods: We previously investigated the effect of empagliflozin on the systemic haemodynamic in patients with stable CHF (NYHA II–III) in a randomized placebo-controlled clinical trial ‘Analysing the Effect of Empagliflozin on Reduction of Tissue Sodium Content in Patients With Chronic Heart Failure (ELSI)’. In a post hoc analysis, we now analysed whether empagliflozin has an effect on the RAS by measuring detailed RAS profiles (LC-MS/MS-based approach) in 72 patients from ELSI. We compared RAS parameters after 1-month and 3-months treatment with empagliflozin or placebo to baseline. The secondary goal was to analyse whether the effect of empagliflozin on RAS parameters was dependent on angiotensin-receptor-blocking (ARB) or angiotensin-converting-enzyme-inhibitor (ACEI) co-medication. Results: Empagliflozin medication induced a significant rise in Ang-II [68.5 pmol/L (21.3–324.2) vs. 131.5 pmol/L (34.9–564.0), P = 0.001], angiotensin-I (Ang-I) [78.7 pmol/L (21.5–236.6) vs. 125.9 pmol/L (52.6–512.9), P < 0.001], Ang-(1-7) [3.0 pmol/L (3.0–15.0) vs. 10.1 pmol/L (3.0–31.3), P = 0.006], and Ang-(1-5) [5.4 pmol/L (2.0–22.9) vs. 9.9 pmol/L (2.8–36.4), P = 0.004], which was not observed in the placebo group (baseline to 3-months treatment). A significant rise in Ang-II (206.4 pmol/L (64.2–750.6) vs. 568.2 pmol/L (164.7–1616.4), P = 0.001), Ang-(1-7) (3.0 pmol/L (3.0–14.1) vs. 15.0 pmol/L (3.0–31.3), P = 0.017), and Ang-(1-5) [12.2 pmol/L (3.8–46.6) vs. 36.4 pmol/L (11.1–90.7), P = 0.001] under empagliflozin treatment was only seen in the subgroup of patients with ARB co-medication, whereas no change of Ang-II (16.7 pmol/L (2.0–60.8) vs. 26.4 pmol/L (10.7–63.4), P = 0.469), Ang-(1-7) (6.6 pmol/L (3.0–20.7) vs. 10.5 pmol/L (3.0–50.5), P = 0.221), and Ang-(1-5) (2.7 pmol/L (2.0–8.4) vs. 2.8 pmol/L (2.0–6.9), P = 0.851) was observed in patients with empagliflozin that were on ACEI co-medication (baseline to 3-months treatment). Conclusions: Our data indicate that empagliflozin might lead to an activation of both the Ang I–ACE–Ang II receptor axis and the Mas-axis pathway. Activation of the Ang I–ACE–Ang II receptor axis and the protective Mas-axis pathway after initiating treatment with empagliflozin was only seen in patients with ARB co-medication, in contrast to co-medication with ACEI.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Angiotensin profiles; Cardioprotective effects; Chronic heart failure; Empagliflozin; Renin–angiotensin system

An isotope dilution LC–MS/MS-based candidate reference method for the quantification of androstenedione in human serum and plasma - Gradl, Katrin; Taibon, Judith; Singh, Neeraj; Albrecht, Eva; Geistanger, Andrea; Pongratz, Stephan; Hutzler, Stefan; Mayer, Magdalena; Kleinschmidt, Christine; Geletneky, Christian; Hofmann, Verena; Köppl, Daniel; et al. (Clinical Mass Spectrometry, 2020)
The accurate measurement of androstenedione in human serum and plasma is required for steroid profiling to assure the appropriate diagnosis and differential diagnosis of hyperandrogenism. In this work, we introduce an isotope dilution liquid chromatography–tandem mass spectrometry (LC–MS/MS) candidate reference measurement procedure for the quantification of androstenedione in human serum and plasma. The performance of the procedure enables its use in the evaluation and standardization of routine assays and for the evaluation of patient samples to ensure the traceability of individual patient results. As the primary standard, a certified reference material from NMIA (National Measurement Institute, Australia) was used. Additionally, a quantitative nuclear magnetic resonance (qNMR) method was developed for the value assignment of the primary reference material, which ensures the direct traceability to SI units, as well as the independence from the availability of reference materials. 13C3-labeled androstenedione was used as the internal standard. The introduced method allows the measurement of androstenedione in the range of 0.05–12 ng/mL, and the assay imprecision was found to be <2% between 5 and 12 ng/mL, 3.5% at 1.5 ng/mL, and 5.2% at 0.05 ng/mL, with an accuracy of 95–105% for the serum and 91–103% for the plasma matrix. The transferability to a second laboratory was validated by method comparison based on 112 patient samples. The comparison of the results obtained from the presented method and an LC–MS/MS routine assay, using 150 native patient samples, showed a good correlation with a bias of the routine method of ≤4.0%.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Androstenedione; Human serum; LC–MS/MS; Quantitative NMR; Reference measurement procedure

An isotope dilution-liquid chromatography-tandem mass spectrometry-based candidate reference measurement procedure for the quantification of cortisol in human serum and plasma - Ott, Myriam; Singh, Neeraj; Bauland, Friederike; Köppl, Daniel; Kandler, Kerstin; Gaudl, Alexander; Geistanger, Andrea; Ceglarek, Uta; Rauh, Manfred; Geletneky, Christian; Taibon, Judith (Clinical Chemistry and Laboratory Medicine, 2025)
Accurate measurement of serum cortisol is crucial for the diagnosis and management of adrenal disorders. Thus, we have developed a novel isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC MS/MS)-based candidate reference measurement procedure (RMP) to quantify cortisol in human serum/plasma, offering higher sensitivity and reliability compared to existing RMPs. Quantitative Nuclear Magnetic Resonance spectroscopic (qNMR) methodology has been utilized to assign the absolute content (g/g) and SI-traceability to the reference materials. A novel two-dimensional heart-cut liquid chromatography (LC) approach was implemented for the LC-MS/MS, combined with a supported liquid extraction (SLE) sample preparation protocol. A multi-day validation experiment assessed precision and accuracy. Reproducibility was assessed by comparing procedure results between two independent laboratories, and measurement uncertainty (MU) was evaluated in compliance with current guidelines. The established RMP exhibited high sensitivity, with a quantification range of 0.800-600 » ng/mL (2.21-1,655 » nmol/L), exceeding the ranges of existing JCTLM-listed RMPs. Intermediate precision was ≤2.6 » %, and repeatability ranged from 0.9 to 1.9 » % across all concentration levels. The relative mean bias ranged from -1.3 to 1.4 » % for all matrices and concentration levels. Measurement uncertainties (MU) for cortisol in single measurements were ≤2.8 » % regardless of the concentration level and sample type. Using the certified International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) reference panel, the equivalence between the candidate RMP and the Joint Committee on Traceability in Laboratory Medicine (JCTLM) listed RMPs (NRMeth 57 and NRMeth 8) was assessed, revealing excellent agreement. This RMP allows for highly sensitive and reproducible determination of cortisol. The performance of the RMP facilitates the standardization of routine assays and ensures traceability in the measurement of individual patient samples.
CRIS-Team Scopus Importer:2025-02-28
Keywords: cortisol; isotope dilution-liquid chromatography-tandem mass spectrometry; qNMR characterization; reference measurement procedure; SI units; traceability

An isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC-MS/MS)-based candidate reference measurement procedure (RMP) for the quantification of aldosterone in human serum and plasma - Taibon, Judith; Santner, Tobias; Singh, Neeraj; Ibrahim, Sara Cheikh; Babitzki, Galina; Koeppl, Daniel; Gaudl, Alexander; Geistanger, Andrea; Ceglarek, Uta; Rauh, Manfred; Geletneky, Christian (Clinical Chemistry and Laboratory Medicine, 2023)
Objectives: An isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC MS/MS)-based candidate reference measurement procedure (RMP) for aldosterone quantification in human serum and plasma is presented.Methods: The material used in this RMP was characterized by quantitative nuclear magnetic resonance (qNMR) to assure traceability to SI Units. For liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis a two-dimensional heart cut LC approach, in combination with an optimal supported liquid extraction protocol, was established for the accurate analysis of aldosterone in human serum and plasma in order to minimize matrix effects and avoid the co-elution of interferences. Assay validation was performed according to current guidelines. Selectivity and specificity were assessed using spiked serum; potential matrix effects were examined by a post column infusion experiment and the comparison of standard line slopes. An extensive protocol over 5 days was applied to determine precision, accuracy and trueness. Measurement uncertainty was evaluated according to the Guide to the Expression of Uncertainty in Measurement (GUM), for which three individual sample preparations were performed on at least two different days.Results: The RMP allowed aldosterone quantification within the range of 20-1,200 pg/mL without interference from structurally-related compounds and no evidence of matrix effects. Intermediate precision was =4.7% and repeatability was 2.8-3.7% for all analyte concentrations. The bias ranged between -2.2 and 0.5% for all levels and matrices. Total measurement uncertainties for target value assignment (n=6) were found to be =2.3%; expanded uncertainties were =4.6% (k=2) for all levels.Conclusions: The RMP showed high analytical performance for aldosterone quantification in human serum and plasma. The traceability to SI units was established by qNMR content determination of aldosterone, which was utilized for direct calibration of the RMP. Thus, this candidate RMP is suitable for routine assay standardization and evaluation of clinical samples.
CRIS-Team WoS Importer:2023-04-21

A pipeline for the fully automated estimation of continuous reference intervals using real-world data - Ammer, Tatjana; Schützenmeister, André; Prokosch, Hans-Ulrich; Rauh, Manfred; Rank, Christopher M.; Zierk, Jakob (Scientific Reports, 2023)
Reference intervals are essential for interpreting laboratory test results. Continuous reference intervals precisely capture physiological age-specific dynamics that occur throughout life, and thus have the potential to improve clinical decision-making. However, established approaches for estimating continuous reference intervals require samples from healthy individuals, and are therefore substantially restricted. Indirect methods operating on routine measurements enable the estimation of one-dimensional reference intervals, however, no automated approach exists that integrates the dependency on a continuous covariate like age. We propose an integrated pipeline for the fully automated estimation of continuous reference intervals expressed as a generalized additive model for location, scale and shape based on discrete model estimates using an indirect method (refineR). The results are free of subjective user-input, enable conversion of test results into z-scores and can be integrated into laboratory information systems. Comparison of our results to established and validated reference intervals from the CALIPER and PEDREF studies and manufacturers’ package inserts shows good agreement of reference limits, indicating that the proposed pipeline generates high-quality results. In conclusion, the developed pipeline enables the generation of high-precision percentile charts and continuous reference intervals. It represents the first parameter-less and fully automated solution for the indirect estimation of continuous reference intervals.
CRIS-Team Scopus Importer:2023-09-01

Arginase 1 functions as anti-resolvin in inflammatory bowel disease - Nuese, B.; Gänsbauer, Maximilian; Baier, J.; Mattner, Jochen; Gerlach, Roman; Wirtz, Stefan; Rauh, Manfred (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Arginase 1 of myeloid cells accounts for disease chronicity in Leishmania mexicana-infected mice - Rai, Baplu; Debus, Andrea; Liang Chunguang; Kunz, Meik; Rauh, Manfred; Bogdan, Christian; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

Assignment of weight-based antibody units for four additional serotypes to a human anti-pneumococcal standard reference serum 007sp - Goldblatt, David; Mckeen, A.; Burbidge, P.; Mcelhiney, S.; Mclaughlin, L.; Johnson, A.; Rauh, Manfred; Giardina, P. C. (Clinical and Vaccine Immunology, 2017)
The pneumococcal ELISA reference standard serum, Lot 89SF, has been in use since 1990 and was replaced with a new reference standard serum, 007sp in 2013. This serum was generated under an FDA-approved clinical protocol, where 278 adult volunteers were immunized with the 23-valent unconjugated polysaccharide vaccine, Pneumovax II®, and a unit of blood was obtained twice within 120 days following immunization. Pooled serum was prepared from the plasma, filled at 6ml per vial and lyophilised. Five independent laboratories participated in bridging the serotype specific IgG assignments for 89SF to 007sp to establish equivalent reference values for 13 pneumococcal capsular serotypes (1,3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F, 23F) using the WHO reference ELISA. A subsequent follow up study established equivalent reference values for an additional seven serotypes (8, 10A, 11A, 12F, 15B, 22F, 33F). In this study three laboratories assigned weight-based IgG concentrations in mcg/mL of serum to 007sp for four additional serotypes; 2, 9N, 17F and 20A. This study completes the assignment of serotypes in 89SF to 007sp. In addition, the IgG antibody assignments for a 12 member WHO QC serum panel were extended to cover the four additional serotypes. Agreement was excellent with a concordance correlation coefficient (rc) > 0.996 when each laboratory was compared to the assigned values for the 12 WHO QC sera. The 007sp preparation has replaced 89SF as the pneumococcal reference standard. Sufficient quantities of 007sp are projected to be available for the next 25 years.
EVALuna2:34239

Assignment of Weight-Based Antibody Units for Seven Additional Serotypes to a Human Pneumococcal Standard Reference Serum, 007sp - Goldblatt, David; Tan, C. Y.; Burbidge, P.; Mcelhiney, S.; Mclaughlin, L.; Tucker, R.; Rauh, Manfred; Sidhu, M.; Giardina, P. C. (Clinical and Vaccine Immunology, 2015)
The pneumococcal enzyme-linked immunosorbent assay (ELISA) reference standard serum, lot 89SF, has been in use since 1990 and was replaced in 2013 with a new reference standard, 007sp, that is projected to be available for the next 25 years. 007sp was generated under an FDA-approved clinical protocol; 278 adult volunteers were immunized with the 23-valent unconjugated polysaccharide vaccine Pneumovax II, and a unit of blood was obtained twice from each immunized subject within 120 days following immunization. Pooled serum was prepared from the plasma of 262 subjects, filled at 6 ml per vial, and lyophilized. Five independent laboratories participated in bridging the serotype-specific IgG assignments for 89SF to the new reference standard, 007sp, to establish equivalent reference values for 13 pneumococcal capsular serotypes (1,3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F, and 23F) by using the WHO reference ELISA. In a second study involving three laboratories, a similar protocol was used to assign weight-based IgG concentrations in micrograms per ml to 007sp of seven serotypes (8, 10A, 11A, 12F, 15B, 22F, and 33F) also present in the 23-valent pneumococcal unconjugated polysaccharide vaccine. In addition, the IgG assignments for a 12-member WHO quality control (QC) serum panel were also extended to cover these seven serotypes. Agreement was excellent, with a concordance correlation coefficient (rc) of >0.996 when each laboratory was compared to the assigned values for the 12 WHO QC serum samples. There are four remaining pneumococcal serotypes (2, 9N, 17F, and 20) found in Pneumovax II for which IgG assignments exist for 89SF and remain to be bridged.
EVALuna2:18928

A surrogate cell-based SARS-CoV-2 spike blocking assay - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Stefan; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al. (European Journal of Immunology, 2021)
To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and successful vaccination against coronavirus disease 2019 (COVID-19), the kinetics of neutralizing or blocking anti-SARS-CoV-2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive surrogate SARS-CoV-2 blocking assay (SUBA) using immobilized recombinant human angiotensin-converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS-CoV-2 spike protein. Spike protein-expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell-associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2- or 3-approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell-bound SARS-CoV-2 spike protein and can be rapidly adjusted to quickly pre-screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS-CoV-2 variants.
CRIS-Team Scopus Importer:2021-10-08
Keywords: COVID-19; hACE2; SARS-CoV-2; Spike protein; Surrogate blocking assay

A Temperature-Based Bioimpedance Correction for Water Loss Estimation During Sports - Ring, Matthias; Lohmüller, Clemens; Rauh, Manfred; Mester, Joachim; Eskofier, Björn (IEEE Journal of Biomedical and Health Informatics, 2016)
The amount of total body water (TBW) can be estimated based on bioimpedance measurements of the human body. In sports, TBW estimations are of importance because mild water losses can impair muscular strength and aerobic endurance. Severe water losses can even be life threatening. TBW estimations based on bioimpedance, however, fail during sports because the increased body temperature corrupts bioimpedance measurements. Therefore, this paper proposes a machine learning method that eliminates the effects of increased temperature on bioimpedance and, consequently, reveals the changes in bioimpedance that are due to TBW loss. This is facilitated by utilizing changes in skin and core temperature. The method was evaluated in a study in which bioimpedance, temperature, and TBW loss were recorded every 15 minutes during a two-hour running workout. The evaluation demonstrated that the proposed method is able to reduce the error of TBW loss estimation by up to 71%, compared to the state of art. In the future, the proposed method in combination with portable bioimpedance devices might facilitate the development of wearable devices for continuous and noninvasive TBW loss monitoring during sports.
EVALuna2:15227

ATF4 promotes angiogenesis and neuronal cell death and confers ferroptosis in a xCT-dependent manner - Chen, Daishi; Fan, Zheng; Rauh, Manfred; Buchfelder, Michael; Eyupoglu, I. Y.; Savaskan, Nicolai (Oncogene, 2017)
Activating transcription factor 4 (ATF4) is a critical mediator of metabolic and oxidative homeostasis and cell survival. ATF4 is elevated in response to diverse microenvironmental stresses, including starvation, ER stress damages and exposure to toxic factors. Here we show that ATF4 expression fosters the malignancy of primary brain tumors (WHO grade III and IV gliomas) and increases proliferation and tumor angiogenesis. Hence, ATF4 expression promotes cell migration and anchorage-independent cell growth, whereas siRNA-mediated knockdown of ATF4 attenuates these features of malignancy in human gliomas. Further experiments revealed that ATF4-dependent tumor promoting effects are mediated by transcriptional targeting the glutamate antiporter xCT/SCL7A11 (also known as system Xc-). Thus, xCT is elevated as a consequence of ATF4 activation. We further found evidence that ATF4-induced proliferation can be attenuated by pharmacological or genetic xCT inhibition and ferroptosis inducers such as sorafenib, erastin and GPx4 inhibitor RSL3. Further, fostered xCT expression promotes cell survival and growth in ATF4 knockdown cells. Moreover, increased xCT levels ameliorate sorafenib and erastin-induced ferroptosis. Conversely, ATF4 knockdown renders cells susceptible for erastin, sorafenib and RSL3-induced ferroptosis. We further identified that ATF4 promotes tumor-mediated neuronal cell death which can be alleviated by xCT inhibition. Moreover, elevated ATF4 expression in gliomas promotes tumor angiogenesis. Noteworthy, ATF4-induced angiogenesis could be diminished by ferroptosis inducers erastin and by GPx4 inhibitor RSL3. Our data provide proof-of-principle evidence that ATF4 fosters proliferation and induces a toxic microenvironmental niche. Furthermore, ATF4 increases tumor angiogenesis and shapes the vascular architecture in a xCT-dependent manner. Thus, inhibition of ATF4 is a valid target for diminishing tumor growth and vasculature via sensitizing tumor cells for ferroptosis.
EVALuna2:34242

A Two-Stage Regression Using Bioimpedance and Temperature for Hydration Assessment During Sports - Ring, Matthias; Lohmüller, Clemens; Rauh, Manfred; Eskofier, Björn (Proceedings of the 2014 22nd International Conference on Pattern Recognition (ICPR), 2014)
Bioimpedance analysis (BIA) estimates the amount of total body water (TBW) in the human body. During sports, however, the increased skin temperature distorts bioimpedance measurements and, thus, prevents the application of BIA. In this paper, we propose a two-stage regression that includes temperature information in order to correct the temperature-distorted bioimpedance. In detail, the first regression stage corrects temperature-distored bioimpedance using information of skin and core temperature. The second regression stage estimates TBW loss on basis of the corrected bioimpedance. The two-stage regression was evaluated using data of an ongoing study. The results showed that estimations of TBW loss during sports can be considerably improved if temperature information is included. However, a remaining error was still observed. Therefore, additional measurements, e.g., skin blood flow, are discussed because they also influence bioimpedance and could further reduce the error.

Blood counts in adult and elderly individuals: defining the norms over eight decades of life - Zierk, Jakob; Krebs, Alexander; Rauh, Manfred; Metzler, Markus; Löscher, Astrid; Strasser, Erwin; Krause, Stefan (British Journal of Haematology, 2020)
The blood count is one of the most common tests used for health assessment. In elderly individuals, selection of a ‘healthy’ reference population for laboratory assessment is difficult due to the high prevalence of chronic morbidities, leading to uncertainty regarding appropriate reference intervals. In particular, age-specific lower haemoglobin reference limits to define anaemia are controversial. Here, we applied a data mining approach to a large dataset of 3 029 904 clinical routine samples to establish blood count reference intervals. We excluded samples from units/specialists with a high proportion of abnormal blood counts, samples from patients with an unknown or decreased estimated glomerular filtration rate, and samples with abnormal test results in selected other analytes. After sample exclusion, 566 775–572 060 samples from different individuals aged 20–100 years were available for analysis. We then used an established statistical algorithm to determine the distribution of physiological test results and calculated age- and sex-specific reference intervals. Our results show substantial trends with age in haematology analytes' reference intervals. Most notably, haemoglobin and red cell counts decline in men with advanced age, accompanied by increases in red cell volume in both sexes. These findings were confirmed in an independent dataset, and suggest an at least partly physiologic cause.
CRIS-Team Scopus Importer:2020-02-14
Keywords: anaemia; haematology; laboratory haematology

Blood counts in adults and elderly individuals - Zierk, Jakob; Krebs, A.; Rauh, Manfred; Metzler, Markus; Parsch, H.; Strasser, Erwin; Krause, Stefan (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Candidate reference measurement procedure based on isotope dilution-two dimensional-liquid chromatography-tandem mass spectrometry for the quantification of androstenedione in human serum and plasma - Ott, Myriam; Bauland, Friederike; Fischer, Vanessa; Köppl, Daniel; Gaudl, Alexander; Geistanger, Andrea; Ceglarek, Uta; Rauh, Manfred; Taibon, Judith (Clinical Chemistry and Laboratory Medicine, 2025)
Objectives: Androstenedione (ASD) is a biomarker used in the diagnosis of hyperandrogenism and adrenal hyperplasia. Therefore, accurate measurement of serumASD is pivotal in clinical settings. We aimed to develop a novel highly selective reference measurement procedure (RMP) based on isotope dilution-two dimensional-liquid chromatographytandem mass spectrometry (ID-2D-LC-MS/MS) for the quantification of ASD in human serum/plasma. Methods: To achieve high selectivity and sensitivity, a twodimensional heart-cut LC approach for LC-MS/MS and a supported liquid extraction sample preparation protocol were employed. Matrix effects were evaluated through a post-column infusion experiment and comparison of standard line slopes. Precision and accuracy were determined via a multi-day validation experiment. Reproducibility was assessed by comparing results from two independent laboratories, and measurement uncertainty (MU) was evaluated in compliance with current guidelines. Results: Our novel RMP proved effective for measuring ASD concentrations ranging from 0.00800 ng/mL to 12.0 ng/mL (0.0279 nmol/L to 41.9 nmol/L) and demonstrated matrixindependence. The relative mean bias varied between 0.6 and 2.2 %across different matrices and concentration levels. Intermediate precision was observed to be between 1.2 and 1.9 %. The expanded measurement uncertainty for ASD target value assignment ranged from 1.7 to 2.5 %, irrespective of sample concentration. Equivalence to the JCTLMlisted RMP was evaluated through a method comparison study, revealing a high degree of agreement (r≥0.997). Additionally, by comparing results from two independent laboratories, the transferability and reproducibility of the RMP were confirmed. Conclusions: This isotope dilution two-dimensional LC-MS/ MS method can be used for the evaluation and standardization of routine assays and for measuring individual patient samples, ensuring traceability.
CRIS-Team Scopus Importer:2025-06-06
Keywords: androstenedione; isotope dilution-liquid chromatography-tandem mass spectrometry; qNMR characterization; reference measurement procedure; SI units; traceability

Cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways by CD101 - Wrage, Marius; Holland, Tim; Nüse, Björn; Kaltwasser, Johanna; Fröhlich, Jessica; Arnold, Harald; Gießler, Claudia; Flamann, Cindy; Bruns, Heiko; Berges, Johannes; Daniel, Christoph; Hoffmann, Markus; et al. (Mucosal Immunology, 2024)
T lymphocytes and myeloid cells express the immunoglobulin-like glycoprotein cluster of differentiation (CD)101, notably in the gut. Here, we investigated the cell-specific functions of CD101 during dextran sulfate sodium (DSS)-induced colitis and Salmonella enterica Typhimurium infection. Similar to conventional CD101−/− mice, animals with a regulatory T cell-specific Cd101 deletion developed more severe intestinal pathology than littermate controls in both models. While the accumulation of T helper 1 cytokines in a CD101-deficient environment entertained DSS-induced colitis, it impeded the replication of Salmonella as revealed by studying CD101−/− x interferon-g−/− mice. Moreover, CD101-expressing neutrophils were capable to restrain Salmonella infection in vitro and in vivo. Both cell-intrinsic and -extrinsic mechanisms of CD101 contributed to the control of bacterial growth and spreading. The CD101-dependent containment of Salmonella infection required the expression of Irg-1 and Nox2 and the production of itaconate and reactive oxygen species. The level of intestinal microbial antigens in the sera of inflammatory bowel disease patients correlated inversely with the expression of CD101 on myeloid cells, which is in line with the suppression of CD101 seen in mice following DSS application or Salmonella infection. Thus, depending on the experimental or clinical setting, CD101 helps to limit inflammatory insults or bacterial infections due to cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways.
CRIS-Team Scopus Importer:2024-07-19

Change of the metabolomic profile during short-term mononuclear cell storage - Steininger, Philipp; Strasser, Erwin; Ziehe, Bettina; Eckstein, Reinhold; Rauh, Manfred (Vox Sanguinis, 2017)
BACKGROUND AND OBJECTIVES: Short-term storage of leukapheresis products used for immunotherapeutic mononuclear cell (MNC) products is a frequent event. The analysis of time-related metabolic patterns enables the characterization of storage-related effects in MNCs and the hypothesis-based optimization of the MNC medium. MATERIALS AND METHODS: The MNC products from seven leukapheresis procedures were stored within a closed bag system for 48 h. Concentrations of amino acids, biogenic amines, phospho- and sphingolipids and hexoses in the medium were measured by targeted metabolomics. The viability of MNC subpopulations was assayed by Annexin V (AnV) and JC-1 staining. RESULTS: Glucose depletion and a significant change of the acylcarnitine profile are early events within the first 24 h of storage. In contrast, for most amino acids, the maximum increase was observed at 48 h of storage as mirrored by an increase in the amino acid levels by a mean factor of 1·2 (1·3, 2·0) after 6 h (24 h, 48 h, respectively). This was except for the concentrations of glutamine and lysine, which did not change significantly. The taurine concentration showed a twofold increase within the first 24 h and remained constant thereafter. The steepest increase in AnV+and 7-AAD+CD4+T cells was found between 24 and 48 h. CONCLUSION: The time-course of apoptosis and metabolic patterns in the MNC products demonstrate that 24 h of storage is a decisive time-point, as afterwards key metabolic pathways showed nonlinear detrimental changes. Optimization of storage by supplementation of specific substrates demands therefore an early intervention.
EVALuna2:32783

Chemotherapeutic xCT inhibitors sorafenib and erastin unraveled with the synaptic optogenetic function analysis tool - Dahlmanns, Marc; Yakubov, Eduard; Chen, Daishi; Sehm, Tina; Rauh, Manfred; Savaskan, Nicolai; Wrosch, Jana Katharina (Cell Death Discovery, 2017)
In the search for new potential chemotherapeutics, the compounds' toxicity to healthy cells is an important factor. The brain with its functional units, the neurons, is especially endangered during the radio- and chemotherapeutic treatment of brain tumors. The effect of the potential compounds not only on neuronal survival but also neuronal function needs to be taken into account. Therefore, in this study we aimed to comprehend the biological effects of chemotherapeutic xCT inhibition on healthy neuronal cells with our synaptic optogenetic function analysis tool (SOFA). We combined common approaches, such as investigation of morphological markers, neuronal function and cell metabolism. The glutamate-cystine exchanger xCT (SLC7A11, system Xc-) is the main glutamate exporter in malignant brain tumors and as such a relevant drug target for treating deadly glioblastomas (WHO grades III and IV). Recently, two small molecules termed sorafenib (Nexavar) and erastin have been found to efficiently block xCT function. We investigated neuronal morphology, metabolic secretome profiles, synaptic function and cell metabolism of primary hippocampal cultures (containing neurons and glial cells) treated with sorafenib and erastin in clinically relevant concentrations. We found that sorafenib severely damaged neurons already after 24 h of treatment. Noteworthy, also at a lower concentration, where no morphological damage or metabolic disturbance was monitored, sorafenib still interfered with synaptic and metabolic homeostasis. In contrast, erastin-treated neurons displayed mostly inconspicuous morphology and metabolic rates. Key parameters of proper neuronal function, such as synaptic vesicle pool sizes, were however disrupted following erastin application. In conclusion, our data revealed that while sorafenib and erastin effectively inhibited xCT function they also interfered with essential neuronal (synaptic) function. These findings highlight the particular importance of investigating the effects of potential neurooncological and general cancer chemotherapeutics also on healthy neuronal cells and their function as revealed by the SOFA tool.
EVALuna2:33743

Chronic antipsychotic treatment targets GIRK current suppression, loss of long-term synaptic depression and behavioural sensitization in a mouse model of amphetamine psychosis - Groos, Dominik; Zheng, Fang; Rauh, Manfred; Quinger, Benedikt; Kornhuber, Johannes; Müller, Christian P.; Alzheimer, Christian (Journal of Psychopharmacology, 2018)
BACKGROUND:: Antipsychotic drugs (APDs) are the mainstay of the pharmacological treatment of psychotic disorders like schizophrenia. While the clinical efficacy of APDs has long since been established, the neurobiological mechanisms underlying their therapeutic benefits are still not well understood. METHODS:: Here, we used an escalating amphetamine regimen to induce a psychosis-like state in mice. To achieve clinically relevant drug concentrations in amphetamine-pretreated mice, the typical APD haloperidol or the atypical APD olanzapine were chronically administered via subcutaneously implanted osmotic mini-pumps. RESULTS:: Demonstrating their therapeutic efficacy, both drugs dampened amphetamine-induced hyperlocomotion and restored normal behaviour in the light-induced activity test. Whole-cell recordings from dopaminergic neurons of the ventral tegmental area (VTA) in ex vivo brain slices revealed two pronounced aberrations associated with the psychosis-like state: Strongly enhanced spontaneous firing and a substantial loss of G protein-gated inwardly rectifying potassium (GIRK) current upon activation of GABAB receptors with baclofen. Chronic haloperidol and olanzapine restored normal firing and partially rescued the GIRK current response to baclofen. In ex vivo slices containing the nucleus accumbens, which receives a dopaminergic projection from the VTA, abrogation of long-term synaptic depression (LTD) and enhanced excitatory drive onto medium spiny neurons were identified as synaptic consequences of amphetamine-induced psychosis. Again, both alterations proved amenable to chronic APD treatment. CONCLUSION:: Our data provide evidence for aberrant neuronal function and plasticity in the mesolimbic dopamine system during an induced psychotic state and identify these alterations as targets of chronic APD treatment.
EVALuna2:35829

Closing the gap - Detection of clinically relevant von Willebrand disease in emergency settings through an improved algorithm based on rotational Thromboelastometry 11 Medical and Health Sciences 1103 Clinical Sciences 11 Medical and Health Sciences 1102 Cardiorespiratory Medicine and Haematology - Topf, H. -G.; Strasser, Erwin; Breuer, Georg; Rascher, Wolfgang; Rauh, Manfred; Fahlbusch, F. B. (BMC Anesthesiology, 2019)
Background: Hemorrhage and blood loss are still among the main causes of preventable death. Global hemostatic assays are useful point-of-care test (POCT) devices to rapidly detect cumulative effects of plasma factors and platelets on coagulation. Thromboelastography (TEG) and Thromboelastometry (ROTEM) are established methods in many anesthesiological departments for guided hemostatic treatment. However, von Willebrand disease remains undetected by standard ROTEM, especially during emergency care, despite being the most prevalent congenital hemostatic disorder. Methods: In our monocentric cohort pilot study we focused on hemostatic challenges associated with von Willebrand disease. Twenty-seven patients with suspected von Willebrand disease were included. We modified the routine ROTEM assay by adding a preincubation with ristocetin and commercially available plasma-derived von Willebrand factor to identify clinically relevant von Willebrand disease (VWD). Results: Addition of von Willebrand factor to the ristocetin assay of a VWD type 3 patient restored the reaction of the whole blood probe to match the response of a healthy person. Our modified ROTEM assay with ristocetin (Ricotem) showed that all high responders (n = 7) had VWD. In the low responder group (n = 16) - 10 of 16 had VWD and in the normal responder group (n = 5), 2 of 5 had mild type 1 VWD. Conclusions: This new modification of the standard ROTEM assay enables the detection of otherwise unnoticed critical von Willebrand disease based on alterations in clot formation and might serve as a novel approach to reliably assess severe VWD patients by platelet-mediated blood clotting in an emergency setting. We recommend incorporating this new VWD-focused screening tool into the current ROTEM-based management algorithm of acute microvascular bleeding.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Bleeding; Emergency; ROTEM; Thromboelastometry; Von Willebrand disease; VWD

Comparison of automated differential blood cell counts from abbott sapphire, siemens advia 120, beckman coulter DxH 800, and sysmex XE-2100 in normal and pathologic samples - Meintker, Lisa; Ringwald, Juergen; Rauh, Manfred; Krause, Stefan (American Journal of Clinical Pathology, 2013)
Reliable automated blood cell characterization and quantification remain challenging in pathologic samples, whereas slide reviews due to unnecessary flagging should be avoided. We compared 4 modern hematology analyzers-Abbott Sapphire, Siemens Advia 120, Sysmex XE-2100, and Beckman Coulter DxH 800-regarding complete blood cell count (CBC), leukocyte differential count, and flagging efficacy in a total of 202 samples from hematology patients and normal controls. Manual differential count was used as reference. The analyzers exhibited very good correlation for CBC parameters. Neutrophils and eosinophils also showed very good correlations, whereas lymphocytes and monocytes correlated fairly. The Advia 120 displayed notably lower measurements for both parameters, which is attributable to classification of some events as large unstained cells. Basophil counts were unreliable with all analyzers. Flagging for blasts and immature granulocytes showed moderate sensitivity and specificity. Operators must not rely on blast flagging alone to detect leukemic samples with any analyzer. © American Society for Clinical Pathology.
Created from Fastlane, Scopus look-up
Keywords: Automated blood cell count; Blasts; Flag; Immature granulocytes; Leukocyte differential count

Complex lipid globules in early-life nutrition improve long-term metabolic phenotype in intra-uterine growth-restricted rats - Teller, Inga C.; Hoyer-Kuhn, Heike; Broenneke, Hella; Nosthoff-Horstmann, Pia; Oosting, Annemarie; Lippach, Gregor; Wohlfarth, Maria; Rauh, Manfred; Van Der Beek, Eline M.; Doetsch, Joerg; Nuesken, Kai D. (British Journal of Nutrition, 2018)
Intra-uterine growth restriction (IUGR) is associated with adverse metabolic outcome later in life. Healthy mice challenged with a Western-style diet (WSD) accumulated less body fat when previously fed a diet containing large lipid globules (complex lipid matrix (CLM)). This study was designed to clarify whether an early-life CLM diet mitigates 'programmed' visceral adiposity and associated metabolic sequelae after IUGR. In rats, IUGR was induced either by bilateral uterine vessel ligation (LIG) or sham operation (i.e. intra-uterine stress) of the dam on gestational day 19. Offspring from non-operated (NOP) dams served as controls. Male offspring of all groups were either fed CLM or 'normal matrix' control diet (CTRL) from postnatal days (PND) 15 to 42. Thereafter, animals were challenged with a mild WSD until dissection (PND 98). Fat mass (micro computer-tomograph scan; weight of fat compartments), circulating metabolic markers and expression of 'metabolic' genes (quantitative real-time PCR) were assessed. CLM diet significantly reduced visceral fat mass in LIG at PND 40. At dissection, visceral fat mass, fasted blood glucose, TAG and leptin concentrations were significantly increased in LIG-CTRL v. NOP-CTRL, and significantly decreased in LIG-CLM v. LIG-CTRL. Gene expression levels of leptin (mesenteric fat) and insulin-like growth factor 1 (liver) were significantly reduced in LIG-CLM v. LIG-CTRL. In conclusion, early-life CLM diet mitigated the adverse metabolic phenotype after utero-placental insufficiency. The supramolecular structure of dietary lipids may be a novel aspect of nutrient quality that has to be considered in the context of primary prevention of obesity and metabolic disease in at-risk populations.
EVALuna2:35819

Conditional Alox12b Knockout: Degradation of the Corneocyte Lipid Envelope in a Mouse Model of Autosomal Recessive Congenital Ichthyoses - Krieg, P.; Dick, Angela; Latzko, Susanne; Rosenberger, Sabine; Meyer, J.; Crumrine, D.; Hielscher, Thomas; Elias, Peter M.; Rauh, Manfred; Schneider, Holm (Journal of Investigative Dermatology, 2019)
CRIS-Team Scopus Importer:2019-09-17

Continuous monitoring of SARS-CoV-2 seroprevalence in children using residual blood samples from routine clinical chemistry - Wachter, Felix; Regensburger, Adrian; Peter, Antonia Sophia; Knieling, Ferdinand; Wagner, Alexandra; Simon, David; Hörning, André; Wölfle, Joachim; Überla, Klaus; Neubert, Antje; Rauh, Manfred (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives The assessment of SARS-CoV-2 infections in children is still challenging, but essential for appropriate political decisions. The aim of this study was to investigate whether residual blood samples can be used for SARS-CoV-2 seroprevalence monitoring in pediatrics. Methods In this repeated cross-sectional cohort study, anonymous residual blood samples from pediatric patients aged 0-17 years were collected in three time-periods (Oct.-Nov. 2020, April 2021, and June-July 2021) and analyzed for SARS-CoV-2 Spike protein (anti-S) and nucleocapsid (anti-N) antibodies using commercial antibody assays. 28 reactive samples were used to compare antibody levels with a pseudotyped neutralization assay. The results were further compared to the official national COVID-19 surveillance data to calculate the number of unreported cases. Results In total, n=2,626 individual blood samples were analyzed. In this unvaccinated pediatric cohort anti-S and anti-N antibody seroprevalence increased over the three time periods (anti-S: 1.38-9.16%, and 14.59%; anti-N: 1.26%, to 6.19%, and 8.56%). Compared to the national surveillance data this leads to a 3.93-5.66-fold increase in the number of unreported cases. However, a correlation between the cumulative incidence of the individual provinces and our assigned data was found (r=0.74, p=0.0151). In addition, reactive samples with anti-S and anti-N and samples with only anti-S showed neutralization capabilities (11/14 and 8/14, respectively). Anti-S levels were not significantly different between age groups and sexes (all p>0.05). Conclusions The present study suggests that residual blood samples from routine laboratory chemistry could be included in the estimation of the total SARS-CoV-2 seroprevalence in children.
CRIS-Team WoS Importer:2022-03-11
Keywords: COVID-19; pediatrics; prevalence; SARS-CoV-2

Data mining of pediatric reference intervals - Zierk, Jakob; Metzler, Markus; Rauh, Manfred (Journal of Laboratory Medicine, 2021)
Laboratory tests are essential to assess the health status and to guide patient care in individuals of all ages. The interpretation of quantitative test results requires availability of appropriate reference intervals, and reference intervals in children have to account for the extensive physiological dynamics with age in many biomarkers. Creation of reference intervals using conventional approaches requires the sampling of healthy individuals, which is opposed by ethical and practical considerations in children, due to the need for a large number of blood samples from healthy children of all ages, including neonates and young infants. This limits the availability and quality of pediatric reference intervals, and ultimately negatively impacts pediatric clinical decision-making. Data mining approaches use laboratory test results and clinical information from hospital information systems to create reference intervals. The extensive number of available test results from laboratory information systems and advanced statistical methods enable the creation of pediatric reference intervals with an unprecedented age-related accuracy for children of all ages. Ongoing developments regarding the availability and standardization of electronic medical records and of indirect statistical methods will further improve the benefit of data mining for pediatric reference intervals.
CRIS-Team Scopus Importer:2021-10-29
Keywords: data mining; indirect methods; pediatric reference intervals

Data mining of reference intervals for coagulation screening tests in adult patients - Zierk, Jakob; Ganslandt, Thomas; Rauh, Manfred; Metzler, Markus; Strasser, Erwin (Clinica Chimica Acta, 2019)
Background: Appropriate reference intervals are essential when evaluating laboratory test results. However, establishment of reference intervals is challenging, especially for coagulation screening tests, and uncertainty exists regarding age- and sex-dependency of test results. Data mining of laboratory information systems is an emerging approach to reference interval determination, and we evaluated its applicability to coagulation tests. Methods: We analyzed measurements of activated partial thromboplastin time (aPTT), prothrombin time (PT), international normalized ratio (INR), thrombin time (TT), and fibrinogen performed during clinical care in the University Hospital Erlangen, Germany (1,778,738 samples from 116,754 adult patients, 45,577-509,859 samples per analyte). We identified the proportion of samples from healthy individuals using an established statistical approach (Reference Limit Estimator), in which the distribution of physiological test results is approximated using a parametrical function, and used for the calculation of reference intervals. Results: We established age- and sex specific reference intervals for aPTT, PT, INR, TT, and fibrinogen, and created batch- and reagent-specific aPTT-reference intervals. Additionally, we evaluated the sensitivity of the established aPTT reference intervals for the detection of factor VIII, IX, XI, XII deficiencies. Conclusion: Data mining of laboratory test results allows the creation of age- and sex-reference intervals for coagulation tests that are specific to the examined population, analytical framework, and reagent. This approach can complement conventional methods when establishing reference intervals and improve clinical decision-making based on coagulation tests. The reference intervals established in this study show only minor variation with sex and age, supporting the practice of providing a common reference interval for adult women and men.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Coagulation screening tests; Data mining; Reference intervals

Detection of expressional changes induced by intrauterine growth restriction in the developing rat mammary gland via exploratory pathways analysis - Beinder, Lea; Fährmann, Nina; Wachtveitl, Rainer; Winterfeld, Ilona; Hartner, Andrea; Menendez-Castro, Carlos; Rauh, Manfred; Ruebner, Matthias; Hübner, Hanna; Nögel, Stephanie; Dörr, Helmuth-Günther; Rascher, Wolfgang; et al. (PLoS ONE, 2014)
Intrauterine growth restriction (IUGR) is thought to lead to fetal programming that in turn contributes to developmental changes of many organs postnatally. There is evidence that IUGR is a risk factor for the development of metabolic and cardiovascular disease later in life. A higher incidence of breast cancer was also observed after IUGR. This could be due to changes in mammary gland developmental pathways. We sought to characterise IUGR-induced alterations of the complex pathways of mammary development at the level of the transcriptome in a rat model of IUGR, using pathways analysis bioinformatics.We analysed the mammary glands of Wistar rats with IUGR induced by maternal low protein (LP) diet at the beginning (d21) and the end (d28) of pubertal ductal morphogenesis. Mammary glands of the LP group were smaller in size at d28, however did not show morphologic changes. We identified multiple differentially expressed genes in the mammary gland using Agilent SurePrint arrays at d21 and d28. In silico analysis was carried out using Ingenuity Pathways Analysis. In mammary gland tissue of LP rats at d21 of life a prominent upregulation of WT1 and CDKN1A (p21) expression was observed. Differentially regulated genes were associated with the extracellular regulated kinase (ERK)-1/-2 pathway. Western Blot analysis showed reduced levels of phosphorylated ERK-1/-2 in the mammary glands of the LP group at d21. To identify possible changes in circulating steroid levels, serum LC-Tandem mass-spectrometry was performed. LP rats showed higher serum progesterone levels and an increased corticosterone/dehydrocorticosterone-ratio at d28.Our data obtained from gene array analysis support the hypothesis that IUGR influences pubertal development of the rat mammary gland. We identified prominent differential regulation of genes and pathways for factors regulating cell cycle and growth. Moreover, we detected new pathways which appear to be programmed by IUGR.
EVALuna2:17429

Development of a rapid and specific MALDI-TOF mass spectrometric assay for SARS-CoV-2 detection - Kollhoff, Lydia; Kipping, Marc; Rauh, Manfred; Ceglarek, Uta; Barka, Günes; Barka, Frederik; Sinz, Andrea (Clinical Proteomics, 2023)
<?qj left?>Abstract: We have developed a rapid and highly specific assay for detecting and monitoring SARS-CoV-2 infections by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). As MALDI-TOF mass spectrometers are available in a clinical setting, our assay has the potential to serve as alternative to the commonly used reverse transcriptase quantitative polymerase chain reaction (RT-qPCR). Sample preparation prior to MALDI-TOF-MS involves the tryptic digestion of SARS-CoV-2 proteins, followed by an enrichment of virus-specific peptides from SARS-CoV-2 nucleoprotein via magnetic antibody beads. Our MALDI-TOF-MS method allows the detection of SARS-CoV-2 nucleoprotein in sample collection medium as low as 8 amol/µl. MALDI-TOF mass spectra are obtained in just a few seconds, which makes our MS-based assay suitable for a high-throughput screening of SARS-CoV-2 in healthcare facilities in addition to PCR. Due to the specific detection of virus peptides, different SARS-CoV-2 variants are readily distinguished from each other. Specifically, we show that our MALDI-TOF-MS assay discriminates SARS-CoV-2 strain B.1.617.2 “delta variant” from all other variants in patients’ samples, making our method highly valuable to monitor the emergence of new virus variants. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-07-21
Keywords: COVID-19; MALDI; Mass spectrometry; SARS-COV-2

Dexamethasone alleviates tumor-associated brain damage and angiogenesis - Fan, Zheng; Sehm, Tina; Rauh, Manfred; Buchfelder, Michael; Eyupoglu, Ilker Y.; Savaskan, Nicolai E. (PLoS ONE, 2014)
Children and adults with the most aggressive form of brain cancer, malignant gliomas or glioblastoma, often develop cerebral edema as a life-threatening complication. This complication is routinely treated with dexamethasone (DEXA), a steroidal anti-inflammatory drug with pleiotropic action profile. Here we show that dexamethasone reduces murine and rodent glioma tumor growth in a concentration-dependent manner. Low concentrations of DEXA are already capable of inhibiting glioma cell proliferation and at higher levels induce cell death. Further, the expression of the glutamate antiporter xCT (system Xc-; SLC7a11) and VEGFA is up-regulated after DEXA treatment indicating early cellular stress responses. However, in human gliomas DEXA exerts differential cytotoxic effects, with some human glioma cells (U251, T98G) resistant to DEXA, a finding corroborated by clinical data of dexamethasone non-responders. Moreover, DEXA-resistant gliomas did not show any xCT alterations, indicating that these gene expressions are associated with DEXA-induced cellular stress. Hence, siRNA-mediated xCT knockdown in glioma cells increased the susceptibility to DEXA. Interestingly, cell viability of primary human astrocytes and primary rodent neurons is not affected by DEXA. We further tested the pharmacological effects of DEXA on brain tissue and showed that DEXA reduces tumor-induced disturbances of the microenvironment such as neuronal cell death and tumor-induced angiogenesis. In conclusion, we demonstrate that DEXA inhibits glioma cell growth in a concentration and species-dependent manner. Further, DEXA executes neuroprotective effects in brains and reduces tumor-induced angiogenesis. Thus, our investigations reveal that DEXA acts pleiotropically and impacts tumor growth, tumor vasculature and tumor-associated brain damage.
EVALuna2:18894

Differences between capillary and venous blood counts in children-A data mining approach - Becker, Mathias; Gscheidmeier, Thomas; Gross, Hans-Juergen; Cario, Holger; Wölfle, Joachim; Rauh, Manfred; Metzler, Markus; Zierk, Jakob (International Journal of Laboratory Hematology, 2022)
Background Capillary sampling of blood counts is a well-established alternative to venipuncture in paediatrics. However, the sampling method has to be considered when interpreting test results, as measurements differ. Ethical and practical considerations prevent simultaneous venous and capillary sample acquisition in comprehensive paediatric cohorts that span all ages for the purpose of a direct method comparison, resulting in uncertainty regarding the interpretation of capillary test results. Methods We applied a data mining method to calculate the differences between capillary and venous blood count analytes using laboratory data collected during patient care. We examined 486 401 blood counts performed between 2010 and 2017 in two German paediatric tertiary care centers in children from birth to 18 years analysed on SYSMEX XE-2100 and SYSMEX XE-5000 devices, and analysed the differences between capillary and venous test results in 15 218 paired samples performed within 24 h. Results We identified the mean systematic differences between capillary and venous (capillary-venous) test results for haemoglobin (+6.5 g/L), haematocrit (+2.38%), platelet count (-7.01 x 10(9)/l), red cell count (+0.18 x 10(12)/L), white cell count (-0.64 x 10(9)/L), mean corpuscular cell volume (+2.07 fl), mean corpuscular haemoglobin (+0.33 pg), mean corpuscular haemoglobin concentration (-4.4 g/L) and red cell distribution width (+0.40%). The effect of age on these mean deltas is negligible, while the levels of test results influence the difference between capillary and venous test results in most analytes. Conclusions Our results improve guidance regarding the interpretation of capillary test results for children of all ages and in both physiological and pathological ranges.
CRIS-Team WoS Importer:2022-05-13

Diminished protein-bound ω-hydroxylated ceramides in the skin of patients with ichthyosis with 12R-lipoxygenase (LOX) or eLOX-3 deficiency - Dick, A.; Tantcheva-Poor, I. .; Oji, V.; Giehl, K. A.; Fischer, J. .; Krieg, P.; Schneider, Holm; Rauh, Manfred (British Journal of Dermatology, 2017)
EVALuna2:34217

Effect of maternal smoking on stress physiology in healthy neonates - Haslinger, C.; Bamert, H.; Rauh, Manfred; Burkhardt, T.; Schaffer, L. (Journal of Perinatology, 2018)
OBJECTIVE: To assess the impact of maternal smoking during pregnancy (MSDP) on the neonatal hypothalamic-pituitary-adrenal axis. STUDY DESIGN: In a prospective observational study, salivary cortisol and cortisone levels were measured at the fourth day of life during resting conditions and in response to a pain-induced stress event in healthy neonates whose mothers smoked cigarettes during each stage of pregnancy and compared with controls. RESULTS: Neonates in the control group (n=70) exhibited a physiologic stress response with a significant increase in cortisol (1.3 to 2.1 ng ml-1; P<0.05) and cortisone (11.8 to 17.8 ng ml-1; P<0.05) from baseline levels, whereas in neonates from mothers who smoked (n=33), cortisol (0.9 to 0.8 ng ml-1; P=0.77) and cortisone (11.5 to 13.0; P=0.19) stress response was not significantly different from baseline levels. A two-way analysis of variance confirmed these findings in both groups. CONCLUSIONS: Healthy neonates whose mothers smoked during pregnancy show a blunted stress response on the fourth day of life. Thus, MSDP leads to a dysregulation of the HPA axis with continued effects in neonatal life. This might explain long-term consequences of MSDP such as overweight, diabetes mellitus and modification of blood pressure control mechanisms in adult life.
EVALuna2:34246

Effects of glucose concentration in the tumor microenvironment on Non Small Lung Cancer (NSCLC) Progression - Gähler, Alexander; Hohenberger, Katja; Tausche, Patrick; Chiriac, Mircea-Teodor; Rauh, Manfred; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia; Neurath-Finotto, Susetta (JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-03

Elevated n-3/n-6 PUFA ratio in early life diet reverses adverse intrauterine kidney programming in female rats - Voggel, Jenny; Fink, Gregor; Zelck, Magdalena; Wohlfarth, Maria; Post, Julia M.; Bindila, Laura; Rauh, Manfred; Amann, Kerstin Ute; Alcazar, Miguel A. Alejandre; Doetsch, Joerg; Nuesken, Kai-Dietrich; Nuesken, Eva (Journal of Lipid Research, 2022)
Intrauterine growth restriction (IUGR) predisposes to chronic kidney disease via activation of proinflammatory pathways, and omega-3 PUFAs (n-3 PUFAs) have anti-inflammatory properties. In female rats, we investigated 1) how an elevated di-etary n-3/n-6 PUFA ratio (1:1) during postnatal kidney development modifies kidney phospholipid (PL) and arachidonic acid (AA) metabolite content and 2) whether the diet counteracts adverse molecular pro-tein signatures expected in IUGR kidneys. IUGR was induced by bilateral uterine vessel ligation or intra-uterine stress through sham operation 3.5 days before term. Control (C) offspring were born after uncom-promised pregnancy. On postnatal (P) days P2-P39, rats were fed control (n-3/n-6 PUFA ratio 1:20) or n-3 PUFA intervention diet (N3PUFA; ratio 1:1). Plasma parameters (P33), kidney cortex lipidomics and pro-teomics, as well as histology (P39) were studied. We found that the intervention diet tripled PL-DHA content (PC 40:6; P < 0.01) and lowered both PL-AA content (PC 38:4 and lyso-phosphatidylcholine 20:4; P < 0.05) and AA metabolites (HETEs, dihydrox-yeicosatrienoic acids, and epoxyeicosatrienoic acids) to 25% in all offspring groups. After ligation, our network analysis of differentially expressed proteins identified an adverse molecular signature indicating inflammation and hypercoagulability. N3PUFA diet reversed 61 protein alterations (P < 0.05), thus miti-gating adverse IUGR signatures. In conclusion, an elevated n-3/n-6 PUFA ratio in early diet strongly reduces proinflammatory PLs and mediators while increasing DHA-containing PLs regardless of prior intrauterine conditions. Counteracting a proin-flammatory hypercoagulable protein signature in young adult IUGR individuals through early diet intervention may be a feasible strategy to prevent developmentally programmed kidney damage in later life.
CRIS-Team WoS Importer:2022-12-02

Enhancing refiner - Improving performance of reference interval estimation for skewed distributions - Ammer, Tatjana; Schutzenmeister, A.; Prokosch, Hans-Ulrich; Rauh, Manfred; Zierk, Jakob; Rank, C. M. (CLINICA CHIMICA ACTA, 2022)
CRIS-Team WoS Importer:2022-07-08

Enzymatic lipid oxidation by eosinophils propagates coagulation, hemostasis, and thrombotic disease. - Uderhardt, Stefan; Ackermann, Jochen A.; Fillep, Tobias; Hammond, Victoria J.; Willeit, Johann; Santer, Peter; Mayr, Manuel; Biburger, Markus; Miller, Meike; Zellner, Katie R.; Stark, Konstantin; Zarbock, Alexander; et al. (Journal of Experimental Medicine, 2017)
Blood coagulation is essential for physiological hemostasis but simultaneously contributes to thrombotic disease. However, molecular and cellular events controlling initiation and propagation of coagulation are still incompletely understood. In this study, we demonstrate an unexpected role of eosinophils during plasmatic coagulation, hemostasis, and thrombosis. Using a large-scale epidemiological approach, we identified eosinophil cationic protein as an independent and predictive risk factor for thrombotic events in humans. Concurrent experiments showed that eosinophils contributed to intravascular thrombosis by exhibiting a strong endogenous thrombin-generation capacity that relied on the enzymatic generation and active provision of a procoagulant phospholipid surface enriched in 12/15-lipoxygenase-derived hydroxyeicosatetraenoic acid-phosphatidylethanolamines. Our findings reveal a previously unrecognized role of eosinophils and enzymatic lipid oxidation as regulatory elements that facilitate both hemostasis and thrombosis in response to vascular injury, thus identifying promising new targets for the treatment of thrombotic disease.

Epicutaneous Application of Imiquimod to Model Psoriasis-Like Skin Disease Induces Water-Saving Aestivation Motifs and Vascular Inflammation - Wild, Johannes; Ringen, Julia; Bieler, Tabea; Knopp, Tanja; Lagrange, Jérémy; Molitor, Michael; Sies, Katharina; Kropp, Angela; Keller, Karsten; Daiber, Andreas; Münzel, Thomas; Rauh, Manfred; et al. (Journal of Investigative Dermatology, 2022)
CRIS-Team Scopus Importer:2022-10-28

Evaluation of an Interactive Visualization Tool for the Interpretation of Pediatric Laboratory Test Results - Hirschmann, Johannes; Sedlmayr, Brita; Zierk, Jakob; Rauh, Manfred; Metzler, Markus; Prokosch, Hans-Ulrich; Toddenroth, Dennis (Studies in health technology and informatics, 2017)
The physiological age-related development of pediatric laboratory results interferes with pathological derangements, which can complicate the interpretation of test results. Recently proposed continuous reference intervals (RIs) promise to be beneficial, although their clinical use may depend on graphical presentations. To estimate the clinical utility of continuous RIs, we developed and evaluated an interactive visualization tool, and examined the differentiation of hemoglobinopathies that is attainable based on the underlying innovative RI model. The implemented web application allows users to easily enter laboratory test results, and displays various visualizations in conjunction with the corresponding RIs, such as charts and personalized Z-scores. To evaluate the usability of the visualization tool, we conducted concurrent think-aloud sessions with four physicians, who were prompted to solve a set of typical interpretation tasks, and acquired additional information through a questionnaire including the System Usability Scale (SUS). We used 85 de-identified clinical cases for an exemplified assessment of how well model-based interpretations of blood count parameters reproduced previously diagnosed hemoglobinopathies. Usability tests as well as questionnaire responses indicated that the developed tool was well received by the physicians. Results from the think-aloud evaluation revealed only minor problems and the tool reached an average SUS score of 86.9, suggesting good usability. Hemoglobinopathy discrimination depended on the considered subtype, although the overall performance of the novel method rivaled the one of the conventional approach. The interactive visualization of innovative continuous reference intervals demonstrated promising results, which justifies further testing on the path towards clinical routine.
EVALuna2:193

Evaluation of five multisteroid LC-MS/MS methods used for routine clinical analysis: Comparable performance was obtained for nine analytes - Braun, Valentin; Ceglarek, Uta; Gaudl, Alexander; Gawinecka, Joanna; Müller, Daniel; Rauh, Manfred; Weber, Matthias; Seger, Christoph (Clinical Chemistry and Laboratory Medicine, 2023)
A mass spectrometry (LC-MS/MS)-based interlaboratory comparison study was performed for nine steroid analytes with five participating laboratories. The sample set contained 40 pooled samples of human serum generated from preanalyzed leftovers. To obtain a well-balanced distribution across reference intervals of each steroid, the leftovers first underwent a targeted mixing step. All participants measured a sample set once using their own multianalyte protocols and calibrators. Four participants used in-house developed measurement platforms, including IVD-CE certified calibrators, which were used by three participants; the 5th lab used the whole LC-MS kit from an IVD manufacturer. All labs reported results for 17-hydroxyprogesterone, androstenedione, cortisol, and testosterone, and four labs reported results for 11-deoxycortisol, corticosterone, cortisone, dehydroepiandrosterone sulfate (DHEAS), and progesterone. Good or acceptable overall comparability was found in Bland-Altmann and Passing-Bablok analyses. Mean bias against the overall mean remained less than ±10 » % except for DHEAS, androstenedione, and progesterone at one site and for cortisol and corticosterone at two sites (max. -18.9 » % for androstenedione). The main analytical problems unraveled by this study included a bias not previously identified in proficiency testing, operator errors, non-supported matrix types and higher inaccuracy and imprecision at lower ends of measuring intervals. This study shows that intermethod comparison is essential for monitoring the validity of an assay and should serve as an example of how external quality assessment could work in addition to organized proficiency testing schemes.
CRIS-Team Scopus Importer:2023-12-15
Keywords: endocrinology; laboratory medicine; LC-MS/MS; method comparison; steroid measurement

Fiber rich food suppressed airway inflammation, GATA3 + Th2 cells, and FcεRIα+ eosinophils in asthma. - Schenzel, Alicia; Geiger, Adriana; Nendel, Elvedina; Yang, Zuqin; Krammer, Susanne; Leberle, Anna; Brunst, Ann Kathrin; Trump, Sonja; Mittler, Susanne; Rauh, Manfred; Geppert, Carol-Immanuel; Tausche, Patrick; et al. (Frontiers in Nutrition, 2024)
BACKGROUND: Allergic Asthma is a disease presenting various endotypes and no current therapies act curative but alleviate disease symptoms. Dietary interventions are gaining increasing importance in regulating immune responses. Furthermore, short chain fatty acids (SFCA), as the main products of dietary fiber's fermentation by the gut bacteria, ameliorate the pathogenesis and disease burden of different illnesses including asthma. Nevertheless, the connection and crosstalk between the gut and lung is poorly understood. OBJECTIVE: In this work, the role of high fiber diet on the development of allergic asthma at baseline and after exacerbation of disease induced by respiratory viruses was investigated. METHODS: Hereby, SCFA in serum of asthmatic and non-asthmatic pre-school children before and after airway disease symptoms were analyzed. Moreover, the effect of high fiber diet in vivo in a murine model of house dust mite extract (HDM) induced allergic asthma and in the end in isolated lung and spleen cells infected ex vivo with Rhinovirus was analyzed. RESULTS: In this study, a decrease of the SCFA 3-Hydroxybutyric acid in serum of asthmatic children after symptomatic episodes at convalescent visit as compared to asthmatic and control children at baseline visit was observed. In experimental asthma, in mice fed with high fiber diet, a reduced lung GATA3 + Th2 type mediated inflammation, mucus production and collagen deposition and expression of Fc epsilon receptor Ia (FcεRIa) in eosinophils was observed. By contrast, the CD8+ memory effector T cells were induced in the lungs of asthmatic mice fed with high fiber diet. Then, total lung cells from these asthmatic mice fed with either standard food or with fiber rich food were infected with RV ex vivo. Here, RV1b mRNA was found significantly reduced in the lung cells derived from fiber rich food fed mice as compared to those derived from standard food fed asthmatic mice. Looking for the mechanism, an increase in CD8+ T cells in RV infected spleen cells derived from fiber rich fed asthmatic mice, was observed. CONCLUSION: Convalescent preschool asthmatic children after a symptomatic episode have less serum ß-Hydroxybutyric acid as compared to control and asthmatic children at baseline visit. Fiber rich diet associated with anti-inflammatory effects as well as anti-allergic effects by decreasing Type 2 and IgE mediated immune responses and inducing CD8+ memory effector T cells in a murine model of allergic asthma. Finally, ex vivo infection with Rhinovirus (RV) of total lung cells from asthmatic mice fed with fiber rich food led to a decreased RV load as compared to mice fed with standard food. Moreover, spleen cells derived from asthmatic mice fed with fiber rich food induced CD8+ T cells after ex vivo infection with RV. CLINICAL IMPLICATIONS: Dietary interventions with increased content in natural fibers like pectins would ameliorate asthma exacerbations. Moreover, respiratory infection in asthma downregulated SCFA in the gut contributing to asthma exacerbations.
EVALuna2:568298

Frequency and impact of enteric hyperoxaluria in pediatric short bowel syndrome: a retrospective single centre study - Schaefer, Jan Thomas; Schulz-Heise, Susanne; Rueckel, Aline; Rauh, Manfred; Jüngert, Jörg; Galiano, Matthias; Meier, Norbert; Wölfle, Joachim; Schiffer, Mario; Hörning, André (Frontiers in Pediatrics, 2023)
Objectives: The survival of pediatric patients with short bowel syndrome has improved in recent years. Enteric hyperoxaluria as a pathophysiological consequence has been hardly addressed so far. It can be associated with nephrolithiasis, nephrocalcinosis or even renal insufficiency. We assessed the prevalence of hyperoxaluria and its pathogenic consequences in a retrospective single centre study over the last 12 years. Methods: We conducted an internal database search for all pediatric patients suffering from short bowel syndrome treated from 2010 to 2022 in the department of pediatric gastroenterology as well as the pediatric nephrology and dialysis unit. Out of 56 patients identified, 26 patients were analysed for etiology of short bowel syndrome, renal excretion of oxalate (24/26), remaining short bowel and large intestinal length as well as further clinical parameters such as eGFR, nephrocalcinosis/urinary stone formation or stool frequency. Results: Hyperoxaluria was detected in 14/26 patients (54%). Nephrocalcinosis was present in four patients. Out of these four patients, hyperoxaluria could be proven (21% of all hyperoxaluric patients) in three cases, one hyperoxaluric patient had nephrolithiasis (7%). In one patient hyperoxaluria lead to end stage renal disease. We found that 80% of patients with volvulus developed enteric hyperoxaluria. None of the investigated factors had an effect on oxalate excretion. Conclusion: Enteric hyperoxaluria is a relevant pathophysiological finding in patients with short bowel syndrome occurring in about 50% of our cohort with multiple pathogenic complications. Regular screening for hyperoxaluria may be implemented in medical care for patients with short bowel syndrome. If necessary, prophylaxis, e.g., dietary advice or metaphylaxis should be initiated.
CRIS-Team Scopus Importer:2023-08-11
Keywords: enteric hyperoxaluria; hyperoxaluria; intestinal failure; kidney stone; nephrolithiasis; pediatric; short bowel syndrome

Glucose-Restricted Diet Regulates the Tumor Immune Microenvironment and Prevents Tumor Growth in Lung Adenocarcinoma - Gähler, Alexander; Trufa, Denis; Chiriac, Mircea-Teodor; Tausche, Patrick; Hohenberger, Katja; Brunst, Ann-Kathrin; Rauh, Manfred; Geppert, Carol-Immanuel; Rieker, Ralf; Krammer, Susanne; Leberle, Anna; Neurath, Markus; et al. (Frontiers in Oncology, 2022)
BackgroundLung cancer is the second common cancer type in western countries and has a high mortality. During the development and progression of the tumor, the nutrients in its environment play a central role. The tumor cells depend crucially on glucose metabolism and uptake. Tumor cell metabolism is dominated by the Warburg effect, where tumor cells produce large amounts of lactate from pyruvate under aerobic conditions. We thus reasoned that, reducing carbohydrates in the diet might support anti-tumoral effects of current immunotherapy and additionally target tumor immune escape. ObjectivesThe link between reducing carbohydrates to improve current immunotherapy is not clear. We thus aimed at analyzing the effects of different glucose levels on the tumor development, progression and the anti-tumoral immune response. MethodsWe correlated the clinical parameters of our LUAD cohort with different metabolic markers. Additionally, we performed cell culture experiments with A549 tumor cell line under different glucose levels. Lastly, we investigated the effect of low and high carbohydrate diet in an experimental murine model of lung cancer on the tumor progression and different immune subsets. ResultsHere we found a positive correlation between the body mass index (BMI), blood glucose levels, reduced overall survival (OS) and the expression of Insulin-like growth factor-1 receptor (IGF1R) in the lung tumoral region of patients with lung adenocarcinoma (LUAD). Furthermore, increasing extracellular glucose induced IGF1R expression in A549 LUAD cells. Functional studies in a murine model of LUAD demonstrated that, glucose restricted diet resulted in decreased tumor load in vivo. This finding was associated with increased presence of lung infiltrating cytotoxic CD8+ T effector memory (TEM), tissue resident memory T (TRM) and natural killer cells as well as reduced IGFR mRNA expression, suggesting that glucose restriction regulates lung immunity in the tumor microenvironment. ConclusionsThese results indicate that, glucose restricted diet improves lung immune responses of the host and suppresses tumor growth in experimental lung adenocarcinoma. As glucose levels in LUAD patients were negatively correlated to postoperative survival rates, glucose-restricted diet emerges as therapeutic avenue for patients with LUAD.
CRIS-Team WoS Importer:2022-05-27

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

HIBCH deficiency in a patient with phenotypic characteristics of mitochondrial disorders - Reuter, Miriam; Sass, Joern Oliver; Leis, Thomas; Koehler, Julia; Mayr, Johannes A.; Feichtinger, Rene G.; Rauh, Manfred; Schanze, Ina; Baehr, Luzy; Trollmann, Regina; Uebe, Steffen; Ekici, Arif Bülent; et al. (American Journal of Medical Genetics Part A, 2014)
HIBCH (3-hydroxyisobutyryl-CoA hydrolase) deficiency (MIM #250620) is a rare autosomal recessive inborn error of metabolism, leading to a block in the catabolic pathway of the amino acid valine and presumably to accumulation of toxic valine metabolites in mitochondria. Only three families with HIBCH deficiency and biallelic HIBCH mutations have been described. We report on a further patient, first child of healthy consanguineous parents, with severe developmental delay, seizures, hyperintensities of the basal ganglia on magnetic resonance imaging (MRI), progressive brain atrophy, optic nerve atrophy, repeatedly elevated blood lactate, and respiratory chain complexes I, I + III and cytochrome c oxidase deficiencies with borderline depletion of mitochondrial DNA in muscle tissue. Laboratory findings in blood and skeletal muscle were inconsistent and did not allow a definite diagnosis, but supported the hypothesis of mitochondrial dysfunction. Homozygosity mapping and whole-exome sequencing revealed a homozygous one-base pair insertion in HIBCH. Deficiency of enzyme activity was confirmed in cultured fibroblasts. Although relatively unspecific, the clinical features were similar to those of the previously reported cases. Given the clinical variability and large number of differential diagnoses, the prevalence of HIBCH deficiency is probably underestimated. Next-generation sequencing approaches are an effective tool for identifying the underlying genetic basis in patients suspected of mitochondrial disorders. © 2014 Wiley Periodicals, Inc.
EVALuna2:9220

High-resolution pediatric reference intervals for 15 biochemical analytes described using fractional polynomials - Zierk, Jakob; Baum, Hannsjörg; Bertram, Alexander; Boeker, Martin; Buchwald, Armin; Cario, Holger; Christoph, Jürgen; Frühwald, Michael C.; Groß, Hans Jürgen; Groening, Arndt; Gscheidmeier, Thomas; Hoff, Torsten; et al. (Clinical Chemistry and Laboratory Medicine, 2021)
Assessment of children's laboratory test results requires consideration of the extensive changes that occur during physiological development and result in pronounced sex- and age-specific dynamics in many biochemical analytes. Pediatric reference intervals have to account for these dynamics, but ethical and practical challenges limit the availability of appropriate pediatric reference intervals that cover children from birth to adulthood. We have therefore initiated the multi-center data-driven PEDREF project (Next-Generation Pediatric Reference Intervals) to create pediatric reference intervals using data from laboratory information systems. We analyzed laboratory test results from 638,683 patients (217,883-982,548 samples per analyte, a median of 603,745 test results per analyte, and 10,298,067 test results in total) performed during patient care in 13 German centers. Test results from children with repeat measurements were discarded, and we estimated the distribution of physiological test results using a validated statistical approach (kosmic). We report continuous pediatric reference intervals and percentile charts for alanine transaminase, aspartate transaminase, lactate dehydrogenase, alkaline phosphatase, γ-glutamyl-transferase, total protein, albumin, creatinine, urea, sodium, potassium, calcium, chloride, anorganic phosphate, and magnesium. Reference intervals are provided as tables and fractional polynomial functions (i.e., mathematical equations) that can be integrated into laboratory information systems. Additionally, Z-scores and percentiles enable the normalization of test results by age and sex to facilitate their interpretation across age groups. The provided reference intervals and percentile charts enable precise assessment of laboratory test results in children from birth to adulthood. Our findings highlight the pronounced dynamics in many biochemical analytes in neonates, which require particular consideration in reference intervals to support clinical decision making most effectively.
CRIS-Team Scopus Importer:2021-03-05
Keywords: continuous reference intervals; data mining; indirect reference intervals; pediatric reference intervals; percentile charts

High salt intake reprioritizes osmolyte and energy metabolism for body fluid conservation - Kitada, Kento; Daub, Steffen; Zhang, Yahua; Klein, Janet D.; Nakano, Daisuke; Pedchenko, Tetyana; Lantier, Louise; Larocque, Lauren M.; Marton, Adriana; Neubert, Patrick; Schröder, Agnes; Rakova, Natalia; et al. (Journal of Clinical Investigation, 2017)
Natriuretic regulation of extracellular fluid volume homeostasis includes suppression of the renin-angiotensin-aldosterone system, pressure natriuresis, and reduced renal nerve activity, actions that concomitantly increase urinary Na+ excretion and lead to increased urine volume. The resulting natriuresis-driven diuretic water loss is assumed to control the extracellular volume. Here, we have demonstrated that urine concentration, and therefore regulation of water conservation, is an important control system for urine formation and extracellular volume homeostasis in mice and humans across various levels of salt intake. We observed that the renal concentration mechanism couples natriuresis with correspondent renal water reabsorption, limits natriuretic osmotic diuresis, and results in concurrent extracellular volume conservation and concentration of salt excreted into urine. This water-conserving mechanism of dietary salt excretion relies on urea transporter-driven urea recycling by the kidneys and on urea production by liver and skeletal muscle. The energy-intense nature of hepatic and extrahepatic urea osmolyte production for renal water conservation requires reprioritization of energy and substrate metabolism in liver and skeletal muscle, resulting in hepatic ketogenesis and glucocorticoid-driven muscle catabolism, which are prevented by increasing food intake. This natriuretic-ureotelic, water-conserving principle relies on metabolism-driven extracellular volume control and is regulated by concerted liver, muscle, and renal actions.
EVALuna2:34241

Histone deacetylases inhibition by SAHA/Vorinostat normalizes the glioma microenvironment via xCT equilibration - Wolf, Ines; Fan, Zheng; Rauh, Manfred; Seufert, Sebastian; Hore, Nirjhar; Buchfelder, Michael; Savaskan, Nic E.; Eyupoglu, Ilker Y. (Scientific Reports, 2014)
Malignant gliomas are characterized by neurodegenerative actions leading to the destruction of surrounding brain parenchyma. The disturbance in glutamate homeostasis caused by increased expression of the glutamate transporter xCT plays a key role in glioma progression. We demonstrate that the HDAC-inhibitor SAHA specifically inhibits the xCT-transporter expression. Thereby, tumor cell stress is engendered, marked by increase in ROS. Moreover, SAHA dependent xCT-reduction correlates with the inhibition of ATF4-expression, a factor known to foster xCT expression. Since xCT/system Xc- is pivotal for the brain tumor microenvironment, normalization of this system is a key in the management of malignant gliomas. To date, the problem lay in the inability to specifically target xCT due to the ubiquitous expression of the xCT-transporter–i.e. in non-cancerously transformed cells too–as well as its essential role in physiological CNS processes. Here, we show xCT-transporter equilibration through SAHA is specific for malignant brain tumors whereas SAHA does not affect the physiological xCT levels in healthy brain parenchyma. Our data indicate that SAHA operates on gliomas specifically via normalizing xCT expression which in consequence leads to reduced extracellular glutamate levels. This in turn causes a marked reduction in neuronal cell death and normalized tumor microenvironment.
EVALuna2:18895

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2016)
We analysed the influence of rhinovirus (RV) in nasopharyngeal fluid (NPF) on type I and III interferon (IFN) responses (e.g. IFN-? and IFN -: ?) and their signal transduction, at baseline and during disease exacerbation, in cohorts of pre-school children with and without asthma.At the time of recruitment into the Europe-wide study PreDicta, and during symptoms, NPF was collected and the local RV colonisation was analysed. Peripheral blood mononuclear cells (PBMCs) were challenged in vitro with RV or not. RNA was analysed by quantitative real-time PCR and gene arrays. Serum was analysed with ELISA for IFNs and C-reactive protein.We found that PBMCs from asthmatic children infected in vitro with the RV1b serotype upregulated MYD88, IRF1, STAT1 and STAT2 mRNA, whereas MYD88, IRF1, STAT1 and IRF9 were predominantly induced in control children. Moreover, during symptomatic visits because of disease exacerbation associated with RV detection in NPF, IFN-? production was found increased, while IFN-? secretion was already induced by RV in asthmatic children at baseline.During asthma exacerbations associated with RV, asthmatic children can induce IFN-? secretion, indicating a hyperactive immune response to repeated respiratory virus infection.
EVALuna2:9365

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna:34061

Imatinib treatment and longitudinal growth in pediatric patients with chronic myeloid leukemia: influence of demographic, pharmacological, and genetic factors in the German CML-PAED cohort - Stiehler, Sophie; Sembill, Stephanie; Schleicher, Oliver; Marx, Martin; Rauh, Manfred; Krumbholz, Manuela; Karow, Axel; Suttorp, Meinolf; Wölfle, Joachim; Maj, Carlo; Metzler, Markus (Haematologica, 2024)
In children and adolescents, impaired growth due to tyrosine kinase inhibitor therapy remains an insufficiently studied adverse effect. This study examines demographic, pharmacological, and genetic factors associated with impaired longitudinal growth in a uniform pediatric cohort treated with imatinib. We analyzed 94 pediatric patients with chronic myeloid leukemia (CML) diagnosed in the chronic phase and treated with imatinib for >12 months who participated in the Germany-wide CML-PAEDII study between February 2006 and February 2021 (clinicaltrials gov. Identifier: NCT00445822). During imatinib treatment, significant height reduction occurred, with medians of -0.35 standard deviation score (SDS) at 12 months and -0.76 SDS at 24 months. Cumulative height SDS change (Δ height SDS) showed a more pronounced effect in prepubertal patients during the first year but were similar between prepubertal and pubertal subgroups by the second year (-0.55 vs. -0.50). From months 12 to 18 on imatinib, only 18% patients achieved individually longitudinal growth adequate to the growth standard (Δ height SDS ≥0). When patients were divided into two subgroups based on median Δ height SDS (classifier Δ height SDS > or ≤-0.37) after 1 year on imatinib therapy, cohort 1 (Δ height SDS ≤-0.37) showed younger age at diagnosis, a higher proportion of prepubertal children, but also better treatment response and higher imatinib serum levels. Exploring the association of growth parameters with pharmacokinetically relevant single nucleotide polymorphisms, known for affecting imatinib response, showed no correlation. This retrospective study provides new insights into imatinib-related growth impairment. We emphasize the importance of optimizing treatment strategies for pediatric patients to realize their maximum growth potential.
CRIS-Team Scopus Importer:2024-08-16

Increased salt consumption induces body water conservation and decreases fluid intake - Rakova, Natalia; Kitada, Kento; Lerchl, Kathrin; Dahlmann, Anke; Birukov, Anna; Daub, Steffen; Kopp, Christoph; Pedchenko, Tetyana; Zhang, Yahua; Beck, Luis; Johannes, Bernd; Marton, Adriana; et al. (Journal of Clinical Investigation, 2017)
BACKGROUND: The idea that increasing salt intake increases drinking and urine volume is widely accepted. We tested the hypothesis that an increase in salt intake of 6 g/d would change fluid balance in men living under ultra-long-term controlled conditions. METHODS: Over the course of 2 separate space flight simulation studies of 105 and 205 days' duration, we exposed 10 healthy men to 3 salt intake levels (12, 9, or 6 g/d). All other nutrients were maintained constant. We studied the effect of salt-driven changes in mineralocorticoid and glucocorticoid urinary excretion on day-to-day osmolyte and water balance. RESULTS: A 6-g/d increase in salt intake increased urine osmolyte excretion, but reduced free-water clearance, indicating endogenous free water accrual by urine concentration. The resulting endogenous water surplus reduced fluid intake at the 12-g/d salt intake level. Across all 3 levels of salt intake, half-weekly and weekly rhythmical mineralocorticoid release promoted free water reabsorption via the renal concentration mechanism. Mineralocorticoid-coupled increases in free water reabsorption were counterbalanced by rhythmical glucocorticoid release, with excretion of endogenous osmolyte and water surplus by relative urine dilution. A 6-g/d increase in salt intake decreased the level of rhythmical mineralocorticoid release and elevated rhythmical glucocorticoid release. The projected effect of salt-driven hormone rhythm modulation corresponded well with the measured decrease in water intake and an increase in urine volume with surplus osmolyte excretion. CONCLUSION: Humans regulate osmolyte and water balance by rhythmical mineralocorticoid and glucocorticoid release, endogenous accrual of surplus body water, and precise surplus excretion. FUNDING: Federal Ministry for Economics and Technology/DLR; the Interdisciplinary Centre for Clinical Research; the NIH; the American Heart Association (AHA); the Renal Research Institute; and the TOYOBO Biotechnology Foundation. Food products were donated by APETITO, Coppenrath und Wiese, ENERVIT, HIPP, Katadyn, Kellogg, Molda, and Unilever.
EVALuna2:34240

Increase of liver stiffness and altered bile acid metabolism after triple CFTR modulator initiation in children and young adults with cystic fibrosis - Schnell, Alexander; Jüngert, Jörg M.; Klett, Daniel; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Schmitt-Grohe, Sabina; Zirlik, Sabine; et al. (Liver International, 2023)
Background: Novel cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies (elexacaftor/tezacaftor/ivacaftor—ETI) promise clinically significant and sustained improvements for patients with cystic fibrosis (CF). In this study, we investigated the impact of ETI therapy on liver stiffness and bile acid metabolism in a cohort of children and young adults with CF. Methods: A prospective observational study (NCT05576324) was conducted from September 2020 to November 2021 enrolling CF patients naive to ETI. Standard laboratory chemistry, sweat test, lung function, share wave velocity (SWV) derived by acoustic radiation force impulse imaging (ARFI) and serum bile acid profiles were assessed before and 6 months after induction of ETI therapy. Results: A total of 20 patients (10 aged <20 years) completed the study. While lung function and BMI improved after ETI therapy, ARFI SWV increased in CF patients <20 years of age (from 1.27 to 1.43 m/s, p = 0.023). Bile acid (BA) profiles revealed a decrease in unconjugated (5.75 vs 1.46, p = 0.007) and increase in glycine-conjugated derivatives (GCDCA) (4.79 vs 6.64 p = 0.016). There was a positive correlation between ARFI SWV values and GCDCA (r = 0.80, p < 0.0001). Glycine-conjugated BA provided high diagnostic accuracy to predict increased ARFI measurements (AUC 0.90) and clinical (Colombo) CFLD grading (AUC 0.97). Conclusions: ARFI SWV and bile acid profiles provide evidence for early increase in liver stiffness and altered bile acid metabolism in young CF patients after initiation of ETI and may serve as synergistic measures for detection of hepatic complications during ETI therapy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: ARFI; bile acids; CFLD; cystic fibrosis

Indirect determination of hematology reference intervals in adult patients on Beckman Coulter UniCell DxH 800 and Abbott CELL-DYN Sapphire devices - Zierk, Jakob; Arzideh, Farhad; Haeckel, Rainer; Rauh, Manfred; Metzler, Markus; Ganslandt, Thomas; Krause, Stefan (Clinical Chemistry and Laboratory Medicine, 2018)
Background Conventional establishment of reference intervals for hematological analytes is challenging due to the need to recruit healthy persons. Indirect methods address this by deriving reference intervals from clinical laboratory databases which contain large datasets of both physiological and pathological test results. Methods We used the "Reference Limit Estimator" (RLE) to establish reference intervals for common hematology analytes in adults aged 18-60 years. One hundred and ninety-five samples from 44,519 patients, measured on two different devices in a tertiary care center were analyzed. We examined the influence of patient cohorts with an increasing proportion of abnormal test results, compared sample selection strategies, explored inter-device differences, and analyzed the stability of reference intervals in simulated datasets with varying overlap of pathological and physiological test results. Results Reference intervals for hemoglobin, hematocrit, red cell count and platelet count remained stable, even if large numbers of pathological samples were included. Reference intervals for red cell indices, red cell distribution width and leukocyte count were sufficiently stable, if patient cohorts with the highest fraction of pathological samples were excluded. In simulated datasets, estimated reference limits shifted, if the pathological dataset contributed more than 15%-20% of total samples and approximated the physiological distribution. Advanced sample selection techniques did not improve the algorithm's performance. Inter-device differences were small except for red cell distribution width. Conclusions The RLE is well-suited to create reference intervals from clinical laboratory databases even in the challenging setting of a adult tertiary care center. The procedure can be used as a complement for reference interval determination where conventional approaches are limited.
EVALuna2:34837

Influence of factor XIII activity on post-operative transfusion in congenital cardiac surgery-A retrospective analysis - Fahlbusch, Fabian B.; Heinlein, Thomas; Rauh, Manfred; Dittrich, Sven; Cesnjevar, Robert; Moosmann, Julia; Nadal, Jennifer; Schmid, Matthias; Münch, Frank; Schroth, Michael; Rascher, Wolfgang; Topf, Hans-Georg (PLoS ONE, 2018)
OBJECTIVES: Coagulation factor XIII (FXIII) plays a key role in fibrin clot stabilization-an essential process for wound healing following cardiothoracic surgery. However, FXIII deficiency as a risk for post-operative bleeding in pediatric cardiac surgery involving cardiopulmonary bypass (CPB) for congenital heart disease (CHD) is controversially discussed. Thus, as primary outcome measures, we analyzed the association of pre-operative FXIII activity and post-operative chest tube drainage (CTD) loss with transfusion requirements post-operatively. Secondary outcomes included the influence of cyanosis and sex on transfusion. METHODS: Our retrospective analysis (2009-2010) encompassed a single center series of 76 cardio-surgical cases with CPB (0-17 years, mean age 5.61 years) that were post-operatively admitted to our pediatric intensive care unit (PICU). The observational period was 48 hours after cardiac surgery. Blood cell counts and coagulation status, including FXIII activity were routinely performed pre- and post-operatively. The administered amount of blood products and volume expanders was recorded electronically, along with the amount of CTD loss. Uni- and multivariate logistic regression analysis was performed to calculate the associations (odds ratios) of variables with post-operative transfusion needs. RESULTS: FXIII activities remained stable following CPB surgery. There was no association of pre- and post-operative FXIII activities and transfusion of blood products or volume expanders in the first 48 hours after surgery. Similarly, FXIII showed no association with CTD loss. Cyanosis and female sex were associated with transfusion rates. CONCLUSIONS: Although essentially involved in wound healing and clotting after surgery, FXIII activity does not serve as a valid predictor of post-operative transfusion need.
EVALuna2:35481

Influence of labor on direct and indirect determinants of placental 11beta-hydroxysteroid dehydrogenase activity - Hübner, Hanna; Heussner, Kirsten; Rübner, Matthias; Schmid, Matthias; Nadal, Jennifer; Wölfle, Joachim; Hartner, Andrea; Menendez-Castro, Carlos; Rauh, Manfred; Beckmann, Matthias; Kehl, Sven; Fahlbusch, Fabian (Archives of Gynecology and Obstetrics, 2020)
Purpose: Labor is a complex process involving multiple para-, auto- and endocrine cascades. The interaction of cortisol, corticotropin-releasing hormone (CRH) and progesterone is essential. The action of cortisol on the human feto-placental unit is regulated by 11beta-hydroxysteroid dehydrogenase type 2 (11β-HSD2/HSD11B2) that converts cortisol into inactive cortisone. The majority of studies on the assessment of placental 11β-HSD2 function determined indirect activity parameters. It remains elusive if indirect measurements correlate with enzymatic function and if these parameters are affected by potential confounders (e.g., mode of delivery). Thus, we compared determinants of indirect 11β-HSD2 tissue activity with its direct enzymatic turnover rate in placental samples from spontaneous births and cesarean (C)-sections. Methods: Using LC–MS/MS, we determined CRH, cortisol, cortisone, progesterone and 17-hydroxy(OH)-progesterone in human term placentas (spontaneous birth vs. C-section, n = 5 each) and measured the enzymatic glucocorticoid conversion rates in placental microsomes. Expression of HSD11B1, 2 and CRH was determined via qRT-PCR in the same samples. Results: Cortisol–cortisone ratio correlated with direct microsomal enzymatic turnover. While this observation seemed independent of sampling site, a strong influence of mode of delivery on tissue steroids was observed. The mRNA expression of HSD11B2 correlated with indirect and direct cortisol turnover rates in C-section placentas only. In contrast to C-sections, CRH, cortisol and cortisone levels were significantly increased in placental samples following spontaneous birth. Conclusion: Labor involves a series of complex hormonal processes including activation of placental CRH and glucocorticoid metabolism. This has to be taken into account when selecting human cohorts for comparative analysis of placental steroids.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 11beta-hydroxysteroid dehydrogenase; CRH; LC–MS/MS; Mode of delivery; Placenta

Influence of Low Protein Diet-Induced Fetal Growth Restriction on the Neuroplacental Corticosterone Axis in the Rat - Schmidt, Marius; Rauh, Manfred; Schmid, Matthias C.; Hübner, Hanna; Rübner, Matthias; Wachtveitl, Rainer; Cordasic, Nada; Rascher, Wolfgang; Menendez-Castro, Carlos; Hartner, Andrea; Fahlbusch, Fabian B. (Frontiers in Endocrinology, 2019)
Objectives: Placental steroid metabolism is linked to the fetal hypothalamus-pituitary-adrenal axis. Intrauterine growth restriction (IUGR) might alter this cross-talk and lead to maternal stress, in turn contributing to the pathogenesis of anxiety-related disorders of the offspring, which might be mediated by fetal overexposure to, or a reduced local enzymatic protection against maternal glucocorticoids. So far, direct evidence of altered levels of circulating/local glucocorticoids is scarce. Liquid chromatography tandem-mass spectrometry (LC-MS/MS) allows quantitative endocrine assessment of blood and tissue. Using a rat model of maternal protein restriction (low protein [LP] vs. normal protein [NP]) to induce IUGR, we analyzed fetal and maternal steroid levels via LC-MS/MS along with the local expression of 11beta-hydroxysteroid- dehydrogenase (Hsd11b).
CRIS-Team WoS Importer:2019-03-20

Influence of Turkish origin on hematology reference intervals in the German population - Mayr, Franz Xaver; Bertram, Alexander; Cario, Holger; Frühwald, Michael C.; Groß, Hans Jürgen; Groening, Arndt; Grützner, Stefanie; Gscheidmeier, Thomas; Hoffmann, Reinhard; Krebs, Alexander; Ruf, Hans Georg; Torge, Antje; et al. (Scientific Reports, 2021)
Reference intervals for laboratory test results have to be appropriate for the population in which they are used to be clinically useful. While sex and age are established partitioning criteria, patients’ origin also influences laboratory test results, but is not commonly considered when creating or applying reference intervals. In the German population, stratification for ethnicity is rarely performed, and no ethnicity-specific hematology reference intervals have been reported yet. In this retrospective study, we investigated whether specific reference intervals are warranted for the numerically largest group of non-German descent, individuals originating from Turkey. To this end, we analyzed 1,314,754 test results from 167,294 patients from six German centers. Using a name-based algorithm, 1.9% of patients were identified as originating from Turkey, in line with census data and the algorithm’s sensitivity. Reference intervals and their confidence intervals were calculated using an indirect data mining approach, and Turkish and non-Turkish reference limits overlapped completely or partially in nearly all analytes, regardless of age and sex, and only 5/144 (3.5%) subgroups’ reference limits showed no overlap. We therefore conclude that the current practice of using common reference intervals is appropriate and allows correct clinical decision-making in patients originating from Turkey.
CRIS-Team Scopus Importer:2021-11-05

Inosine Released from Dying or Dead Cells Stimulates Cell Proliferation via Adenosine Receptors - Chen, Jin; Chaurio, Ricardo A.; Maueröder, Christian; Derer, Anja; Rauh, Manfred; Kost, Andriy; Liu, Yi; Mo, Xianming; Hueber, Axel; Bilyy, Rostyslav; Herrmann, Martin; Zhao, Yi; et al. (Frontiers in Immunology, 2017)
Many antitumor therapies induce apoptotic cell death in order to cause tumor regression. Paradoxically, apoptotic cells are also known to promote wound healing, cell proliferation, and tumor cell repopulation in multicellular organisms. We aimed to characterize the nature of the regenerative signals concentrated in the micromilieu of dead and dying cells.Cultures of viable melanoma B16F10 cells, mouse fibroblasts, and primary human fibroblast-like synoviocytes (FLS) in the presence of dead and dying cells, their supernatants (SNs), or purified agonists and antagonists were used to evaluate the stimulation of proliferation. Viable cell quantification was performed by either flow cytometry of harvested cells or by crystal violet staining of adherent cells. High-performance liquid chromatography and liquid chromatography coupled with mass spectrometry of cell SNs were deployed to identify the nature of growth-promoting factors. Coimplantation of living cells in the presence of SNs collected from dead and dying cells and specific agonists was used to evaluate tumor growth in vivo.The stimulation of proliferation of few surviving cells by bystander dead cells was confirmed for melanoma cells, mouse fibroblasts, and primary FLS. We found that small soluble molecules present in the protein-free fraction of SNs of dead and dying cells were responsible for the promotion of proliferation. The nucleoside inosine released by dead and dying cells acting via adenosine receptors was identified as putative inducer of proliferation of surviving tumor cells after irradiation and heat treatment.Inosine released by dead and dying cells mediates tumor cell proliferation via purinergic receptors. Therapeutic strategies surmounting this pathway may help to reduce the rate of recurrence after radio- and chemotherapy.
EVALuna2:13419

Intrauterine Growth Restriction (IUGR) Induces Signs of Subclinical Atherosclerosis in 6-Year-Old Infants Despite Absence Of Excessive Growth - Tzschoppe, Anja; Von Kries, Ruediger; Struwe, Ellen; Rascher, Wolfgang; Dörr, Helmuth-Günther; Juengert, Joerg; Rauh, Manfred; Beckmann, Matthias; Schild, Ralf; Goecke, Tamme W.; Doetsch, Joerg (Klinische Pädiatrie, 2017)
Background Postnatal catch-up growth and rapid weight gain after intrauterine growth restriction (IUGR) seem to increase the risk for later disease. This study aimed to compare features of the metabolic syndrome early in life between IUGR and appropriate for gestational age (AGA) infants. Patients Data for 9 infants with IUGR defined by a birth weight<10th percentile and ultrasound-proven placental insufficiency and 11 AGA children were available. Method Postnatal growth, auxological, cardiovascular, and metabolic parameters up to a chronological age of 6 years were assessed: Fasting serum concentrations of LDL-cholesterol, insulin, leptin, IGF-I, DHEAS, skinfold thicknesses, blood pressure, and mean carotid intima-media thickness (cIMT). Results All IUGR infants showed catch-up growth, although mean BMI SDS and total subcutaneous fat mass at the age of 6 years were still slightly lower compared to the AGA cohort. Reduced serum leptin concentrations were observed in IUGR infants (p=0.02), whereas no significant difference was found for IGF-I, insulin, LDL-cholesterol and DHEAS concentrations. Mean cIMT was significantly higher in IUGR infants (p<0.05). Mean arterial pressure did no differ. Discussion and Conclusion In 6-year-old IUGR infants with catch-up growth, who still had a slightly reduced BMI SDS compared to the AGA group, signs of subclinical atherosclerosis were detectable suggesting that cardiovascular risk in IUGR may be present even in the absence of excessive growth.
EVALuna2:34095

L-arginine metabolism as pivotal interface of mutual host–microbe interactions in the gut - Nüse, Björn; Holland, Tim; Rauh, Manfred; Gerlach, Roman; Mattner, Jochen (Gut Microbes, 2023)
L-arginine (L-arg) is a versatile amino acid and a central intestinal metabolite in mammalian and microbial organisms. Thus, L-arg participates as precursor of multiple metabolic pathways in the regulation of cell division and growth. It also serves as a source of carbon, nitrogen, and energy or as a substrate for protein synthesis. Consequently, L-arg can simultaneously modify mammalian immune functions, intraluminal metabolism, intestinal microbiota, and microbial pathogenesis. While dietary intake, protein turnover or de novo synthesis usually supply L-arg in sufficient amounts, the expression of several key enzymes of L-arg metabolism can change rapidly and dramatically following inflammation, sepsis, or injury. Consequently, the availability of L-arg can be restricted due to increased catabolism, transforming L-arg into an essential amino acid. Here, we review the enzymatic pathways of L-arg metabolism in microbial and mammalian cells and their role in immune function, intraluminal metabolism, colonization resistance, and microbial pathogenesis in the gut.
CRIS-Team Scopus Importer:2023-07-21
Keywords: colonization resistance; dietary L-arg supplementation; host–microbe interaction; intestinal microbiota; L-arginine (L-arg); microbial pathogenesis; mucosal immune function; mutual metabolic pathways; virulence factor

Latent class distributional regression for the estimation of non-linear reference limits from contaminated data sources - Hepp, Tobias; Zierk, Jakob; Rauh, Manfred; Metzler, Markus; Mayr, Andreas (BMC Bioinformatics, 2020)
Background: Medical decision making based on quantitative test results depends on reliable reference intervals, which represent the range of physiological test results in a healthy population. Current methods for the estimation of reference limits focus either on modelling the age-dependent dynamics of different analytes directly in a prospective setting or the extraction of independent distributions from contaminated data sources, e.g. data with latent heterogeneity due to unlabeled pathologic cases. In this article, we propose a new method to estimate indirect reference limits with non-linear dependencies on covariates from contaminated datasets by combining the framework of mixture models and distributional regression. Results: Simulation results based on mixtures of Gaussian and gamma distributions suggest accurate approximation of the true quantiles that improves with increasing sample size and decreasing overlap between the mixture components. Due to the high flexibility of the framework, initialization of the algorithm requires careful considerations regarding appropriate starting weights. Estimated quantiles from the extracted distribution of healthy hemoglobin concentration in boys and girls provide clinically useful pediatric reference limits similar to solutions obtained using different approaches which require more samples and are computationally more expensive. Conclusions: Latent class distributional regression models represent the first method to estimate indirect non-linear reference limits from a single model fit, but the general scope of applications can be extended to other scenarios with latent heterogeneity.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Distributional regression; Finite mixture models; Latent class regression; Reference limits

Maternal SARS-CoV-2 infection during pregnancy: possible impact on the infant - Morhart, Patrick; Mardin, Christian; Rauh, Manfred; Juengert, Joerg; Hammersen, Johanna; Kehl, Sven; Schuh, Wolfgang; Maier-Wohlfart, Sigrun; Hermes, Katharina; Neubert, Antje; Schneider, Michael; Hein, Alexander; et al. (European Journal of Pediatrics, 2021)
The risk and potential consequences of mother-to-child transmission of severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) during pregnancy are still a matter of debate. We studied the impact of SARS-CoV-2 infection on 56 complete households, including 27 newborns whose mothers were pregnant when exposed to the virus. Two PCR-confirmed perinatal SARS-CoV-2 transmissions with mild symptoms in affected neonates were recorded. In addition, we observed a severe eye malformation (unilateral microphthalmia, optic nerve hypoplasia, and congenital retinopathy) associated with maternal SARS-CoV-2 infection in weeks 5 and 6 of embryonic development. This embryopathy could not be explained by other infectious agents, genetic factors, drug use, or maternal disease during pregnancy. Eight other women with a history of SARS-CoV-2 infection prior to gestational week 12, however, delivered healthy infants. Conclusion: The repeated occurrence of mother-to-child transmission in our cohort with risks that remain incompletely understood, such as long-term effects and the possibility of an embryopathy, should sensitize researchers and stimulate further studies as well as support COVID-19 vaccination recommendations for pregnant women. Trial registration number: NCT04741412. Date of registration: November 18, 2020What is Known:•Materno-fetal transmission of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) during pregnancy has rarely been reported so far, but was demonstrated in isolated cases.What is New:•In a study of complete households with documented SARS-CoV-2 infection, including a cohort of pregnant women, we observed perinatal coronavirus transmission at a higher frequency than expected.•We also describe a newborn boy with an eye malformation reminiscent of rubella embryopathy but associated with early gestation SARS-CoV-2 infection of his mother.•A coronavirus-related embryopathy, reported here for the first time, is a finding that requires further investigation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Case report; Coronavirus; Embryopathy; Malformation; Materno-fetal transmission

Measurement of amniotic fluid steroids of midgestation via LC-MS/MS - Fahlbusch, Fabian B.; Heussner, Kirsten; Schmid, Matthias; Schild, Ralf; Rübner, Matthias; Hübner, Hanna; Rascher, Wolfgang; Dörr, Helmuth-Günther; Rauh, Manfred (Journal of Steroid Biochemistry and Molecular Biology, 2015)
Analysis of steroids by mass spectrometry (MS) has evolved into a reliable tool for the simultaneous detection of multiple steroids. As amniotic fluid (AF) and fetal serum composition of early pregnancy are closely related, the analysis of AF can yield information on the physiological status of the developing fetus. We evaluated the use of liquid-chromatography tandem mass spectrometry (LC-MS/MS) for AF steroid analysis, including the analysis of its sensitivity and accuracy for gender verification in healthy subjects.AF of 78 male and 94 female healthy newborns was analyzed by LC-MS/MS at 16 weeks of gestation. The levels of androstenedione, corticosterone, cortisol, cortisone, deoxycorticosterone, 11-deoxycortisol, dehydroepiandrosterone (DHEA), dehydroepiandrosterone-sulfate (DHEA-S), 17-hydroxyprogesterone, progesterone (17-OHP) and testosterone were measured. Steroid levels were compared to RIA and GC-MS levels of midgestation from the literature. Cross-validated logistic regression was used to obtain statistical predictions of gender at birth from testosterone and the above steroids.LC-MS/MS analysis of AF steroids yielded comparable results with published GC-MS data. Gender specific differences were found for androstenedione and testosterone concentrations with higher levels in the male fetus. In contrast to published RIA data no gender specific differences were observed for 17-hydroxyprogesterone and dehydroepiandrosterone AF concentrations. Testosterone concentrations yielded highly accurate predictions for male gender at birth. Additional analysis of further steroids did neither increase the accuracy, sensitivity nor specificity of this prediction. The estimated optimal cut-off value for amniotic testosterone level was 0.074 ?g/L for healthy male newborns.LC-MS/MS is a reliable method for the determination of steroids in amniotic fluid. The determination of testosterone in amniotic fluid by LC-MS/MS in early pregnancy of healthy subjects can be used to offer a reliable prediction of fetal gender at birth.
EVALuna2:17444

Microbiota-Derived Propionate Modulates Megakaryopoiesis and Platelet Function - Dürholz, Kerstin; Schmid, Eva; Frech, Michael; Azizov, Vugar; Otterbein, Nadine; Lucas, Sébastien; Rauh, Manfred; Schett, Georg; Bruns, Heiko; Zaiss, Mario (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is associated with an increased risk for cardiovascular events driven by abnormal platelet clotting effects. Platelets are produced by megakaryocytes, deriving from megakaryocyte erythrocyte progenitors (MEP) in the bone marrow. Increased megakaryocyte expansion across common autoimmune diseases was shown for RA, systemic lupus erythematosus (SLE) and primary Sjögren’s syndrome (pSS). In this context, we evaluated the role of the microbial-derived short chain fatty acid (SCFA) propionate on hematopoietic progenitors in the collagen induced inflammatory arthritis model (CIA) as we recently showed attenuating effects of preventive propionate treatment on CIA severity. In vivo, propionate treatment starting 21 days post immunization (dpi) reduced the frequency of MEPs in the bone marrow of CIA and naïve mice. Megakaryocytes numbers were reduced but increased the expression of the maturation marker CD61. Consistent with this, functional analysis of platelets showed an upregulated reactivity state following propionate-treatment. This was confirmed by elevated histone 3 acetylation and propionylation as well as by RNAseq analysis in Meg-01 cells. Taken together, we identified a novel nutritional axis that skews platelet formation and function.
CRIS-Team Scopus Importer:2022-08-05
Keywords: hematopoietic progenitors; megakaryocytes; microbiota; platelets; rheumatoid arthritis; short-chain fatty acids

Microbiota-derived propionate modulates megakaryopoiesis and platelet function - Schmid, Erik; Dürholz, Kerstin; Frech, Michael; Otterbein, N.; Lucas, Sébastien; Rauh, Manfred; Schett, Georg; Bruns, Heiko; Zaiss, Mario (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

miRNA-26b Overexpression in Ulcerative Colitis-associated Carcinogenesis - Benderska, Natalya; Dittrich, Anna-Lena; Knaup, Sabine; Rau, Tilman; Neufert, Clemens; Wach, Sven; Fahlbusch, Fabian B.; Rauh, Manfred; Wirtz, Ralph M.; Agaimy, Abbas; Srinivasan, Swetha; Mahadevan, Vijayalakshmi; et al. (Inflammatory Bowel Diseases, 2015)
Longstanding ulcerative colitis (UC) bears a high risk for development of UC-associated colorectal carcinoma (UCC). The inflammatory microenvironment influences microRNA expression, which in turn deregulates target gene expression. microRNA-26b (miR-26b) was shown to be instrumental in normal tissue growth and differentiation. Thus, we aimed to investigate the impact of miR-26b in inflammation-associated colorectal carcinogenesis.Two different cohorts of patients were investigated. In the retrospective group, a tissue microarray with 38 samples from 17 UC/UCC patients was used for miR-26b in situ hybridization and quantitative reverse transcription polymerase chain reaction analyses. In the prospective group, we investigated miR-26b expression in 25 fresh-frozen colon biopsies and corresponding serum samples of 6 UC and 15 non-UC patients, respectively. In silico analysis, Ago2-RNA immunoprecipitation, luciferase reporter assay, quantitative reverse transcription polymerase chain reaction examination, and miR-26b mimic overexpression were employed for target validation.miR-26b expression was shown to be upregulated with disease progression in tissues and serum of UC and UCC patients. Using miR-26b and Ki-67 expression levels, an UCC was predicted with high accuracy. We identified 4 novel miR-26b targets (DIP1, MDM2, CREBBP, BRCA1). Among them, the downregulation of the E3 ubiquitin ligase DIP1 was closely related to death-associated protein kinase stabilization along the normal mucosa-UC-UCC sequence. In silico functional pathway analysis revealed that the common cellular pathways affected by miR-26b are highly related to cancerogenesis and the development of gastrointestinal diseases.We suggest that miR-26b could serve as a biomarker for inflammation-associated processes in the gastrointestinal system. Because miR-26b expression is downregulated in sporadic colon cancer, it could discriminate between UCC and the sporadic cancer type.
EVALuna2:1970

Mixture density networks for the indirect estimation of reference intervals - Hepp, Tobias; Zierk, Jakob; Rauh, Manfred; Metzler, Markus; Seitz, Sarem (BMC Bioinformatics, 2022)
Background: Reference intervals represent the expected range of physiological test results in a healthy population and are essential to support medical decision making. Particularly in the context of pediatric reference intervals, where recruitment regulations make prospective studies challenging to conduct, indirect estimation strategies are becoming increasingly important. Established indirect methods enable robust identification of the distribution of “healthy” samples from laboratory databases, which include unlabeled pathologic cases, but are currently severely limited when adjusting for essential patient characteristics such as age. Here, we propose the use of mixture density networks (MDN) to overcome this problem and model all parameters of the mixture distribution in a single step. Results: Estimated reference intervals from varying settings with simulated data demonstrate the ability to accurately estimate latent distributions from unlabeled data using different implementations of MDNs. Comparing the performance with alternative estimation approaches further highlights the importance of modeling the mixture component weights as a function of the input in order to avoid biased estimates for all other parameters and the resulting reference intervals. We also provide a strategy to generate partially customized starting weights to improve proper identification of the latent components. Finally, the application on real-world hemoglobin samples provides results in line with current gold standard approaches, but also suggests further investigations with respect to adequate regularization strategies in order to prevent overfitting the data. Conclusions: Mixture density networks provide a promising approach capable of extracting the distribution of healthy samples from unlabeled laboratory databases while simultaneously and explicitly estimating all parameters and component weights as non-linear functions of the covariate(s), thereby allowing the estimation of age-dependent reference intervals in a single step. Further studies on model regularization and asymmetric component distributions are warranted to consolidate our findings and expand the scope of applications.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Distributional regression; Latent class regression; Mixture density networks; Reference intervals

Model-Based Simulation of Maintenance Therapy of Childhood Acute Lymphoblastic Leukemia - Jost, Felix; Zierk, Jakob; Le, Thuy T.T.; Raupach, Thomas; Rauh, Manfred; Suttorp, Meinolf; Stanulla, Martin; Metzler, Markus; Sager, Sebastian (Frontiers in Physiology, 2020)
Acute lymphoblastic leukemia is the most common malignancy in childhood. Successful treatment requires initial high-intensity chemotherapy, followed by low-intensity oral maintenance therapy with oral 6-mercaptopurine (6MP) and methotrexate (MTX) until 2–3 years after disease onset. However, intra- and inter-individual variability in the pharmacokinetics (PK) and pharmacodynamics (PD) of 6MP and MTX make it challenging to balance the desired antileukemic effects with undesired excessive myelosuppression during maintenance therapy. A model to simulate the dynamics of different cell types, especially neutrophils, would be a valuable contribution to improving treatment protocols (6MP and MTX dosing regimens) and a further step to understanding the heterogeneity in treatment efficacy and toxicity. We applied and modified a recently developed semi-mechanistic PK/PD model to neutrophils and analyzed their behavior using a non-linear mixed-effects modeling approach and clinical data obtained from 116 patients. The PK model of 6MP influenced the accuracy of absolute neutrophil count (ANC) predictions, whereas the PD effect of MTX did not. Predictions based on ANC were more accurate than those based on white blood cell counts. Using the new cross-validated mathematical model, simulations of different treatment protocols showed a linear dose-effect relationship and reduced ANC variability for constant dosages. Advanced modeling allows the identification of optimized control criteria and the weighting of specific influencing factors for protocol design and individually adapted therapy to exploit the optimal effect of maintenance therapy on survival.
CRIS-Team Scopus Importer:2020-04-14
Keywords: 6-mercaptopurine; childhood acute lymphoblastic leukemia; maintenance therapy; methotrexate; neutropenia; non-linear mixed-effects modeling; population pharmacokinetics/pharmacodynamics

Multisite measurement of regional oxygen saturation in Fontan patients with and without protein-losing enteropathy at rest and during exercise - Schroeer, Simon; Fahlbusch, Fabian B.; Münch, Frank; Alkassar, Muhannad; Toka, Hakan R.; Rauh, Manfred; Rueffer, Andre; Cesnjevar, Robert; Dittrich, Sven; Toka, Okan; Moosmann, Julia (Pediatric Research, 2019)
Background: Protein-losing enteropathy (PLE) is a severe complication of Fontan circulation with increased risk of end-organ dysfunction. We evaluated tissue oxygenation via near-infrared spectroscopy (NIRS) at different exercise levels in Fontan patients. Methods: Assessment of multisite NIRS during cycle ergometer exercise and daily activities in three groups: Fontan patients with PLE; without PLE; patients with dextro-transposition of the great arteries (d-TGA); comparing univentricular with biventricular circulation and Fontan with/without PLE. Renal threshold analysis (<65%;<55%;<45%) of regional oxygen saturation (rSO2) was performed. Results: Fontan patients showed reduced rSO2 (p < 0.05) in their quadriceps femoris muscle compared with biventricular d-TGA patients at all time points. rSO2 in renal tissue was reduced at baseline (p = 0.002), exercise (p = 0.0062), and daily activities (p = 0.03) in Fontan patients with PLE. Renal threshold analysis identified critically low renal rSO2 (rSO2 < 65%) in Fontan patients with PLE during exercise (95% of monitoring time below threshold) and daily activities (83.7% time below threshold). Conclusion: Fontan circulation is associated with decreased rSO2 values in skeletal muscle and hypoxemia of renal tissue solely in patients with PLE. Reduced rSO2 already during activities of daily life, might contribute to comorbidities in patients with Fontan circulation, including PLE and renal failure.
CRIS-Team Scopus Importer:2019-05-21

Neutrophil Extracellular Traps Initiate Gallstone Formation - Munoz, Luis Enrique; Boeltz, Sebastian; Bilyy, Rostyslav; Schauer, Christine; Mahajan, Aparna; Widulin, Navena; Grüneboom, Anika; Herrmann, Irmgard; Boada, Edgyda; Rauh, Manfred; Krenn, Veit; Biermann, Mona H.C.; et al. (Immunity, 2019)
The presence of gallstones (cholelithiasis) is a highly prevalent and severe disease and one of the leading causes of hospital admissions worldwide. Due to its substantial health impact, we investigated the biological mechanisms that lead to the formation and growth of gallstones. We show that gallstone assembly essentially requires neutrophil extracellular traps (NETs). We found consistent evidence for the presence of NETs in human and murine gallstones and describe an immune-mediated process requiring activation of the innate immune system for the formation and growth of gallstones. Targeting NET formation via inhibition of peptidyl arginine deiminase type 4 or abrogation of reactive oxygen species (ROS) production, as well as damping of neutrophils by metoprolol, effectively inhibit gallstone formation in vivo. Our results show that after the physicochemical process of crystal formation, NETs foster their assembly into larger aggregates and finally gallstones. These insights provide a feasible therapeutic concept to prevent cholelithiasis in patients at risk.
CRIS-Team Scopus Importer:2019-09-17
Keywords: calcium carbonate crystals; cholesterol crystals; gallstone growth; gallstones; lisosomal leakage; lithogenic diet; neutrophil extracellular traps; neutrophils; NOX2; PADi4

NEXT-GENERATION REFERENCE INTERVALS FOR PEDIATRIC HEMATOLOGY - Zierk, Jakob; Hirschmann, J.; Toddenroth, Dennis; Arzideh, F.; Streichert, T.; Haeckel, R.; Prokosch, Hans-Ulrich; Rauh, Manfred; Metzler, Markus (2017)
EVALuna2:32792

Next-generation reference intervals for pediatric hematology - Zierk, Jakob; Hirschmann, Johannes; Toddenroth, Dennis; Arzideh, Farhad; Haeckel, Rainer; Bertram, Alexander; Cario, Holger; Frühwald, Michael C.; Groß, Hans Jürgen; Groening, Arndt; Grützner, Stefanie; Gscheidmeier, Thomas; et al. (Clinical Chemistry and Laboratory Medicine, 2019)
Interpreting hematology analytes in children is challenging due to the extensive changes in hematopoiesis that accompany physiological development and lead to pronounced sex- and age-specific dynamics. Continuous percentile charts from birth to adulthood allow accurate consideration of these dynamics. However, the ethical and practical challenges unique to pediatric reference intervals have restricted the creation of such percentile charts, and limitations in current approaches to laboratory test result displays restrict their use when guiding clinical decisions. We employed an improved data-driven approach to create percentile charts from laboratory data collected during patient care in 10 German centers (9,576,910 samples from 358,292 patients, 412,905-1,278,987 samples per analyte). We demonstrate visualization of hematology test results using percentile charts and z-scores (www.pedref.org/hematology) and assess the potential of percentiles and z-scores to support diagnosis of different hematological diseases. We created percentile charts for hemoglobin, hematocrit, red cell indices, red cell count, red cell distribution width, white cell count and platelet count in girls and boys from birth to 18 years of age. Comparison of pediatricians evaluating complex clinical scenarios using percentile charts versus conventional/tabular representations shows that percentile charts can enhance physician assessment in selected example cases. Age-specific percentiles and z-scores, compared with absolute test results, improve the identification of children with blood count abnormalities and the discrimination between different hematological diseases. The provided reference intervals enable precise assessment of pediatric hematology test results. Representation of test results using percentiles and z-scores facilitates their interpretation and demonstrates the potential of digital approaches to improve clinical decision-making.
CRIS-Team Scopus Importer:2019-05-09
Keywords: hematology; laboratory test result display; pediatric reference intervals

NFATc1 in CD4+ T cells and CD11c+ dendritic cells drives TH2-mediated eosinophilic inflammation in allergic asthma - Yang, Zuqin; Krammer, Susanne; Mitländer, Hannah; Grund, Janina; Zirlik, Sabine; Wirtz, Stefan; Rauh, Manfred; Sadeghi Shermeh, Atefeh; Finotto, Susetta (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Asthma, a chronic lung disease, is a significant public health problem worldwide. It is marked by increased TH2 response resulting in eosinophil accumulation. The pathophysiology of asthma involves various cell types, including epithelial cells, dendritic cells (DCs), innate lymphoid cells, B cells, and effector cells. Nuclear factor of activated T cells, cytoplasmic 1 (NFATc1), a critical transcription factor for immune regulation, is known for its role in T cells and, more recently, in myeloid cells. However, the specific contributions of NFATc1 in T cells and DCs in the context of asthma are not well understood. Objective: We explored NFATc1’s role in T cells and DCs in modulating TH2 immune responses within the pathophysiology of allergic asthma. Methods: We induced asthma in mice lacking Nfatc1 in CD4+ T cells or CD11c+ DCs using house dust mite, thereby enabling investigation into NFATc1’s role in both cell types in experimental allergic asthma. Additionally, we examined NFATc1 expression in these cell types and its correlation with blood eosinophil levels in an adult asthma cohort. Results: In a house dust mite–induced asthma model, we found that Nfatc1 deficiency either in CD4+ T cells or CD11c+ DCs resulted in reduced TH2-driven eosinophilic inflammation, IgE levels, and mast cell presence in the lung of asthmatic mice. Nfatc1’s absence in CD4+ T cells directly hampered TH2 cell polarization and functionality, whereas in CD11c+ DCs, it affected DC differentiation and maturation, thereby weakening T-cell priming, proliferation, and subsequent TH2 differentiation. Correspondingly, translational research indicated significant correlations between CD4+NFATc1+ and CD11c+NFATc1+ cell populations and eosinophil levels in asthmatic patients, but not in healthy controls. Conclusion: NFATc1 in T cells and DCs modulates TH2-mediated eosinophilic inflammation in allergic asthma, thus offering insight into asthma pathogenesis and identifying NFATc1 as a potential target for therapeutic intervention.
CRIS-Team Scopus Importer:2024-11-15
Keywords: allergic asthma; dendritic cells; eosinophils; NFATc1; T cells; T

Nrf2-Keap1 pathway promotes cell proliferation and diminishes ferroptosis - Fan, Zheng; Wirth, A-K; Chen, Daishi; Wruck, C. J.; Rauh, Manfred; Buchfelder, Michael; Savaskan, Nicolai (Oncogenesis, 2017)
Cancer cells are hallmarked by high proliferation and imbalanced redox consumption and signaling. Various oncogenic pathways such as proliferation and evading cell death converge on redox-dependent signaling processes. Nrf2 is a key regulator in these redox-dependent events and operates in cytoprotection, drug metabolism and malignant progression in cancer cells. Here, we show that patients with primary malignant brain tumors (glioblastomas, WHO °IV gliomas, GBM) have a devastating outcome and overall reduced survival when Nrf2 levels are upregulated. Nrf2 overexpression or Keap1 knockdown in glioma cells accelerate proliferation and oncogenic transformation. Further, activation of the Nrf2-Keap1 signaling upregulates xCT (aka SLC7A11 or system Xc-) and amplifies glutamate secretion thereby impacting on the tumor microenvironment. Moreover, both fostered Nrf2 expression and conversely Keap1 inhibition promote resistance to ferroptosis. Altogether, the Nrf2-Keap1 pathway operates as a switch for malignancy in gliomas promoting cell proliferation and resistance to cell death processes such as ferroptosis. Our data demonstrate that the Nrf2-Keap1 pathway is critical for cancer cell growth and operates on xCT. Nrf2 presents the Achilles' heel of cancer cells and thus provides a valid therapeutic target for sensitizing cancer for chemotherapeutics.
EVALuna2:34244

On Sweat Analysis for Quantitative Estimation of Dehydration during Physical Exercise - Ring, Matthias; Lohmüller, Clemens; Rauh, Manfred; Eskofier, Björn (Proceedings of the 2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2015)
Quantitative estimation of water loss during physical exercise is of importance because dehydration can impair both muscular strength and aerobic endurance. A physiological indicator for deficit of total body water (TBW) might be the concentration of electrolytes in sweat. It has been shown that concentrations differ after physical exercise depending on whether water loss was replaced by fluid intake or not. However, to the best of our knowledge, this fact has not been examined for its potential to quantitatively estimate TBW loss. Therefore, we conducted a study in which sweat samples were collected continuously during two hours of physical exercise without fluid intake. A statistical analysis of these sweat samples revealed significant correlations between chloride concentration in sweat and TBW loss (r = 0.41, p < 0.01), and between sweat osmolality and TBW loss (r = 0.43, p < 0.01). A quantitative estimation of TBW loss resulted in a mean absolute error of 0.49 l per estimation. Although the precision has to be improved for practical applications, the present results suggest that TBW loss estimation could be realizable using sweat samples.

Pediatric reference intervals for alkaline phosphatase - Zierk, Jakob; Arzideh, Farhad; Haeckel, Rainer; Cario, Holger; Fruehwald, Michael C.; Gross, Hans-Juergen; Gscheidmeier, Thomas; Hoffmann, Reinhard; Krebs, Alexander; Lichtinghagen, Ralf; Neumann, Michael; Ruf, Hans-Georg; et al. (Clinical Chemistry and Laboratory Medicine, 2017)
BACKGROUND: Interpretation of alkaline phosphatase activity in children is challenging due to extensive changes with growth and puberty leading to distinct sex- and age-specific dynamics. Continuous percentile charts from birth to adulthood allow accurate consideration of these dynamics and seem reasonable for an analyte as closely linked to growth as alkaline phosphatase. However, the ethical and practical challenges unique to pediatric reference intervals have restricted the creation of such percentile charts, resulting in limitations when clinical decisions are based on alkaline phosphatase activity. METHODS: We applied an indirect method to generate percentile charts for alkaline phosphatase activity using clinical laboratory data collected during the clinical care of patients. A total of 361,405 samples from 124,440 patients from six German tertiary care centers and one German laboratory service provider measured between January 2004 and June 2015 were analyzed. Measurement of alkaline phosphatase activity was performed on Roche Cobas analyzers using the IFCC's photometric method. RESULTS: We created percentile charts for alkaline phosphatase activity in girls and boys from birth to 18 years which can be used as reference intervals. Additionally, data tables of age- and sex-specific percentile values allow the incorporation of these results into laboratory information systems. CONCLUSIONS: The percentile charts provided enable the appropriate differential diagnosis of changes in alkaline phosphatase activity due to disease and changes due to physiological development. After local validation, integration of the provided percentile charts into result reporting facilitates precise assessment of alkaline phosphatase dynamics in pediatrics.
EVALuna2:34216

Pharmacokinetic–pharmacodynamic modeling of maintenance therapy for childhood acute lymphoblastic leukemia - Gebhard, Anna; Lilienthal, Patrick; Metzler, Markus; Rauh, Manfred; Sager, Sebastian; Schmiegelow, Kjeld; Toksvang, Linea Natalie; Zierk, Jakob (Scientific Reports, 2023)
In the treatment of childhood acute lymphoblastic leukemia (ALL), current protocols combine initial high-dose multiagent chemotherapy with prolonged oral therapy with 6-mercaptopurine (6MP) and low-dose methotrexate (MTX) maintenance therapy. Decades of research on ALL treatment have resulted in survival rates of approximately 90%. However, dose-response relationships vary widely between patients and insight into the influencing factors, that would allow for improved personalized treatment management, is insufficient. We use a detailed data set with measurements of thioguanine nucleotides and MTX in red blood cells and absolute neutrophil count (ANC) to develop pharmacokinetic models for 6MP and MTX, as well as a pharmacokinetic–pharmacodynamic (PKPD) model capable of predicting individual ANC levels and thus contributing to the development of personalized treatment strategies. Here, we show that integrating metabolite measurements in red blood cells into the full PKPD model improves results when less data is available, but that model predictions are comparable to those of a fixed pharmacokinetic model when data availability is not limited, providing further evidence of the quality of existing models. With this comprehensive model development leading to dynamics similar to simpler models, we validate the suitability of this model structure and provide a foundation for further exploration of maintenance therapy strategies through simulation and optimization.
CRIS-Team Scopus Importer:2023-09-08

Plasma concentrations of the amyloid-? peptides in young volunteers: the influence of the APOE genotype - Zimmermann, Rüdiger; Huber, Ellen; Schamber, Christine; Lelental, Natalia; Mroczko, Barbara; Brandner, Sebastian; Maler, Juan Manuel; Oberstein, Timo; Szmitkowski, Maciej; Rauh, Manfred; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Alzheimer's Disease, 2014)
Changes in the concentrations of amyloid-? (A?) in the body fluids are the earliest alterations observed in Alzheimer's disease (AD), however, there is a lack of data about how early these alterations occur, before the onset of the clinical symptoms. APOE genotype is the most recognized genetic risk/protective factor of AD, meaning that a group of non-demented persons carrying ?4 allele is enriched in the subjects who will develop AD, compared to the group of non-carriers. Therefore, we studied the plasma concentrations of A? peptides (A?1-42, A?1-40, A?x-42, and A?x-40), and the APOE genotype in 173 young volunteers (average age, 28 ± 7.6 years) without memory deficits, in order to see whether the non-demented group of subjects at risk already characterize with A? changes three-to-four decades before the age at which dementia usually occurs. We did not find statistically significant differences among the groups of ?4 carriers, ?3 homozygotes, and ?2 carriers. We conclude that the APOE genotype does not influence the metabolism of the A? peptides in young persons without memory deficits.
EVALuna2:18883

Prospective, randomized, double-blind, placebo-controlled phase IIa clinical trial on the effects of an estrogen-progestin combination as add-on to inpatient psychotherapy in adult female patients suffering from anorexia nervosa - Paslakis, Georgios; Maas, Stefanie; Gebhardt, Bernd; Mayr, Andreas; Rauh, Manfred; Erim, Yesim (BMC Psychiatry, 2018)

Pulmonary Dysfunction after Pediatric COVID-19 - Heiß, Rafael; Tan, Lina; Schmidt, Sandy; Regensburger, Adrian; Ewert, Franziska; Mammadova, Dilbar; Bühler, Adrian; Vogel-Claussen, Jens; Voskrebenzev, Andreas; Rauh, Manfred; Rompel, Oliver; Nagel, Armin Michael; et al. (Radiology, 2022)
Background Long COVID occurs in lower frequency in children and adolescents than in adults. Morphologic and free-breathing phase-resolved functional low-field MRI may identify persistent pulmonary manifestations after SARS-CoV-2 infection. Purpose To characterize both morphologic and functional changes of lung parenchyma on low-field MRI in children and adolescents with post COVID-19 compared with healthy controls. Materials and Methods Between August and December 2021, a cross-sectional, prospective clinical trial using low-field MRI was performed in children and adolescents from a single academic medical center. The primary outcome was the frequency of morphologic changes on MRI. Secondary outcomes included MRI-derived functional proton ventilation and perfusion parameters. Clinical symptoms, the duration from positive RT-PCR test and serological parameters were compared with imaging results. Nonparametric tests for pairwise and corrected tests for groupwise comparisons were applied to assess differences in healthy controls, recovered participants and with long COVID. Results A total of 54 participants post COVID-19 infection (mean age, 11 years ±3 [SD], 56 males) and 9 healthy controls (mean age, 10 years ±3 [SD], 70 males) were included: 29 (54%) in the COVID-19 group had recovered from infection and 25 (46%) were classified as having long COVID on the day of enrollment. Morphologic abnormality was identified in one recovered participant. Both ventilated and perfused lung parenchyma (V/Q match) was reduced from 81±6.1% in healthy controls to 62±19% (P =.006) in the recovered group and 60±20% (P=.003) in the long COVID group. V/Q match was lower in post COVID patients with infection less than 180 days (63±20%, P=.03), 180 to 360 days (63±18%, P=0.03) and 360 days ago (41±12%, P<.001) as compared with the never-infected healthy controls (81±6.1%). Conclusion Low-field MRI showed persistent pulmonary dysfunction in both children and adolescents recovered from COVID-19 and with long COVI

Reduced Perinatal Leptin Availability May Contribute to Adverse Metabolic Programming in a Rat Model of Uteroplacental Insufficiency - Nuesken, Eva; Wohlfarth, Maria; Lippach, Gregor; Rauh, Manfred; Schneider, Holm; Doetsch, Joerg; Nuesken, Kai-Dietrich (Endocrinology, 2016)
Leptin availability in perinatal life critically affects metabolic programming. We tested the hypothesis that uteroplacental insufficiency and intrauterine stress affect perinatal leptin availability in rat offspring. Pregnant rats underwent bilateral uterine vessel ligation (LIG; n = 14), sham operation (SOP; n = 12), or no operation (controls, n = 14). Fetal livers (n = 180), placentas (n = 180), and maternal blood were obtained 4 hours (gestational day [E] 19), 24 hours (E20), and 72 hours (E22) after surgery. In the offspring, we took blood samples on E22 (n = 44), postnatal day (P) 1 (n = 29), P2 (n = 16), P7 (n = 30), and P12 (n = 30). Circulating leptin (ELISA) was significantly reduced in LIG (E22, P1, P2) and SOP offspring (E22). Postnatal leptin surge was delayed in LIG but was accelerated in SOP offspring. Placental leptin gene expression (quantitative RT-PCR) was reduced in LIG (E19, E20, E22) and SOP (E20, E22). Hepatic leptin receptor (Lepr-a, mediating leptin degradation) gene expression was increased in LIG fetuses (E20, E22) only. Surprisingly, hypoxia-inducible factors (Hif; Western blot) were unaltered in placentas and were reduced in the livers of LIG (Hif1a, E20; Hif2a, E19, E22) and SOP (Hif2a, E19) fetuses. Gene expression of prolyl hydroxylase 3, a factor expressed under hypoxic conditions contributing to Hif degradation, was increased in livers of LIG (E19, E20, E22) and SOP (E19) fetuses and in placentas of LIG and SOP (E19). In summary, reduced placental leptin production, increased fetal leptin degradation, and persistent perinatal hypoleptinemia are present in intrauterine growth restriction offspring, especially after uteroplacental insufficiency, and may contribute to perinatal programming of leptin resistance and adiposity in later life.
EVALuna2:33880

Reduction of Tissue Na+ Accumulation After Renal Transplantation - Dahlmann, Anke; Linz, Peter; Zucker, Isabelle; Haag, Viktor; Jantsch, Jonathan; Dienemann, Thomas; Nagel, Armin Michael; Neubert, Patrick; Rosenhauer, Daniela; Rauh, Manfred; Horn, Stephan; Müller, Dominik N.; et al. (Kidney International Reports, 2021)
Introduction: Chronic kidney disease (CKD) engenders salt-sensitive hypertension. Whether or not tissue Nathorn accumulation is increased in CKD patients remains uncertain. How tissue Nathorn is affected after renal transplantation has not been assessed.
CRIS-Team WoS Importer:2021-10-01

Reference Interval Estimation from Mixed Distributions using Truncation Points and the Kolmogorov-Smirnov Distance (kosmic) - Zierk, Jakob; Arzideh, Farhad; Kapsner, Lorenz; Prokosch, Hans-Ulrich; Metzler, Markus; Rauh, Manfred (Scientific Reports, 2020)
Appropriate reference intervals are essential when using laboratory test results to guide medical decisions. Conventional approaches for the establishment of reference intervals rely on large samples from healthy and homogenous reference populations. However, this approach is associated with substantial financial and logistic challenges, subject to ethical restrictions in children, and limited in older individuals due to the high prevalence of chronic morbidities and medication. We implemented an indirect method for reference interval estimation, which uses mixed physiological and abnormal test results from clinical information systems, to overcome these restrictions. The algorithm minimizes the difference between an estimated parametrical distribution and a truncated part of the observed distribution, specifically, the Kolmogorov-Smirnov-distance between a hypothetical Gaussian distribution and the observed distribution of test results after Box-Cox-transformation. Simulations of common laboratory tests with increasing proportions of abnormal test results show reliable reference interval estimations even in challenging simulation scenarios, when <20% test results are abnormal. Additionally, reference intervals generated using samples from a university hospital’s laboratory information system, with a gradually increasing proportion of abnormal test results remained stable, even if samples from units with a substantial prevalence of pathologies were included. A high-performance open-source C++ implementation is available at https://gitlab.miracum.org/kosmic.
CRIS-Team Scopus Importer:2020-02-14

refineR: A Novel Algorithm for Reference Interval Estimation from Real-World Data - Ammer, Tatjana; Schuetzenmeister, Andre; Prokosch, Hans-Ulrich; Rauh, Manfred; Rank, Christopher M.; Zierk, Jakob (Scientific Reports, 2021)
Reference intervals are essential for the interpretation of laboratory test results in medicine. We propose a novel indirect approach to estimate reference intervals from real-world data as an alternative to direct methods, which require samples from healthy individuals. The presented refineR algorithm separates the non-pathological distribution from the pathological distribution of observed test results using an inverse approach and identifies the model that best explains the non-pathological distribution. To evaluate its performance, we simulated test results from six common laboratory analytes with a varying location and fraction of pathological test results. Estimated reference intervals were compared to the ground truth, an alternative indirect method (kosmic), and the direct method (N = 120 and N = 400 samples). Overall, refineR achieved the lowest mean percentage error of all methods (2.77%). Analyzing the amount of reference intervals within ± 1 total error deviation from the ground truth, refineR (82.5%) was inferior to the direct method with N = 400 samples (90.1%), but outperformed kosmic (70.8%) and the direct method with N = 120 (67.4%). Additionally, reference intervals estimated from pediatric data were comparable to published direct method studies. In conclusion, the refineR algorithm enables precise estimation of reference intervals from real-world data and represents a viable complement to the direct method.
CRIS-Team Scopus Importer:2021-08-27

Regulated on Activation, Normal T cell Expressed and Secreted (RANTES) drives the resolution of allergic asthma - Li, Nina; Mirzakhani, Hoomann; Kiefer, Alexander; Kölle, Julia; Vuorinen, Tytti; Rauh, Manfred; Yang, Zuqin; Krammer, Susanne; Xepapadaki, Paraskevi; Lewandowska-Polak, Anna; Lukkarinen, Heikki; Zhang, Nan; et al. (iScience, 2021)
RANTES is implicated in allergic asthma and in T cell-dependent clearance of infection. RANTES receptor family comprises CCR1, CCR3, and CCR5, which are G-protein-coupled receptors consisting of seven transmembrane helices. Infections with respiratory viruses like Rhinovirus cause induction of RANTES production by epithelial cells. Here, we studied the role of RANTES in the peripheral blood mononuclear cells in cohorts of children with and without asthma and validated and extended this study to the airways of adults with and without asthma. We further translated these studies to a murine model of asthma induced by house dust mite allergen in wild-type RANTES and CCR5-deficient mice. Here we show an unpredicted therapeutic role of RANTES in the resolution of allergen-induced asthma by orchestrating the transition of effector GATA-3+CD4+ T cells into immune-regulatory-type T cells and inflammatory eosinophils into resident eosinophils as well as increased IL-10 production in the lung.
CRIS-Team WoS Importer:2021-11-19

RELATION BETWEEN NOISE ANNOYANCE, STRESS HORMONES AND THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Rauh, Manfred; Ott, Christian; Striepe, Kristina; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Renal adaptation in pre-obesity patients with hypertension - Bosch, Agnes; Rauh, Manfred; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Journal of Hypertension, 2024)
Background and hypothesis: Obesity aggravates the risk to develop chronic kidney disease in hypertensive patients. Whether pre-obesity already impairs renal function, renal perfusion and intraglomerular hemodynamics in hypertensive patients is unknown. Methods: Renal hemodynamic profiles were measured using steady state input clearance (infusion of para-amino-hippuric acid and inulin) in 36 patients with primary arterial hypertension stage 1-2 without antihypertensive medication. Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated. The study population was divided into two groups based on median of waist circumference (WC) (96 cm) (pre-obesity and non-obesity group1) and median of body mass index (BMI) (26.5 kg/m2) (pre-obesity and non-obesity group2), respectively. Results: All patients were males, non-smoking, aged 36 ± 10 years, with an office blood pressure of 145 ± 8.6/89 ± 11.8 mmHg. None of the patients had cardiovascular disease. Patients from the pre-obese group 1 showed lower glomerular filtration rate (GFR), lower renal plasma flow (RPF) and lower IGP compared to the non-obese group1. Renal vascular resistance (RVR) and RA were higher in the pre-obese group1 compared to the non-obese group1. Similar differences in the hemodynamic profile were found for patients in the pre-obesity group2 compared to the non-obesity group2. Conclusion: The renal hemodynamic profile in hypertensive patients with pre-obesity, irrespective whether defined by WC or BMI, was characterized by a reduced GFR and RPF and by an increased RVR preferentially at the preglomerular site. Our results suggest that hypofiltration is the first phase of renal adaptation in pre-obesity hypertension.
CRIS-Team Scopus Importer:2024-09-20
Keywords: body mass index; clearance analysis; pre-obesity; renal hemodynamic; waist circumference

Report from the HarmoSter study: Different LC-MS/MS androstenedione, DHEAS and testosterone methods compare well; however, unifying calibration is a double-edged sword - Fanelli, Flaminia; Peitzsch, Mirko; Bruce, Stephen; Cantù, Marco; Temchenko, Anastasia; Mezzullo, Marco; Lindner, Johanna M.; Hawley, James M.; Ackermans, Mariette T.; Van Den Ouweland, Jody; Köppl, Daniel; Nardi, Elena; et al. (Clinical Chemistry and Laboratory Medicine, 2024)
Current LC-MS/MS applications for circulating androgen measurements are technically diverse. Previously, variable results have been reported for testosterone. Data are scarce for androstenedione and absent for DHEAS. We assessed the agreement of androstenedione, DHEAS and testosterone LC-MS/MS measurements among nine European centers and explored benefits of calibration system unification. Androgens were measured twice by laboratory-specific procedures in 78 patient samples and in EQA materials. Results were obtained by in-house and external calibration. Intra- and inter-laboratory performances were valued. Intra-laboratory CVs ranged between 4.2-13.2 » % for androstenedione, 1.6-10.8 » % for DHEAS, and 4.3-8.7 » % and 2.6-7.1 » % for female and male testosterone, respectively. Bias and trueness in EQA materials were within ±20 » %. Median inter-laboratory CV with in-house vs. external calibration were 12.0 vs. 9.6 » % for androstenedione (p<0.001), 7.2 vs. 4.9 » % for DHEAS (p<0.001), 6.4 vs. 7.6 » % for female testosterone (p<0.001) and 6.8 and 7.4 » % for male testosterone (p=0.111). Median bias vs. all laboratory median with in-house and external calibration were -13.3 to 20.5 » % and -4.9 to 18.7 » % for androstenedione, -10.9 to 4.8 » % and -3.4 to 3.5 » % for DHEAS, -2.7 to 6.5 % and -11.3 to 6.6 » % for testosterone in females, and -7.0 to 8.5 » % and -7.5 to 11.8 » % for testosterone in males, respectively. Methods showed high intra-laboratory precision but variable bias and trueness. Inter-laboratory agreement was remarkably good. Calibration system unification improved agreement in androstenedione and DHEAS, but not in testosterone measurements. Multiple components, such as commutability of calibrators and EQA materials and internal standard choices, likely contribute to inter-laboratory variability.
CRIS-Team Scopus Importer:2024-01-26
Keywords: androstenedione; dehydroepiandrosterone-sulfate; harmonization; inter-laboratory performance; liquid chromatography-tandem mass spectrometry; testosterone

Report from the HarmoSter study: impact of calibration on comparability of LC-MS/MS measurement of circulating cortisol, 17OH-progesterone and aldosterone - Fanelli, Flaminia; Cantu, Marco; Temchenko, Anastasia; Mezzullo, Marco; Lindner, Johanna M.; Peitzsch, Mirko; Hawley, James M.; Bruce, Stephen; Binz, Pierre-Alain; Ackermans, Mariette T.; Heijboer, Annemieke C.; Van Den Ouweland, Jody; et al. (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives Liquid chromatography-tandem mass spectrometry (LC-MS/MS) is recommended for measuring circulating steroids. However, assays display technical heterogeneity. So far, reproducibility of corticosteroid LC-MS/MS measurements has received scant attention. The aim of the study was to compare LC-MS/MS measurements of cortisol, 17OH-progesterone and aldosterone from nine European centers and assess performance according to external quality assessment (EQA) materials and calibration. Methods Seventy-eight patient samples, EQA materials and two commercial calibration sets were measured twice by laboratory-specific procedures. Results were obtained by in-house (CAL1) and external calibrations (CAL2 and CAL3). We evaluated intra and inter-laboratory imprecision, correlation and agreement in patient samples, and trueness, bias and commutability in EQA materials. Results Using CAL1, intra-laboratory CVs ranged between 2.8-7.4%, 4.4-18.0% and 5.2-22.2%, for cortisol, 17OH-progesterone and aldosterone, respectively. Trueness and bias in EQA materials were mostly acceptable, however, inappropriate commutability and target value assignment were highlighted in some cases. CAL2 showed suboptimal accuracy. Median inter-laboratory CVs for cortisol, 17OH-progesterone and aldosterone were 4.9, 11.8 and 13.8% with CAL1 and 3.6, 10.3 and 8.6% with CAL3 (all p<0.001), respectively. Using CAL1, median bias vs. all laboratory-medians ranged from -6.6 to 6.9%, -17.2 to 7.8% and -12.0 to 16.8% for cortisol, 17OH-progesterone and aldosterone, respectively. Regression lines significantly deviated from the best fit for most laboratories. Using CAL3 improved cortisol and 17OH-progesterone between-method bias and correlation. Conclusions Intra-laboratory imprecision and performance with EQA materials were variable. Inter-laboratory performance was mostly within specifications. Although residual variability persists, adopting common traceable calibrators and RMP-determined EQA materials is beneficial for standardization of LC-MS/MS steroid measurements.
CRIS-Team WoS Importer:2022-03-04

Report from the HarmoSter study: inter-laboratory comparison of LC-MS/MS measurements of corticosterone, 11-deoxycortisol and cortisone - Fanelli, Flaminia; Bruce, Stephen; Cantu, Marco; Temchenko, Anastasia; Mezzullo, Marco; Lindner, Johanna M.; Peitzsch, Mirko; Binz, Pierre-Alain; Ackermans, Mariette T.; Heijboer, Annemieke C.; Van Den Ouweland, Jody; Koeppl, Daniel; et al. (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives Liquid chromatography-tandem mass spectrometry (LC-MS/MS) panels that include glucocorticoid-related steroids are increasingly used to characterize and diagnose adrenal cortical diseases. Limited information is currently available about reproducibility of these measurements among laboratories. The aim of the study was to compare LC-MS/MS measurements of corticosterone, 11-deoxycortisol and cortisone at eight European centers and assess the performance after unification of calibration. Methods Seventy-eight patient samples and commercial calibrators were measured twice by laboratory-specific procedures. Results were obtained according to in-house and external calibration. We evaluated intra-laboratory and inter-laboratory imprecision, regression and agreement against performance specifications derived from 11-deoxycortisol biological variation. Results Intra-laboratory CVs ranged between 3.3 and 7.7%, 3.3 and 11.8% and 2.7 and 12.8% for corticosterone, 11-deoxycortisol and cortisone, with 1, 4 and 3 laboratories often exceeding the maximum allowable imprecision (MAI), respectively. Median inter-laboratory CVs were 10.0, 10.7 and 6.2%, with 38.5, 50.7 and 2.6% cases exceeding the MAI for corticosterone, 11-deoxycortisol and cortisone, respectively. Median laboratory bias vs. all laboratory-medians ranged from -5.6 to 12.3% for corticosterone, -14.6 to 12.4% for 11-deoxycortisol and -4.0 to 6.5% for cortisone, with few cases exceeding the total allowable error. Modest deviations were found in regression equations among most laboratories. External calibration did not improve 11-deoxycortisol and worsened corticosterone and cortisone inter-laboratory comparability. Conclusions Method imprecision was variable. Inter-laboratory performance was reasonably good. However, cases with imprecision and total error above the acceptable limits were apparent for corticosterone and 11-deoxycortisol. Variability did not depend on calibration but apparently on imprecision, accuracy and specificity of individual methods. Tools for improving selectivity and accuracy are required to improve harmonization.
CRIS-Team WoS Importer:2022-11-11

Respiratory infections regulated blood cells IFN-β-PD-L1 pathway in pediatric asthma - Kölle, Julia; Haag, Patricia; Vuorinen, Tytti; Kiefer, Alexander; Rauh, Manfred; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Finotto, Susetta (Immunity, Inflammation and Disease, 2020)
Background: Respiratory infections, in general, and rhinovirus infection specifically are the main reason for asthma exacerbation in children and programmed cell death protein 1 ligand (PD-L1) expression inhibits T cell responses. Objective: Could the interferon (IFN) type I expression in peripheral blood mononuclear cells (PBMCs) improve disease exacerbation in pediatric asthma?. Results: Here we found increased level of PD-L1 messenger RNA (mRNA) in total blood cells isolated from preschool children with virus-induced asthma, with lower percentage of forced expiratory volume in 1 second and with high serum levels of the C-reactive-protein. Conclusions and Clinical Relevance: These data indicate that, in the presence of infection in the airways of preschool children, worse asthma is associated with induced PD-L1 mRNA expression in blood cells. Further, type I IFN, IFN-β, a cytokine that is involved in the clearance of infections, was found to be associated with a better lung function in asthmatic children. These data suggest that improving peripheral blood IFN type I expression in PBMCs in pediatric asthma could improve disease exacerbation due to suppressing PD-L1 expression in blood cells.
CRIS-Team Scopus Importer:2020-05-22
Keywords: human rhinovirus; IFNβ; PD-L1; pediatric asthma

Rhinovirus species/genotypes and interferon-λ: subtypes, receptor and polymorphisms - missing pieces of the puzzle of childhood asthma? - Bergauer, Annika; Sopel, Nina; Kro, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna2:25986

RIbench: A Proposed Benchmark for the Standardized Evaluation of Indirect Methods for Reference Interval Estimation - Ammer, Tatjana; Schuetzenmeister, Andre; Prokosch, Hans-Ulrich; Zierk, Jakob; Rank, Christopher M.; Rauh, Manfred (Clinical Chemistry, 2022)
Background Indirect methods leverage real-world data for the estimation of reference intervals. These constitute an active field of research, and several methods have been developed recently. So far, no standardized tool for evaluation and comparison of indirect methods exists. Methods We provide RIbench, a benchmarking suite for quantitative evaluation of any existing or novel indirect method. The benchmark contains simulated test sets for 10 biomarkers mimicking routine measurements of a mixed distribution of non-pathological (reference) values and pathological values. The non-pathological distributions represent 4 common distribution types: normal, skewed, heavily skewed, and skewed-and-shifted. To identify strengths and weaknesses of indirect methods, test sets have varying sample sizes and pathological distributions differ in location, extent of overlap, and fraction. For performance evaluation, we use an overall benchmark score and sub-scores derived from absolute z-score deviations between estimated and true reference limits. We illustrate the application of RIbench by evaluating and comparing the Hoffmann method and 4 modern indirect methods -TML (Truncated-Maximum-Likelihood), kosmic, TMC (Truncated-Minimum-Chi-Square), and refineR- against one another and against a nonparametric direct method (n = 120). Results For the modern indirect methods, pathological fraction and sample size had a strong influence on the results: With a pathological fraction up to 20% and a minimum sample size of 5000, most methods achieved results comparable or superior to the direct method. Conclusions We present RIbench, an open-source R-package, for the systematic evaluation of existing and novel indirect methods. RIbench can serve as a tool for enhancement of indirect methods, improving the estimation of reference intervals.
CRIS-Team WoS Importer:2022-11-04

Role of nuclear factor of activated T cells 2 (NFATc2) in allergic asthma - Jakobi, M.; Mirzakahni, H.; Kiefer, Alexander; Rauh, Manfred; Zimmermann, Theodor; Papadopoulos, N. G.; Raby, B. A.; Weiss, S. T.; Finotto, Susetta (ALLERGY, 2020)
CRIS-Team WoS Importer:2020-10-02

Routine Surveillance of SARS-CoV-2 Serostatus in Pediatrics Allows Monitoring of Humoral Response - Wachter, Felix; Knieling, Ferdinand; Raming, Roman; Simon, David; Wölfle, Joachim; Hörning, André; Neubert, Antje; Rauh, Manfred; Regensburger, Adrian (Microorganisms, 2023)
The occurrence of SARS-CoV-2 infections during the pandemic was mainly based on PCR testing of symptomatic patients. However, with new variants, vaccinations, and the changing of the clinical disease severity, knowledge about general immunity is elusive. For public health systems, timely knowledge of these conditions is essential, but it is particularly scarce for the pediatric population. Therefore, in this study, we wanted to investigate the spike and nucleocapsid seroprevalence in pediatric patients using routine residual blood tests collected during the pandemic. This prospective observational study was conducted over seven one-month periods. Herein, the latest four time periods (November 2021, January 2022, March 2022, and May 2022) are depicted. Each patient of a tertiary-care center in Germany was anonymized after collection of clinical diagnosis (ICD-10) and then routinely tested for the respective spike and nucleocapsid SARS-CoV-2 antibody titer. A total of 3235 blood samples from four time periods were included. Spike seroprevalence rose from 37.6% to 51.9% to 70.5% to 85.1% and nucleocapsid seroprevalence from 11.6% to 17.0% to 36.7% to 58.1% in May 2022. In detail, significant changes in seroprevalence between age groups but not between sex or diagnosis groups were found. Quantitative measures revealed rising spike and constant nucleocapsid antibody levels over the pandemic with a half-life of 102 days for spike and 45 days for nucleocapsid antibodies. Routine laboratory assessment of SARS-CoV-2 in residual blood specimens of pediatric hospitals enables monitoring of the seroprevalence and may allow inferences about general immunity in this cohort.
EVALuna2:547467
Keywords: COVID-19; pediatrics; seroprevalence; SARS-CoV-2; Omicron; surveillance

Salivary Markers for Quantitative Dehydration Estimation During Physical Exercise - Ring, Matthias; Lohmueller, Clemens; Rauh, Manfred; Mester, Joachim; Eskofier, Björn (IEEE Journal of Biomedical and Health Informatics, 2017)

Serum (1→3)-β-D-glucan and galactomannan levels in patients with cystic fibrosis: a retrospective cohort study - Traeger, Johannes; Melichar, Volker Otto; Meyer, Renate; Rauh, Manfred; Bogdan, Christian; Held, Jürgen (BMC Pulmonary Medicine, 2018)
BACKGROUND: Aspergillus fumigatus is frequently encountered in sputum samples of patients with cystic fibrosis (CF), which traditionally has been interpreted as saprophytic airway colonization. However, this mere bystander role has been challenged by recent data. There is now evidence that Aspergillus fumigatus accelerates the decline of pulmonary function. (1→3)-β-D-glucan (BDG) and galactomannan (GM) are highly sensitive fungal biomarkers that are used to diagnose invasive fungal disease. However, their diagnostic value in CF patients is largely unknown. METHODS: We conducted a retrospective cohort study on 104 CF patients to determine whether serum BDG and GM levels correlate with parameters such as Aspergillus-positive sputum cultures and lung function. RESULTS: Aspergillus fumigatus was persistently detected in 22 of the 104 CF patients (21%). Mean serum BDG and GM levels in the Aspergillus-positive patients were significantly higher than in those without persistent Aspergillus detection (89 versus 40 pg/ml [p = 0.022] and 0.30 versus 0.15 ODI [p = 0.013], respectively). 27 and 7 patients had elevated BDG (≥ 60 pg/ml) or GM levels (> 0.5 ODI), respectivly. BDG and GM levels showed a significant correlation (p = 0.004). Patients with increased serum concentrations of BDG were more frequently Aspergillus-positive (40.7 versus 14.3%, p = 0.004) and had a significantly lower forced expiratory volume in one second (FEV1) than patients with a normal BDG (61.6 versus 77.1%, p = 0.007). In the multivariate analysis, BDG but not GM or the growth of A. fumigatus, proved to be an independent predictor for the FEV1. CONCLUSIONS: CF patients with persistent Aspergillus detection have elevated BDG and GM levels which ranged between healthy and invasively infected patients. Serum BDG may be superior to GM and fungal culture in predicting an impaired lung function in CF patients.
EVALuna2:35821

Sex differences in the development of vascular and renal lesions in mice with a simultaneous deficiency of Apoe and the integrin chain Itga8 - Marek, Ines; Canu, Maurizio; Cordasic, Nada; Rauh, Manfred; Volkert, Gudrun; Fahlbusch, Fabian B.; Rascher, Wolfgang; Hilgers, Karl Friedrich; Hartner, Andrea; Menendez-Castro, Carlos (Biology of Sex Differences, 2017)
BACKGROUND: Apoe-deficient (Apoe-/-) mice develop progressive atherosclerotic lesions with age but no severe renal pathology in the absence of additional challenges. We recently described accelerated atherosclerosis as well as marked renal injury in Apoe-/- mice deficient in the mesenchymal integrin chain Itga8 (Itga8-/-). Here, we used this Apoe-/-, Itga8-/- mouse model to investigate the sex differences in the development of atherosclerosis and concomitant renal injury. We hypothesized that aging female mice are protected from vascular and renal damage in this mouse model. METHODS: Apoe-/- mice were backcrossed with Itga8-/- mice. Mice were kept on a normal diet. At the age of 12 months, the aortae and kidneys of male and female Apoe-/-Itga8+/+ mice or Apoe-/-Itga8-/- mice were studied. En face preparations of the aorta were stained with Sudan IV (lipid deposition) or von Kossa (calcification). In kidney tissue, immunostaining for collagen IV, CD3, F4/80, and PCNA and real-time PCR analyses for Il6, Vegfa, Col1a1 (collagen I), and Ssp1 (secreted phosphoprotein 1, synonym osteopontin) as well as ER stress markers were performed. RESULTS: When compared to male mice, Apoe-/-Itga8+/+ female mice had a lower body weight, equal serum cholesterol levels, and lower triglyceride levels. However, female mice had increased aortic lipid deposition and more aortic calcifications than males. Male Apoe-/- mice with the additional deficiency of Itga8 developed increased serum urea, glomerulosclerosis, renal immune cell infiltration, and reduced glomerular cell proliferation. In females of the same genotype, these renal changes were less pronounced and were accompanied by lower expression of interleukin-6 and collagen I, while osteopontin expression was higher and markers of ER stress were not different. CONCLUSIONS: In this model of atherosclerosis, the female sex is a risk factor to develop more severe atherosclerotic lesions, even though serum fat levels are higher in males. In contrast, female mice are protected from renal damage, which is accompanied by attenuated inflammation and matrix deposition. Thus, sex affects vascular and renal injury in a differential manner.
EVALuna2:3958

Short-term response of metabolic hormones to coronary artery bypass surgery - Nemeth, Adam; Cziraki, Attila; Sulyok, Endre; Horvath, Ivan Gabor; Alotti, Nasri; Rauh, Manfred; Rascher, Wolfgang; Szabados, Sandor (Advances in Medical Sciences, 2014)
To explore the response pattern of plasma adipokine and ghrelin levels to coronary artery bypass graft (CABG) surgery in patients with (on-pump) and without (off-pump) cardiopulmonary bypass (CPB).Sixteen consecutive patients (age: 62 ± 10 years, male: 10) with obstructive coronary artery disease (CAD) who underwent elective CABG surgery with CPB and intraoperative GIK infusion were selected for on-pump group and 19 CAD patients (age: 63 ± 10 years, male: 16) were included in the off-pump group. Blood samples were taken before, during and after surgery. Intraoperative samples were withdrawn simultaneously for peripheral vein and sinus coronarius (SC). Plasma adipokine concentrations were measured by ELISA, those of ghrelin by RIA kits.In response to surgical intervention there was an early, transient fall in plasma levels of adiponectin (p<0.0001) and resistin (p=0.002) followed by an increase to approach their initial values. Plasma ghrelin also increased (p=0.045), this increase, however, was confined to the period of GIK supported CPB. Plasma insulin (p=0.003) and resistin (p=0.009) was significantly higher in the peripheral vein than in SC. The perioperative hormone profile of patients without CPB (off-pump) proved to be comparable to that of on-pump patients in spite of the insulin administration and greater oxidative and inflammatory stress.Adipose tissue-derived factors appear to mediate the metabolic and vascular changes that occur in patients with CABG surgery. Epicardial adipose tissue is unlikely to have major contribution to the development of CAD as adipokines are not elevated in SC independent of the mode of intervention.
EVALuna2:18893

Soluble CD83 Triggers Resolution of Arthritis and Sustained Inflammation Control in IDO Dependent Manner - Royzman, Dmytro; Andrev, Darja; Stich, Lena; Rauh, Manfred; Bäuerle, Tobias; Ellmann, Stephan; Boon, Louis; Kindermann, Markus; Peckert, Katrin; Bozec, Aline; Schett, Georg; Steinkasserer, Alexander; et al. (Frontiers in Immunology, 2019)
Interference with autoimmune-mediated cytokine production is a key yet poorly developed approach to treat autoimmune and inflammatory diseases such as rheumatoid arthritis. Herein, we show that soluble CD83 (sCD83) enhances the resolution of autoimmune antigen-induced arthritis (AIA) by strongly reducing the expression levels of cytokines such as IL-17A, IFN gamma, IL-6, and TNF alpha within the joints. Noteworthy, also the expression of RANKL, osteoclast differentiation, and joint destruction was significantly inhibited by sCD83. In addition, osteoclasts which were cultured in the presence of synovial T cells, derived from sCD83 treated AIA mice, showed a strongly reduced number of multinuclear large osteoclasts compared to mock controls. Enhanced resolution of arthritis by sCD83 was mechanistically based on IDO, since inhibition of IDO by 1-methyltryptophan completely abrogated sCD83 effects on AIA. Blocking experiments, using anti-TGF-beta antibodies further revealed that also TGF-beta is mechanistically involved in the sCD83 induced reduction of bone destruction and cartilage damage as well as enhanced resolution of inflammation. Resolution of arthritis was associated with increased numbers of regulatory T cells, which are induced in a sCD83-IDO-TGF-beta dependent manner. Taken together, sCD83 represents an interesting approach for downregulating cytokine production, inducing regulatory T cells and inducing resolution of autoimmune arthritis.
CRIS-Team WoS Importer:2019-04-12

Soluble ST2 regulation by rhinovirus and 25(OH)-vitamin D3 in the blood of asthmatic children - Haag, Patricia; Sharma, H.; Rauh, Manfred; Zimmermann, Theodor; Vuorinen, T.; Papadopoulos, N. G.; Weiss, S. T.; Finotto, Susetta (Clinical and Experimental Immunology, 2018)
Paediatric asthma exacerbations are often caused by rhinovirus (RV). Moreover, 25(OH)-vitamin D3 (VitD3) deficiency during infancy was found associated with asthma. Here, we investigated the innate immune responses to RV and their possible modulation by 25(OH)-VitD3 serum levels in a preschool cohort of children with and without asthma. The innate lymphoid cell type 2 (ILC2)-associated marker, ST2, was found up-regulated in the blood cells of asthmatic children with low serum levels of 25(OH)-VitD3 in the absence of RV in their airways. Furthermore, in blood cells from control and asthmatic children with RV in their airways, soluble (s) ST2 (sST2) protein was found reduced. Asthmatic children with low 25(OH)-VitD3 in serum and with RV in vivo in their airways at the time of the analysis had the lowest sST2 protein levels in the peripheral blood compared to control children without RV and high levels of 25(OH)-VitD3. Amphiregulin (AREG), another ILC2-associated marker, was found induced in the control children with RV in their airways and low serum levels of 25(OH)-VitD3. In conclusion, the anti-inflammatory soluble form of ST2, also known as sST2, in serum correlated directly with interleukin (IL)-33 in the airways of asthmatic children. Furthermore, RV colonization in the airways and low serum levels of 25(OH)-VitD3 were found to be associated with down-regulation of sST2 in serum in paediatric asthma. These data indicate a counter-regulatory role of 25(OH)-VitD3 on RV-induced down-regulation of serum sST2 in paediatric asthma, which is relevant for the therapy of this disease.
EVALuna2:35820

Species differences of 11beta-hydroxysteroid dehydrogenase type 2 function in human and rat term placenta determined via LC-MS/MS - Heussner, Kirsten; Rübner, Matthias; Hübner, Hanna; Rascher, Wolfgang; Menendez-Castro, Carlos; Hartner, Andrea; Fahlbusch, Fabian B.; Rauh, Manfred (Placenta, 2016)
INTRODUCTION: Glucocorticoid-induced fetal programming has been associated with negative metabolic and cardiovascular sequelae in the adult. The placental enzyme 11beta-hydroxysteroid dehydrogenase type 2 (11β-HSD2) shields the fetus from maternal glucocorticoid excess by catalyzing the conversion of these hormones into biologically inactive derivatives. In vivo experiments addressing placental barrier function are mostly conducted in rodents. Therefore we set out to characterize species-specific differences of rat and human placental 11β-HSD2 steroid turnover, introducing Liquid Chromatography Tandem Mass-Spectrometry (LC-MS/MS) as a tool for rat tissue analysis. MATERIALS AND METHODS: Using LC-MS/MS we determined corticotropin-releasing hormone (CRH), cortisol (F), cortisone (E), corticosterone (B) and 11-dehydrocorticosterone (A) in human and rat placenta at term and measured the enzymatic 11β-HSD glucocorticoid conversion-rates in placental microsomes of both species. In parallel, further glucocorticoid derivatives and sex steroids were determined in the same placental samples. RESULTS: In contrast to the human placenta, we did not detect CRH in the rat placenta. While cortisol (F) and cortisone (E) were exclusively present in human term placenta (E/F-ratio >1), rat placenta showed significant levels of corticosterone (B) and 11-dehydrocorticosterone (A), with an A/B-ratio <1. In line with these species-specific findings, human placenta showed a prominent 11β-HSD2 activity, while in rat placenta higher 11β-HSD1 glucocorticoid turnover rates were determined. DISCUSSION: Placental steroid metabolism of human and rat shows relevant species-specific differences, especially regarding the barrier function of 11β-HSD2 at term. The exclusive expression of CRH in the human placenta further points to relevant differences in the regulation of parturition in rats. Consideration of these findings is warranted when transferring results from rodent placental glucocorticoid metabolism into humans.
EVALuna2:33462

Sulfasalazine impacts on ferroptotic cell death and alleviates the tumor microenvironment and glioma-induced brain edema. - Sehm, Tina; Fan, Zheng; Ghoochani, Ali; Rauh, Manfred; Engelhorn, Tobias; Minakaki, Georgia; Dörfler, Arnd; Klucken, Jochen; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai (Oncotarget, 2016)
The glutamate transporter xCT (SCL7a11, system Xc-, SXC) is an emerging key player in glutamate/cysteine/glutathione homeostasis in the brain and in cancer. xCT expression correlates with the grade of malignancy. Here, we report on the use of the U.S. Food and Drug Administration and EMA-approved xCT inhibitor, sulfasalazine (SAS) in gliomas. SAS does not affect cell viability in gliomas at concentrations below 200 µM. At higher concentrations SAS becomes gliomatoxic. Mechanistically SAS inhibits xCT and induces ferroptotic cell death in glioma cells. There is no evidence for impact on autophagic flux following SAS application. However, SAS can potentiate the efficacy of the standard chemotherapeutic and autophagy-inducing agent temozolomide (Temcat, Temodal or Temodar®). We also investigated SAS in non-transformed cellular constituents of the brain. Neurons and brain tissue are almost non-responding to SAS whereas isolated astrocytes are less sensitive towards SAS toxicity compared to gliomas. In vivo SAS treatment does not affect experimental tumor growth and treated animals revealed comparable tumor volume as untreated controls. However, SAS treatment resulted in reduced glioma-derived edema and, hence, total tumor volume burden as revealed by T2-weighted magnetic resonance imaging. Altogether, we show that SAS can be utilized for targeting the glutamate antiporter xCT activity as a tumor microenvironment-normalizing drug, while crucial cytotoxic effects in brain tumors are minor.

T Cell Costimulation Molecules CD80/86 Inhibit Osteoclast Differentiation by Inducing the IDO/Tryptophan Pathway - Bozec, Aline; Zaiss, Mario; Kagwiria, Rosebeth; Voll, Reinhard; Rauh, Manfred; Chen, Zhu; Müller-Schmucker, Sandra; Kroczek, Richard A.; Heinzerling, Lucie; Moser, Muriel; Mellor, Andrew L.; David, Jean-Pierre; et al. (Science Translational Medicine, 2014)
Bone resorption is seminal for the physiological remodeling of bone during life. However, this process needs to be strictly controlled; excessive bone resorption results in pathologic bone loss, osteoporosis, and fracture. We describe a control mechanism of bone resorption by the adaptive immune system. CD80/86, a pair of molecules expressed by antigen-presenting cells and involved in T cell costimulation, act as negative regulator for the generation of bone-resorbing osteoclasts. CD80/86-deficient mice were osteopenic because of increased osteoclast differentiation. CD80/86-deficient osteoclasts escaped physiological inhibition by CTLA-4 or regulatory T cells. Mechanistically, engagement of CD80/86 by CTLA-4 induced activation of the enzyme indoleamine 2,3-dioxygenase (IDO) in osteoclast precursors, which degraded tryptophan and promoted apoptosis. Concordantly, IDO-deficient mice also showed an osteopenic bone phenotype with higher numbers of osteoclast precursors and osteoclasts. Also, IDO-deficient mononuclear cells escaped the anti-osteoclastogenic effect of CTLA-4. This molecular mechanism was also present in humans because targeting CD80/86 by abatacept, a CTLA-4-immunoglobulin fusion protein, reduced, whereas blockade of CTLA-4 by ipilimumab antibody enhanced, the frequency of peripheral osteoclast precursors and osteoclastogenesis. In summary, these data show an important role of the adaptive immune system, in particular T cell CD80/86 costimulation molecules, in the physiological regulation of bone resorption and preservation of bone mass, as well as affect the understanding of the function of current and future drugs fostering or blocking the effects of CTLA-4 in humans.
EVALuna2:12912

Temozolomide toxicity operates in a xCT/SLC7a11 dependent manner and is fostered by ferroptosis - Sehm, Tina; Rauh, Manfred; Wiendieck, Kurt; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E. (Oncotarget, 2016)
The glutamate exchanger xCT (SLC7a11) is causally linked with the malignancy grade of brain tumors and represents a key player in glutamate, cystine and glutathione metabolism. Although blocking xCT is not cytotoxic for brain tumors, xCT inhibition disrupts the neurodegenerative and microenvironment-toxifying activity of gliomas. Here, we report on the use of various xCT inhibitors as single modal drugs and in combination with the autophagy-inducing standard chemotherapeutic agent temozolomide (Temodal/Temcad®, TMZ). xCT overexpressing cells (xCTOE) are more resistant to the FDA and EMA approved drug sulfasalazine (Azulfidine/Salazopyrin/Sulazine®, SAS) and RNAi-mediated xCT knock down (xCTKD) in gliomas increases the susceptibility towards SAS in rodent gliomas. In human gliomas, challenged xCT expression had no impact on SAS-induced cytotoxicity. Noteworthy, other xCT inhibitors such as erastin and sorafenib showed enhanced efficacy on xCTKD gliomas. In contrast, cytotoxic action of TMZ operates independently from xCT expression levels on rodent gliomas. Human glioma cells with silenced xCT expression display higher vulnerability towards TMZ alone as well as towards combined TMZ and SAS. Hence, we tested the partial xCT blockers and ferroptosis inducing agents erastin and sorafenib (Nexavar®, FDA and EMA-approved drug for lung cancer). Noteworthy, xCTOE gliomas withstand erastin and sorafenib-induced cell death in a concentration-dependent manner, whereas siRNA-mediated xCT knock down increased susceptibility towards erastin and sorafenib. TMZ efficacy can be potentiated when combined with erastin, however not by sorafenib. Moreover, gliomas with high xCT expression are more vulnerable towards combinatorial treatment with erastin-temozolomide. These results disclose that ferroptosis inducers are valid compounds for potentiating the frontline therapeutic agent temozolomide in a multitoxic approach.
EVALuna2:33853

The association of leptin secretion with cognitive performance in patients with eating disorders - Wollenhaupt, Carina; Wilke, Leonhard; Erim, Yesim; Rauh, Manfred; Steins-Loeber, Sabine; Paslakis, Georgios (Psychiatry Research, 2019)
This study is an investigation of neuropsychological performance in patients with anorexia nervosa, bulimia nervosa, and binge eating disorder and hormonal secretion patterns for ghrelin, leptin, insulin, and glucose. An oral glucose tolerance test (OGTT)was performed in a cohort of n = 30 female patients suffering from eating disorders as well as n = 20 control females. All participants underwent the Wisconsin Card Sorting Test (WCST), the Trail Making Test (TMT), and a go/no-go task using food vs. neutral stimuli. Patients with anorexia nervosa differed from controls in their leptin response to the OGTT. While the four groups under investigation did not differ in neuropsychological performance, we found leptin responses to the OGTT to be associated with performance in the food-specific go/no-go task. These preliminary results may indicate a putative association between leptin concentrations and neuropsychological performance, particularly in measures of inhibitory control. Further studies investigating the role of leptin in impulsive behaviors in eating disorders would be useful.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Eating disorder; Ghrelin; Go/no-go test; Leptin; Neuropsychological performance; Oral glucose tolerance test

The effect of dietary lipid quality in early life on serum LysoPC(18:2) levels and their association with adult blood glucose levels in intrauterine growth restricted rats - Kodde, Andrea; Mischke, Mona; Rakhshandehroo, Maryam; Voggel, Jenny; Fink, Gregor; Nuesken, Eva; Rauh, Manfred; Van Der Beek, Eline M.; Doetsch, Joerg; Nuesken, Kai-Dietrich (Nutrition & Metabolism, 2021)
Being born small-for-gestational-age, especially with subsequent catch-up growth, is associated with impaired metabolic health in later-life. We previously showed that a postnatal diet with an adapted lipid droplet structure can ameliorate some of the adverse metabolic consequences in intrauterine growth-restricted (IUGR) rats. The aim of the present work was to explore possible underlying mechanism(s) and potential biomarkers. To this end, serum metabolomics was performed in postnatal day (PN) 42 and PN96 samples of the above-mentioned rat offspring, born after uterine vasculature ligation. Blood samples were collected at PN42, directly after a postnatal dietary intervention with either complex lipid matrix (CLM) or control (CTRL) diet, and at PN96 after a subsequent western-style diet (WSD). Offspring of Non-operated (NOP) dams fed CTRL in early life were included as control group. In the PN42 metabolomics data, 11 co-abundance modules of metabolites were identified, of which four were significantly correlated to adult blood glucose levels at PN96. Further analyses showed that Lysophosphatidylcholine(18:2) (LysoPC(18:2)) levels were reduced by ligation (p < 0.01) and restored in CLM fed animals (p < 0.05). LysoPC(18:2) levels at PN42 correlated inversely with adult blood glucose levels. These data indicate that early-life LysoPC(18:2) blood levels may predict adult blood glucose levels and are affected by a postnatal diet with an adapted lipid droplet structure in IUGR offspring.
CRIS-Team WoS Importer:2021-12-03

The oxido-metabolic driver ATF4 enhances temozolamide chemo-resistance in human gliomas - Chen, Daishi; Rauh, Manfred; Buchfelder, Michael; Eyupoglu, Ilker Y.; Savaskan, Nicolai (Oncotarget, 2017)
Malignant gliomas are devastating neoplasia with limited curative treatment options. Temozolomide (TMZ, Temcat®, Temodal® or Temodar®) is a first-line treatment for malignant gliomas but the development of drug resistance remains a major concern. Activating transcription factor 4 (ATF4) is a critical oxido-metabolic regulator in gliomas, and its role in the pathogenesis of TMZ-resistance remains elusive. We investigated the effect of TMZ on human glioma cells under conditions of enhanced ATF4 expression (ATF4OE) and ATF4 knock down (ATF4KD). We monitored cell survival, ATF4 mRNA expression of ATF4 and xCT (SLC7a11) regulation within human gliomas. TMZ treatment induces a transcriptional response with elevated expression of ATF4, xCT and Nrf2, as a sign of ER stress and toxic cell damage response. ATF4 overexpression (ATF4OE) fosters TMZ resistance in human gliomas and inhibits TMZ-induced autophagy. Conversely, ATF4 suppression by small interfering RNAs (ATF4KD) leads to increased TMZ susceptibility and autophagy in comparison to wild type gliomas. ATF4OE gliomas show reduced cell cycle shift and apoptotic cell death, whereas ATF4KD gliomas reveal higher susceptibility towards cell cycle rearrangements. Hence, the migration capacity of ATF4OE glioma cells is almost not affected by TMZ treatment. In contrast, ATF4KD gliomas show a migratory stop following TMZ application. Mechanistically, xCT elevation is a consequence of ATF4 activation and increased levels of xCT amplifies ATF4-induced TMZ resistance. Our data show that ATF4 operates as a chemo-resistance gene in gliomas, and the tumor promoting function of ATF4 is mainly determined by its transcriptional target xCT. Therefore, therapeutic inactivation of ATF4 can be a promising strategy to overcome chemo-resistance and promote drug efficacy in human gliomas.
EVALuna2:34245

Tryptophan Catabolism to Serotonin and Kynurenine in Women Undergoing in-vitro Fertilization - Bodis, Jozsef; Sulyok, Endre; Koppan, Miklos; Varnagy, Akos; Premusz, Viktoria; Godony, Krisztina; Rascher, Wolfgang; Rauh, Manfred (Physiological Research, 2020)
This cross-sectional clinical study was designed to explore the impact of tryptophan-kynurenine and tryptophan-serotonin (5-HT) pathways on reproductive performance during in vitro fertilization (IVF). Paired serum and follicular fluid (FF) samples were obtained from 64 consecutive IVF patients. The analysis was done by using LC-MS/MS. Ovarian hyperstimulation resulted in decreased serum tryptophan (p<0.004), 5-HT (p<0.049) and kynurenine (p<0.001). FF levels of tryptophan (R=0.245, p<0.051), kynurenine (R=0.556, p<0.001) and 5-HT (R=0.523, p<0.001) were positively related to their respective serum levels. Clinical pregnancy was associated with higher serum 5-HT (p<0.045) and FF 5-HT (p<0.020) and lower kynurenine to 5-HT ratio (p<0.024). Chemical pregnancy was also positively related to FF 5-HT (R=0.362, p<0.024). Moreover, there was a direct relationship of the number of mature oocytes to the FF 5-HT (R=0.363, p<0.020) but it was inversely related to FF tryptophan to 5-HT and FF kynurenine to 5-HT ratios (R=-0.389, p<0.016 and R=-0.337, p<0.036, respectively). Multivariate logistic regression revealed that the number of mature oocytes was significantly influenced by FF 5-HT (β=0.473, p<0.001). In IVF patients ovarian hyperstimulation results in a reduction of the availability of tryptophan to catabolic pathways to kynurenine and 5-HT. Outcome measures improved significantly when 5-HT predominated over kynurenine.
CRIS-Team Scopus Importer:2021-04-19
Keywords: in vitro Fertilization; Kynurenine; Oocyte maturation; Serotonin; Tryptophan

Type 1 interferon alpha (IFN-a) regulation by respiratory viruses in pediatric asthma - Finotto, Susetta; Bergauer, Annika; Sopel, Nina; Kross, B.; Vuorinen, T.; Weiss, S. T.; Rauh, Manfred; Melichar, V. O.; Kiefer, Alexander; Zimmermann, Theodor; Ml, Kowalski; Jartti, T.; et al. (2017)
EVALuna2:33022

Ultra-long-term human salt balance studies reveal interrelations between sodium, potassium, and chloride intake and excretion - Birukov, Anna; Rakova, Natalia; Lerchl, Kathrin; Engberink, Rik H. G. Olde; Johannes, Bernd; Wabel, Peter; Moissl, Ulrich; Rauh, Manfred; Luft, Friedrich C.; Titze, Jens (American Journal of Clinical Nutrition, 2016)
BACKGROUND: The intake of sodium, chloride, and potassium is considered important to healthy nutrition and cardiovascular disease risk. Estimating the intake of these electrolytes is difficult and usually predicated on urine collections, commonly for 24 h, which are considered the gold standard. We reported on data earlier for sodium but not for potassium or chloride. OBJECTIVE: We were able to test the value of 24-h urine collections in a unique, ultra-long-term balance study conducted during a simulated trip to Mars. DESIGN: Four healthy men were observed while ingesting 12 g salt/d, 9 g salt/d, and 6 g salt/d, while their potassium intake was maintained at 4 g/d for 105 d. Six healthy men were studied while ingesting 12 g salt/d, 9 g salt/d, and 6 g salt/d, with a re-exposure of 12 g/d, while their potassium intake was maintained at 4 g/d for 205 d. Food intake and other constituents were recorded every day for each subject. All urine output was collected daily. RESULTS: Long-term urine recovery rates for all 3 electrolytes were very high. Rather than the expected constant daily excretion related to daily intake, we observed remarkable daily variation in excretion, with a 7-d infradian rhythm at a relatively constant intake. We monitored 24-h aldosterone excretion in these studies and found that aldosterone appeared to be the regulator for all 3 electrolytes. We report Bland-Altman analyses on the value of urine collections to estimate intake. CONCLUSIONS: A single 24-h urine collection cannot predict sodium, potassium, or chloride intake; thus, multiple collections are necessary. This information is important when assessing electrolyte intake in individuals.
EVALuna2:33935

Verbesserte Qualität gelagerter Erythrozytenkonzentrate durch maschinelle Autotransfusion - Münch, Frank; Purbojo, Ariawan; Wenzel, F.; Kohl, M.; Dittrich, Sven; Rauh, Manfred; Zimmermann, Rüdiger; Kwapil, Nicola (Die Anaesthesiologie, 2022)
Background The transfusion of packed red blood cells (PRBC) is associated with various side effects, including storage damage to PRBCs. The cells change their structure, releasing potassium as well as lactate. Mechanical rinsing, available in many hospitals, is able to remove toxic substances and possibly minimizes the negative side effects of transfusion. Objective The primary aim of our study was to improve the quality of PRBCs before transfusion. The effects of different washing solutions on PRBC quality were analyzed. Material and methods This in vitro study compares 30 mechanically washed PRBCs. They were either processed with standard normal saline 0.9% (n = 15, N group) or a hemofiltration solution containing 4 mmol/l potassium (n = 15, HF group) by a mechanical rinsing device (Xtra, LivaNova, Munich, Germany). A subgroup analysis was performed based on the storage duration of the processed PRBCs (7, 14, 37 days). Samples were taken before washing (EKpra), immediately after washing (EKpost) and 10 h later (EKpost10h), after storage in the "wash medium" at room temperature. Concentrations of ATP (probability of survival in transfused erythrocytes), lactate, citrate and electrolytes (potassium, sodium, chloride, calcium) were tested. Results and conclusion Mechanical rinsing improves pretransfusion quality of PRBC. Washing with a hemofiltration solution results in a more physiological electrolyte composition. Even 10 h after mechanical rinsing with a hemofiltration solution, the quality of 37-day-old PRBC is comparable to young PRBC that have been stored for 7 days and have not been washed. Washing stored PRBC increases the ATP content, which subsequently leads to an increased probability of survival of red cells after transfusion.
CRIS-Team WoS Importer:2022-08-26

Virtual reality jogging as a novel exposure paradigm for the acute urge to be physically active in patients with eating disorders: Implications for treatment - Paslakis, Georgios; Fauck, Vanessa; Roeder, Kathrin; Rauh, Elisabeth; Rauh, Manfred; Erim, Yesim (International Journal of Eating Disorders, 2017)
<br
EVALuna2:24045

Vitamin D3 resolved human and experimental asthma via B lymphocyte-induced maturation protein 1 in T cells and innate lymphoid cells. - Grund, Janina; Krammer, Susanne; Yang, Zuqin; Mitländer, Hannah; Rauh, Manfred; Zirlik, Sabine; Kiefer, Alexander; Zimmermann, Theodor; Rieker, Ralf; Geppert, Carol-Immanuel; Papadopoulos, Nikolaos G.; Neurath-Finotto, Susetta (Journal of Allergy and Clinical Immunology: Global, 2023)
BACKGROUND: Vitamin D3 (VitD3) is known to have immunomodulatory functions, and VitD3 deficiency is associated with more severe asthma. OBJECTIVE: We aimed to assess the immunoregulatory effects of VitD3 food supplementation on asthma manifestation, with particular focus on T cells and type 2 innate lymphoid cells. METHODS: Preschool children and adult asthmatic cohorts were analyzed in the context of VitD3 supplementation and serum levels. In a murine model of ovalbumin-induced asthma, effects of diet VitD3 sufficiency and deficiency on T cells and type 2 innate lymphoid cells immune mechanisms were investigated. RESULTS: We found less severe and better-controlled asthma phenotypes along with reduced need for steroid medication in preschool children and asthmatic adults with VitD3 supplementation. VitD3 serum levels correlated with B lymphocyte-induced maturation protein 1 (Blimp-1) expression in blood peripheral mononuclear cells. VitD3-supplement-fed mice showed decreased asthmatic traits, with a decrease in IgE serum levels, reduced airway mucus, and increased IL-10 production by lung cells. Furthermore, we discovered an upregulation of effector T cells and Blimp-1+ lung tissue-resident memory T cells as well as induction of anti-inflammatory Blimp-1+ lung innate lymphoid cells producing IL-10. CONCLUSION: Supplementing VitD3 resulted in amelioration of clinical asthma manifestations in human studies as well as in experimental allergic asthma, indicating that VitD3 shifts proinflammatory immune responses to anti-inflammatory immune responses via upregulating Blimp-1 in lung innate lymphoid cells and tissue-resident memory cells.
EVALuna2:544627
Keywords: Allergic asthma; pediatric asthma; adult asthma; vitamin D3; vitamin D3 supplementation; TRM; ILC2s; Blimp-1; resolution of asthma

Water Conservation Overrides Osmotic Diuresis During SGLT2 Inhibition in Patients With Heart Failure - Marton, Adriana; Saffari, Seyed Ehsan; Rauh, Manfred; Sun, Ruo Ning; Nagel, Armin Michael; Linz, Peter; Lim, Tzy Tiing; Takase-Minegishi, Kaoru; Pajarillaga, Anastacia; Saw, Sharon; Morisawa, Norihiko; Yam, Wan Keat; et al. (Journal of the American College of Cardiology, 2024)
Background: Sodium-glucose cotransporter 2 inhibitors are believed to improve cardiac outcomes due to their osmotic diuretic potential. Objectives: The goal of this study was to test the hypothesis that vasopressin-driven urine concentration overrides the osmotic diuretic effect of glucosuria induced by dapagliflozin treatment. Methods: DAPA-Shuttle1 (Hepato-renal Regulation of Water Conservation in Heart Failure Patients With SGLT-2 Inhibitor Treatment) was a single-center, double-blind, randomized, placebo-controlled trial, in which patients with chronic heart failure NYHA functional classes I/II and reduced ejection fraction were randomly assigned to receive dapagliflozin 10 mg daily or placebo (1:1) for 4 weeks. The primary endpoint was change from baseline in urine osmolyte concentration. Secondary endpoints included changes in copeptin levels and solute free water clearance. Results: Thirty-three randomized, sodium-glucose cotransporter 2 inhibitor–naïve participants completed the study, 29 of whom (placebo: n = 14; dapagliflozin: n = 15) provided accurate 24-hour urine collections (mean age 59 ± 14 years; left ventricular ejection fraction 31% ± 9%). Dapagliflozin treatment led to an isolated increase in urine glucose excretion by 3.3 mmol/kg/d (95% CI: 2.51–4.04; P < 0.0001) within 48 hours (early) which persisted after 4 weeks (late; 2.7 mmol/kg/d [95% CI: 1.98–3.51]; P < 0.0001). Dapagliflozin treatment increased serum copeptin early (5.5 pmol/L [95% CI: 0.45-10.5]; P < 0.05) and late (7.8 pmol/L [95% CI: 2.77–12.81]; P < 0.01), leading to proportional reductions in free water clearance (early: −9.1 mL/kg/d [95% CI: −14 to −4.12; P < 0.001]; late: −11.0 mL/kg/d [95% CI: −15.94 to −6.07; P < 0.0001]) and elevated urine concentrations (late: 134 mmol/L [95% CI: 39.28–229.12]; P < 0.01). Therefore, urine volume did not significantly increase with dapagliflozin (mean difference early: 2.8 mL/kg/d [95% CI: −1.97 to 7.48; P = 0.25]; mean difference late: 0.9 mL/kg/d [95% CI: −3.83 to 5.62]; P = 0.70). Conclusions: Physiological-adaptive water conservation eliminated the expected osmotic diuretic potential of dapagliflozin and thereby prevented a glucose-driven increase in urine volume of approximately 10 mL/kg/d · 75 kg = 750 mL/kg/d. (Hepato-renal Regulation of Water Conservation in Heart Failure Patients With SGLT-2 Inhibitor Treatment [DAPA-Shuttle1]; NCT04080518).
CRIS-Team Scopus Importer:2024-04-12
Keywords: aestivation; decongestion; longevity; water conservation